Covalent treatment of keratin-containing materials

By applying reducing agents and monomers to the keratin-containing materials to form covalent bonds, the problem of temporary effects of existing hair care products is solved, significantly improving the hydrophobicity and strength of hair and nails, and achieving a more lasting protective effect.

CN111936117BActive Publication Date: 2025-01-07LIVING PROOF INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN201880084855.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2017-11-17
Filing Date
2018-11-16
Publication Date
2025-01-07
Estimated Expiration
2038-11-16

AI Technical Summary

Technical Problem

Conditioning molecules in existing hair care products are deposited on the hair surface through non-covalent interactions, resulting in short-lived effects and difficulty in maintaining healthy native-like hair and nails for a long time.

Method used

Long-term protection is provided by applying reducing agents and monomers to the keratin-containing material to form covalent bonds, improving the hydrophobicity of hair and nails, extreme tensile strength and protein loss values.

Benefits of technology

Significantly improves the hydrophobicity and strength of hair and nails, extends the care effect, reduces the frequency of care, and provides longer-lasting protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111936117B_ABST
    Figure CN111936117B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for grafting monomers and polymer materials on keratin-containing materials to provide a covalent coating on the keratin-containing material. A mixture comprising a reducing agent is applied to a sample of keratin-containing material. Then, the sample of keratin-containing material comprises a plurality of free thiol groups. A monomer is applied to the sample of keratin-containing material. The free thiol groups react with the monomer to form a plurality of covalent bonds between the free thiol groups and the monomer. The reducing agent and the monomer may be applied separately, semi-simultaneously or simultaneously. The disclosed method may be performed with or without a catalyst. The disclosed method may be performed with or without an additive.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Related Applications

[0002] This application claims the benefit of priority to U.S. Provisional Patent Application Serial No. 62 / 587,896, filed on November 17, 2017. Background Art

[0003] The human body contains many keratin components, including hair, eyebrows, eyelashes, fingernails and toenails. These protein-based structures enhance the body's function in a variety of ways - for example, hair helps protect the body from extreme temperatures, eyelashes and eyebrows keep debris out of the eyes, and fingernails provide counterpressure for the fingertips, which improves dexterity.

[0004] These keratinous materials are primarily composed of the protein keratin, but in their native form also contain important small molecule components that improve functionality. For example, fingernails and toenails function best (i.e., have optimal mechanical properties and flexibility) when they contain functional phospholipid molecules. 1 These molecules are removed during normal wear and tear and are particularly sensitive to harsh cleaning solvents. Consumers can partially mitigate this decline in function by using moisturizers, but they must often take the time to reapply these products. A long-term approach to achieving healthy, native-like nails remains an unmet need.

[0005] Likewise, upon emerging from the follicle, mammalian hair is covered by a thin layer of covalently bound lipids of 18-methyleicosanoic acid (18-MEA) that is bound to the outermost proteinaceous membrane layer ( Figure 1 ). 18-MEA molecules are covalently attached to the outermost keratin layer of the epidermis via thioester bonds and impart enhanced hydrophobicity and a styling, smooth feel to the hair while acting as a boundary lubricant to reduce frictional resistance. 2-6

[0006] When hair is repeatedly weathered in response to stress such as washing, drying, brushing, combing, rubbing, styling and sun exposure, the 18-MEA layer is lost and the hair surface becomes more hydrophilic, negatively charged and has a damaged feeling. There are many products that can address this demand, including conditioners, leave-in creams and smooth oils. These products contain emollients and conditioning molecules such as natural oil derivatives, long-chain alcohols, carboxylic acids and quaternary ammonium compounds, but because the conditioning molecules in these products are only deposited on the surface of the hair via non-covalent interactions, they are usually washed off from the hair and the effect is short-lived. Therefore, consumers must often spend time reapplying these products. The long-term method of obtaining healthy native-like hair is a demand that is still not met. Summary of the invention

[0007] In one aspect, the present disclosure provides a method of treating a keratin-containing material comprising:

[0008] i) providing a sample of a keratin-containing material comprising a plurality of disulfide bonds;

[0009] ii) applying a mixture to the keratin-containing material sample for a period of time, the mixture comprising a reducing agent at a concentration of about 0.1 wt. % to about 15 wt. %, thereby producing a reduced keratin-containing material sample, wherein the reduced keratin-containing material sample comprises a plurality of free thiol groups; and

[0010] iii) applying a monomer to the reduced keratin-containing material sample, wherein the monomer is selected from acrylates, methacrylates, monomers comprising vinyl groups, monomers comprising alkyne groups and monomers comprising maleimide groups, thereby forming a plurality of covalent bonds between the free thiol groups and the monomer.

[0011] In another aspect, the present disclosure provides a method of treating a keratin-containing material comprising:

[0012] i) providing a sample of a keratin-containing material comprising a plurality of disulfide bonds;

[0013] ii) applying a mixture comprising a reducing agent and a catalyst to a sample of keratin-containing material for a period of time, the mixture comprising a reducing agent at a concentration of about 0.1 wt % to about 15 wt %, wherein the sample of keratin-containing material comprises a plurality of free thiol groups; and

[0014] iii) applying a monomer to the keratin-containing material sample, wherein the monomer is selected from acrylates, methacrylates, monomers comprising vinyl groups, monomers comprising alkyne groups and monomers comprising maleimide groups, thereby forming a plurality of covalent bonds between the free thiol groups and the monomer.

[0015] In another aspect, the present disclosure provides a method of treating a keratin-containing material comprising:

[0016] i) providing a sample of keratin-containing material comprising a plurality of disulfide bonds; and

[0017] ii) applying a mixture comprising a reducing agent and a monomer, wherein the reducing agent concentration is from about 0.1 wt % to about 15 wt % to the sample of keratin-containing material for a period of time; wherein the monomer is selected from acrylates, methacrylates, monomers comprising vinyl groups, monomers comprising alkyne groups, and monomers comprising maleimide groups, thereby forming a plurality of free thiol groups, which react with the monomer to form a plurality of covalent bonds between the free thiol groups and the monomer.

[0018] In another aspect, the present disclosure provides a method for treating a keratin-containing material, wherein the hydrophobicity of the keratin-containing material is improved, the method comprising:

[0019] i) providing a sample of a keratin-containing material comprising a plurality of disulfide bonds;

[0020] ii) applying a mixture comprising a reducing agent to a sample of keratin-containing material for a period of time, wherein the sample of keratin-containing material comprises a plurality of free thiol groups; and

[0021] iii) applying a monomer to the keratin-containing material sample, wherein the monomer is selected from the group consisting of acrylates, methacrylates, monomers comprising vinyl groups, monomers comprising alkyne groups and monomers comprising maleimide groups, thereby forming a plurality of covalent bonds between the free thiol groups and the monomer;

[0022] Thereby improving the hydrophobicity of keratin-containing materials.

[0023] In another aspect, the present disclosure provides a method for treating a keratin-containing material, wherein the hydrophobicity of the keratin-containing material is improved, the method comprising:

[0024] i) providing a sample of a keratin-containing material comprising a plurality of disulfide bonds;

[0025] ii) applying a mixture comprising a reducing agent and a catalyst to a sample of keratin-containing material for a period of time, wherein the sample of keratin-containing material comprises a plurality of free thiol groups; and

[0026] iii) applying a monomer to the keratin-containing material sample, wherein the monomer is selected from the group consisting of acrylates, methacrylates, monomers comprising vinyl groups, monomers comprising alkyne groups and monomers comprising maleimide groups, thereby forming a plurality of covalent bonds between the free thiol groups and the monomer;

[0027] Thereby improving the hydrophobicity of keratin-containing materials.

[0028] In another aspect, the present disclosure provides a method for treating a keratin-containing material, wherein the hydrophobicity of the keratin-containing material is improved, the method comprising:

[0029] i) providing a sample of keratin-containing material comprising a plurality of disulfide bonds; and

[0030] ii) applying a mixture comprising a reducing agent and a monomer to the sample of keratin-containing material for a period of time; wherein the monomer is selected from acrylates, methacrylates, monomers comprising vinyl groups, monomers comprising alkyne groups and monomers comprising maleimide groups, thereby forming a plurality of free thiol groups, which react with the monomer to form a plurality of covalent bonds between the free thiol groups and the monomer;

[0031] Thereby improving the hydrophobicity of keratin-containing materials.

[0032] In another aspect, the present disclosure provides a method of treating a keratin-containing material, wherein the ultimate tensile strength of the keratin-containing material is improved, the method comprising:

[0033] i) providing a sample of a keratin-containing material comprising a plurality of disulfide bonds;

[0034] ii) applying a mixture comprising a reducing agent to a sample of keratin-containing material for a period of time, wherein the sample of keratin-containing material comprises a plurality of free thiol groups; and

[0035] iii) applying a monomer to the keratin-containing material sample, wherein the monomer is selected from the group consisting of acrylates, methacrylates, monomers comprising vinyl groups, monomers comprising alkyne groups and monomers comprising maleimide groups, thereby forming a plurality of covalent bonds between the free thiol groups and the monomer;

[0036] Thereby improving the ultimate tensile strength of keratin-containing materials.

[0037] In another aspect, the present disclosure provides a method of treating a keratin-containing material, wherein the ultimate tensile strength of the keratin-containing material is improved, the method comprising:

[0038] i) providing a sample of a keratin-containing material comprising a plurality of disulfide bonds;

[0039] ii) applying a mixture comprising a reducing agent and a catalyst to a sample of keratin-containing material for a period of time, wherein the sample of keratin-containing material comprises a plurality of free thiol groups; and

[0040] iii) applying a monomer to the keratin-containing material sample, wherein the monomer is selected from the group consisting of acrylates, methacrylates, monomers comprising vinyl groups, monomers comprising alkyne groups and monomers comprising maleimide groups, thereby forming a plurality of covalent bonds between the free thiol groups and the monomer;

[0041] Thereby improving the ultimate tensile strength of keratin-containing materials.

[0042] In another aspect, the present disclosure provides a method of treating a keratin-containing material, wherein the ultimate tensile strength of the keratin-containing material is improved, the method comprising:

[0043] i) providing a sample of keratin-containing material comprising a plurality of disulfide bonds; and

[0044] ii) applying a mixture comprising a reducing agent and a monomer to the sample of keratin-containing material for a period of time; wherein the monomer is selected from acrylates, methacrylates, monomers comprising vinyl groups, monomers comprising alkyne groups and monomers comprising maleimide groups, thereby forming a plurality of free thiol groups, which react with the monomer to form a plurality of covalent bonds between the free thiol groups and the monomer;

[0045] Thereby improving the ultimate tensile strength of keratin-containing materials.

[0046] In another aspect, the present disclosure provides a method of treating a keratin-containing material, wherein the protein loss level of the keratin-containing material is improved, the method comprising:

[0047] i) providing a sample of a keratin-containing material comprising a plurality of disulfide bonds;

[0048] ii) applying a mixture comprising a reducing agent to a sample of keratin-containing material for a period of time, wherein the sample of keratin-containing material comprises a plurality of free thiol groups; and

[0049] iii) applying a monomer to the keratin-containing material sample, wherein the monomer is selected from the group consisting of acrylates, methacrylates, monomers comprising vinyl groups, monomers comprising alkyne groups and monomers comprising maleimide groups, thereby forming a plurality of covalent bonds between the free thiol groups and the monomer;

[0050] Thereby improving the protein loss value of keratin-containing materials.

[0051] In another aspect, the present disclosure provides a method of treating a keratin-containing material, wherein the protein loss level of the keratin-containing material is improved, the method comprising:

[0052] i) providing a sample of a keratin-containing material comprising a plurality of disulfide bonds;

[0053] ii) applying a mixture comprising a reducing agent and a catalyst to a sample of keratin-containing material for a period of time, wherein the sample of keratin-containing material comprises a plurality of free thiol groups; and

[0054] iii) applying a monomer to the keratin-containing material sample, wherein the monomer is selected from the group consisting of acrylates, methacrylates, monomers comprising vinyl groups, monomers comprising alkyne groups and monomers comprising maleimide groups, thereby forming a plurality of covalent bonds between the free thiol groups and the monomer;

[0055] Thereby improving the protein loss value of keratin-containing materials.

[0056] In another aspect, the present disclosure provides a method of treating a keratin-containing material, wherein the protein loss level of the keratin-containing material is improved, the method comprising:

[0057] i) providing a sample of keratin-containing material comprising a plurality of disulfide bonds; and

[0058] ii) applying a mixture comprising a reducing agent and a monomer to the sample of keratin-containing material for a period of time; wherein the monomer is selected from acrylates, methacrylates, monomers comprising vinyl groups, monomers comprising alkyne groups and monomers comprising maleimide groups, thereby forming a plurality of free thiol groups, which react with the monomer to form a plurality of covalent bonds between the free thiol groups and the monomer;

[0059] Thereby improving the protein loss value of keratin-containing materials.

[0060] In another aspect, the present disclosure provides a method for treating a keratin-containing material, wherein the denaturation temperature of the keratin-containing material is improved, the method comprising:

[0061] i) providing a sample of a keratin-containing material comprising a plurality of disulfide bonds;

[0062] ii) applying a mixture comprising a reducing agent to a sample of keratin-containing material for a period of time, wherein the sample of keratin-containing material comprises a plurality of free thiol groups; and

[0063] iii) applying a monomer to the keratin-containing material sample, wherein the monomer is selected from the group consisting of acrylates, methacrylates, monomers comprising vinyl groups, monomers comprising alkyne groups and monomers comprising maleimide groups, thereby forming a plurality of covalent bonds between the free thiol groups and the monomer;

[0064] Thereby improving the denaturation temperature of keratin-containing materials.

[0065] In another aspect, the present disclosure provides a method for treating a keratin-containing material, wherein the denaturation temperature of the keratin-containing material is improved, the method comprising:

[0066] i) providing a sample of a keratin-containing material comprising a plurality of disulfide bonds;

[0067] ii) applying a mixture comprising a reducing agent and a catalyst to a sample of keratin-containing material for a period of time, wherein the sample of keratin-containing material comprises a plurality of free thiol groups; and

[0068] iii) applying a monomer to the keratin-containing material sample, wherein the monomer is selected from the group consisting of acrylates, methacrylates, monomers comprising vinyl groups, monomers comprising alkyne groups and monomers comprising maleimide groups, thereby forming a plurality of covalent bonds between the free thiol groups and the monomer;

[0069] Thereby improving the denaturation temperature of keratin-containing materials.

[0070] In another aspect, the present disclosure provides a method for treating a keratin-containing material, wherein the denaturation temperature of the keratin-containing material is improved, the method comprising:

[0071] i) providing a sample of keratin-containing material comprising a plurality of disulfide bonds; and

[0072] ii) applying a mixture comprising a reducing agent and a monomer to the sample of keratin-containing material for a period of time; wherein the monomer is selected from acrylates, methacrylates, monomers comprising vinyl groups, monomers comprising alkyne groups and monomers comprising maleimide groups, thereby forming a plurality of free thiol groups, which react with the monomer to form a plurality of covalent bonds between the free thiol groups and the monomer;

[0073] Thereby improving the denaturation temperature of keratin-containing materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0074] Figure 1 Depicted is a cartoon illustrating the covalent attachment of the hydrophilic molecule 18-MEA to the hair surface via a thioester bond.

[0075] Figure 2A Depicted is the conversion of the disulfide functionality constituting the amino acid cysteine ​​to a free thiol in the presence of a reducing agent.

[0076] Figure 2B Schematic representation of the polymerization of free thiol functional groups with olefin-containing molecules such as acrylates or vinyl ethers using a free radical thiol-ene reaction mediated by a photoinitiator and UV light.

[0077] Figure 2C Schematic representation of a free thiol function acting as a nucleophile and adding to the double bond of an electrophilic olefin-containing monomer such as an acrylate or maleimide.

[0078] Figure 3 Schematic representation of the proposed mechanism for activation on water in the thiol-Michael system.

[0079] Figure 4 Schematic representation of the reaction of DTNB with free thiols to form mixed disulfides and the UV-active molecule TNB.

[0080] Figure 5Depicted is the visual appearance of reduced hair fibers at various liquor ratios.

[0081] Figure 6 A kinetic study of the reduction of hair with a reducing agent is depicted.

[0082] Figure 7 Schematic representation of the reaction of NEM with free thiol groups to form stable thioethers.

[0083] Figure 8 Schematic representation of UV-mediated free radical thiol-ene coupling with hydrophobic acrylates or vinyl ethers.

[0084] Fig. 9 Exemplary monomers useful in the disclosed methods of treating keratin-containing materials are depicted.

[0085] Fig.10 Schematic representation of the thiol-Michael addition reaction via a nucleophile-initiated pathway.

[0086] Fig.11 Depicted are FTIR spectra of hair grafted with exemplary acrylate monomers at various monomer to thiol ratios for 3 hours.

[0087] Fig.12 Depicted are FTIR spectra of hair grafted with exemplary acrylate monomers at various monomer to thiol ratios for 3 hours.

[0088] Fig.13 Depicted are FTIR spectra of hair grafted with exemplary acrylate monomers at various catalyst concentrations for 1 hour.

[0089] Fig.14 Depicted are FTIR spectra of hair grafted with exemplary acrylate monomers in a mixed aqueous solvent system for 1 hour.

[0090] Fig.15 Schematic representation of the thiol-Michael addition reaction via a base-initiated pathway.

[0091] Fig.16 Depicted are FTIR spectra of hair grafted with exemplary acrylate monomers at various secondary amine catalyst ratios for 3 hours.

[0092] Fig.17 Depicted are FTIR spectra of hair grafted with exemplary acrylate monomers at various monomer to thiol ratios for 3 hours.

[0093] Fig.18 Depicted are FTIR spectra of hair grafted with exemplary acrylate monomers in an aqueous solvent system for 1 hour.

[0094] Fig.19 Depicted are the amount of thiol groups consumed at different time points during grafting using an exemplary maleimide monomer.

[0095] Fig. 20A Depicted is the carbonyl peak region of the FTIR spectrum of hair grafted with an exemplary maleimide monomer in an aqueous solvent system for 1 hour.

[0096] Fig. 20B Depicted are the alkyl peak regions of the FTIR spectra of hair grafted with an exemplary maleimide monomer in an aqueous solvent system for 1 hour.

[0097] Fig.21 Depicted is the FTIR spectrum of hair grafted with an exemplary acrylate monomer simultaneously with an amine and a reducing agent for 1 hour.

[0098] Fig. 22 Depicted are FTIR spectra of hair grafted with an exemplary acrylate monomer simultaneously with an amine and various concentrations of a reducing agent for 1 hour.

[0099] Fig.23A Depicted are the alkyl peak regions of the FTIR spectra after 30 minutes of grafting with an exemplary acrylate monomer at various monomer to thiol ratios.

[0100] Fig. 23B Depicted are the carbonyl peak regions of FTIR spectra of hair grafted with exemplary acrylate monomers at various monomer to thiol ratios for 30 minutes.

[0101] Fig.24 Depicted are FTIR spectra of hair after simultaneous grafting with an exemplary acrylate monomer with an amine and a reducing agent for different reaction times.

[0102] Fig.25 Depicted are the carbonyl peak regions of the FTIR spectra of hair after a two-step grafting process using an exemplary acrylate monomer with either a secondary or tertiary amine and a reducing agent.

[0103] Fig.26A Depicted are the carbonyl peak regions of FTIR spectra of hair grafted with exemplary acrylate monomers simultaneously with varying concentrations of tertiary amine and reducing agent for 15 minutes.

[0104] Fig.26B Depicted are the carbonyl peak regions of the FTIR spectra of hair grafted with an exemplary acrylate monomer simultaneously with higher concentrations of a tertiary amine and a reducing agent for 15 minutes.

[0105] Fig.26CDepicted are the carbonyl peak regions of FTIR spectra of hair grafted with exemplary acrylate monomers simultaneously with varying concentrations of tertiary amines and reducing agents for 1 hour.

[0106] Fig.26D Depicted are the carbonyl peak regions of the FTIR spectra of hair grafted with exemplary acrylate monomers simultaneously with higher concentrations of tertiary amine and reducing agent for 1 hour.

[0107] Fig.27A Depicted are the carbonyl peak regions of FTIR spectra of hair after simultaneous grafting of an exemplary acrylate monomer with an exemplary reducing agent on bleached hair for different reaction times.

[0108] Fig.27B Depicted are the alkyl peak regions of the FTIR spectra of hair after different reaction times of simultaneous grafting of an exemplary acrylate monomer with an exemplary reducing agent on bleached hair.

[0109] Fig.28A Depicted are the carbonyl peak regions of FTIR spectra of hair after simultaneous grafting of an exemplary acrylate monomer with an exemplary reducing agent on bleached hair for different reaction times.

[0110] Fig.28B Depicted are the alkyl peak regions of the FTIR spectra of hair after different reaction times of simultaneous grafting of an exemplary acrylate monomer with an exemplary reducing agent on bleached hair.

[0111] Fig.29 Depicted is the FTIR spectrum of hair after grafting with exemplary acrylate monomers on thermally damaged hair.

[0112] Fig.30 Exemplary acrylate monomers for simultaneous grafting are depicted.

[0113] Fig.31 Depicted are the carbonyl peak regions of FTIR spectra of hair grafted simultaneously with different exemplary acrylate monomers, tertiary amines, and reducing agents for 15 minutes.

[0114] Fig.32A Depicted are the carbonyl peak regions of the FTIR spectra of virgin hair after semi-simultaneous grafting with exemplary PEG-diacrylate monomers at various weight ratios of the mixture to the hair sample.

[0115] Fig.32B Depicted are the carbonyl peak regions of the FTIR spectra of bleached hair after semi-simultaneous grafting with exemplary PEG-diacrylate monomers at various weight ratios of the mixture to the hair sample.

[0116] Fig.33Depicted are the carbonyl peak regions of the FTIR spectra of hair after semi-simultaneous grafting with an exemplary PEG-diacrylate monomer with varying concentrations of catalyst.

[0117] Fig.34 Depicted are the carbonyl peak regions of the FTIR spectra of hair after semi-simultaneous grafting with an exemplary PEG-diacrylate monomer following application of various concentrations of a reducing agent.

[0118] Fig.35 Depicted are the carbonyl peak regions of the FTIR spectra of hair after semi-simultaneous grafting with an exemplary PEG-diacrylate monomer at various pH values.

[0119] Fig.36A Depicted are the carbonyl peak regions of the FTIR spectra of native hair after semi-simultaneous grafting with various PEG-diacrylate monomers.

[0120] Fig.36B Depicted are the alkyl peak regions of the FTIR spectra of native hair after semi-simultaneous grafting with various PEG-diacrylate monomers.

[0121] Fig.37A Depicted are the carbonyl peak regions of the FTIR spectra of bleached hair after semi-simultaneous grafting with various PEG-diacrylate monomers.

[0122] Fig.37B Depicted are the alkyl peak regions of the FTIR spectra of bleached hair after semi-simultaneous grafting with various PEG-diacrylate monomers.

[0123] Fig.38 Depicted are FTIR spectra showing virgin hair (dashed line) and treated hair grafted with exemplary monomers (solid line).

[0124] Fig.39A Depicted are the absolute weight gains of hair locks treated with various monomer to thiol to catalyst ratios.

[0125] Fig.39B Plotted are monomer conversions for locks treated with various monomer to thiol to catalyst ratios.

[0126] Fig.40 Depicted are frizzy hair locks grafted with solutions containing different concentrations of exemplary monomers based on the disclosed method.

[0127] Fig.41 Depicted is a hairpiece with one side grafted with an exemplary acrylate monomer (left) and one side left untreated (right).

[0128] Fig.42Depicted is a wig form with one side reduced only (left) and one side reduced and grafted with an exemplary acrylate monomer (right) and then curled and exposed to 90% relative humidity for 15 minutes.

[0129] Fig.43 Depicted is a hair model with one side reduced and grafted with an exemplary acrylate monomer (left) compared to untreated hair (right).

[0130] Fig.44 The gloss properties of hair locks grafted with exemplary vinyl ether monomers based on the disclosed methods are depicted.

[0131] Fig.45A A scanning electron micrograph (SEM) of a tangled native hair is depicted.

[0132] Fig.45B A SEM of the native hair cortex is depicted.

[0133] Fig.45C Depicted is a SEM of knotted bleached hair.

[0134] Fig.45D Depicted is a SEM of the cortex of bleached hair.

[0135] Fig.45E Depicted is a SEM of tangled reduced bleached hair.

[0136] Fig.45F Depicted is a SEM of the reduced bleached hair cortex.

[0137] Figure 45G Depicted is a SEM of knotted reduced and grafted bleached hair.

[0138] Figure 45H Depicted is a SEM of the reduced and grafted bleached hair cortex.

[0139] Fig.46 Depicted are the carbonyl peak regions of the FTIR spectra of hair after semi-simultaneous grafting with an exemplary PEG-diacrylate monomer and various fatty acid additives.

[0140] Fig.47 Depicted are protein loss values ​​for hair following semi-simultaneous grafting of an exemplary PEG-diacrylate monomer with various fatty acid additives.

[0141] Fig.48A Depicted are the carbonyl peak regions of the FTIR spectra of hair after semi-simultaneous grafting with an exemplary PEG-diacrylate monomer and various amino acid or peptide mixture additives.

[0142] Fig.48BDepicted are the alkyl peak regions of the FTIR spectra of hair after semi-simultaneous grafting with an exemplary PEG-diacrylate monomer and various amino acid or peptide mixture additives.

[0143] Fig.49 Depicted are the carbonyl peak regions of the FTIR spectra of hair after semi-simultaneous grafting with an exemplary PEG-diacrylate monomer and various amino acids or N-acetylamino acid additives.

[0144] Fig.50 Depicted are protein loss values ​​for hair following semi-simultaneous grafting of an exemplary PEG-diacrylate monomer with various amino acids or N-acetylamino acid additives.

[0145] Fig.51 Depicted are protein loss values ​​for hair following semi-simultaneous grafting with an exemplary PEG-diacrylate monomer and various concentrations of an exemplary N-acetylamino acid additive.

[0146] Fig.52A Depicted are the carbonyl peak regions of FTIR spectra of hair after semi-simultaneous grafting with an exemplary PEG-diacrylate monomer and various post-treatment times with gluconolactone and citric acid.

[0147] Fig.52B Depicted are the alkyl peak regions of the FTIR spectra of hair after semi-simultaneous grafting with an exemplary PEG-diacrylate monomer and various post-treatment times with gluconolactone and citric acid.

[0148] Fig.53A Depicted are the carbonyl peak regions of FTIR spectra of hair after semi-simultaneous grafting with an exemplary PEG-diacrylate monomer and various post-treatment times with gluconolactone and citric acid.

[0149] Fig.53B Depicted are the alkyl peak regions of the FTIR spectra of hair after semi-simultaneous grafting with an exemplary PEG-diacrylate monomer and various post-treatment times with gluconolactone and citric acid.

[0150] Fig.54 Depicted are the denaturation temperatures of untreated hair and hair after semi-simultaneous grafting with an exemplary PEG-diacrylate monomer and post-treatment with gluconolactone and citric acid.

[0151] Fig.55 Depicted are protein loss values ​​for hair following semi-simultaneous grafting with an exemplary PEG-diacrylate monomer and application of gluconolactone and citric acid post-treatment for varying periods of time.

[0152] Fig.56ADepicted are the carbonyl peak regions of FTIR spectra of hair after semi-simultaneous grafting with an exemplary PEG-diacrylate monomer and post-treatment with gluconolactone and citric acid at different pH values.

[0153] Fig.56B Depicted are the alkyl peak regions of the FTIR spectra of hair after semi-simultaneous grafting with an exemplary PEG-diacrylate monomer and post-treatment with gluconolactone and citric acid at different pH values.

[0154] Fig.57 Depicted are the denaturation temperatures of untreated hair and hair after semi-simultaneous grafting with an exemplary PEG-diacrylate monomer and post-treatment with gluconolactone and citric acid at different pH values.

[0155] Fig.58A Depicted are the carbonyl peak regions of the FTIR spectra of hair after semi-simultaneous grafting with an exemplary PEG-diacrylate monomer and post-treatment with gluconolactone and citric acid at different concentrations.

[0156] Fig.58B Depicted are the alkyl peak regions of the FTIR spectra of hair after semi-simultaneous grafting with an exemplary PEG-diacrylate monomer and post-treatment with gluconolactone and citric acid at different concentrations.

[0157] Fig.59 Depicted are the denaturation temperatures of untreated hair and hair after semi-simultaneous grafting with an exemplary PEG-diacrylate monomer and post-treatment with gluconolactone and citric acid at different concentrations.

[0158] Fig.60A Depicted are the denaturation temperatures of untreated virgin hair, untreated bleached hair, bleached hair after semi-simultaneous grafting with an exemplary PEG-diacrylate monomer and post-treatment with gluconolactone and citric acid, and bleached hair treated with various commercially available products.

[0159] Fig.60B Depicted are protein loss values ​​for untreated virgin hair, untreated bleached hair, bleached hair after semi-simultaneous grafting with an exemplary PEG-diacrylate monomer and post-treatment with gluconolactone and citric acid, and bleached hair treated with various commercially available products.

[0160] Fig.61A Depicted are the carbonyl peak regions of the FTIR spectra of hair after semi-simultaneous grafting with an exemplary PEG-diacrylate monomer and post-treatment with gluconolactone or various polycarboxylic acids.

[0161] Fig.61BDepicted are the alkyl peak regions of the FTIR spectra of hair after semi-simultaneous grafting with an exemplary PEG-diacrylate monomer and post-treatment with gluconolactone or various polycarboxylic acids.

[0162] Fig.62 Depicted are the denaturation temperatures of untreated hair and hair after semi-simultaneous grafting with an exemplary PEG-diacrylate monomer and post-treatment with gluconolactone or various polycarboxylic acids.

[0163] Fig.63A Depicted are the carbonyl peak regions of the FTIR spectra of hair after semi-simultaneous grafting with an exemplary PEG-diacrylate monomer and post-treatment with gluconolactone or various polycarboxylic acids.

[0164] Fig.63B Depicted are the alkyl peak regions of the FTIR spectra of hair after semi-simultaneous grafting with an exemplary PEG-diacrylate monomer and post-treatment with gluconolactone or various polycarboxylic acids.

[0165] Fig.64 Depicted are the denaturation temperatures of untreated hair and hair after semi-simultaneous grafting with an exemplary PEG-diacrylate monomer and post-treatment with gluconolactone or various polycarboxylic acids.

[0166] Fig.65A Depicted are initial images of untreated hair and hair after semi-simultaneous grafting with exemplary PEG-diacrylate monomers.

[0167] Fig.65B Images of untreated hair and hair after semi-simultaneous grafting with an exemplary PEG-diacrylate monomer and 15 washes with shampoo and conditioner are depicted.

[0168] Fig.66 The images depicted show a wig model with wavy hair, one side of which was grafted with an exemplary PEG-diacrylate monomer (left) and one side was untreated (right), immediately after grafting and after 3, 7, and 10 washes, respectively.

[0169] Fig.67 The images depicted show a wig model with curly hair, one side of which was grafted with an exemplary PEG-diacrylate monomer (left) and one side was untreated (right), immediately after grafting and after 3, 7, and 10 washes, respectively.

[0170] Fig.68 The images depicted show a wig model with wavy hair, one side grafted with an exemplary PEG-diacrylate monomer to enhance natural curl (left) and one side untreated (right), immediately after grafting and after 3, 7 and 10 washes, respectively.

[0171] Fig.69 The depicted images show a wig model with wavy hair, one side of which was grafted with an exemplary PEG-diacrylate monomer and post-treated with gluconolactone and citric acid (left), and one side of which was treated with a commercially available product (right).

[0172] Fig.70A Depicted are the denaturation temperatures of untreated virgin hair, hair after semi-simultaneous grafting with an exemplary PEG-diacrylate monomer and post-treatment with gluconolactone and citric acid, and hair treated with a commercial product.

[0173] Fig.70B Depicted are protein loss values ​​for untreated virgin hair, hair after semi-simultaneous grafting with an exemplary PEG-diacrylate monomer and post-treatment with gluconolactone and citric acid, and hair treated with a commercial product.

[0174] Fig.71 The images depicted show a wig model with wavy hair that has been treated with a commercially available product, has an exemplary PEG-diacrylate monomer and N-acetylamino acid additive grafted on one side (left), and has not been additionally treated (right).

[0175] Fig.72 The images depicted show a wig model with curly hair that has been treated with a commercial perming product, without additional treatment (left), and with exemplary PEG-diacrylate monomers and N-acetylamino acid additives grafted on one side (right).

[0176] Fig.73A Depicted are the denaturation temperatures of untreated virgin hair, hair after straightening with a commercial product and insertion of an exemplary mixture of PEG-diacrylate monomer and N-acetylamino acid additive, and hair after straightening with a commercial product.

[0177] Fig.73B Depicted are the denaturation temperatures of untreated virgin hair, hair after being permed with a commercial product and inserting an exemplary mixture of PEG-diacrylate monomer and N-acetylamino acid additive, and hair after being permed with a commercial product.

[0178] Fig.74 The images depicted show a wig model with wavy hair, treated with a commercial reducing product, neutralized on one side with hydrogen peroxide (left), and treated on one side with gluconolactone and citric acid (right).

[0179] Fig.75ADepicted are the denaturation temperatures of untreated virgin hair, hair after reduction with a commercial reducing product and neutralization with hydrogen peroxide, and hair after reduction with a commercial reducing product and post-treatment with gluconolactone and citric acid.

[0180] Fig.75B Depicted are protein loss values ​​for untreated virgin hair, hair after reduction with a commercial reducing product and neutralization with hydrogen peroxide, and hair after reduction with a commercial reducing product and post-treatment with gluconolactone and citric acid.

[0181] Fig.76A The images depicted show a subject with wavy and frizzy hair before and after semi-simultaneous grafting with an exemplary PEG-diacrylate monomer and post-treatment with gluconolactone and citric acid.

[0182] Fig.76B The images depicted show a subject with bleached and curly hair before and after semi-simultaneous grafting with an exemplary PEG-diacrylate monomer and post-treatment with gluconolactone and citric acid.

[0183] Fig.77 The images depicted show a subject with straight and curly hair before and after semi-simultaneous grafting with an exemplary PEG-diacrylate monomer and post-treatment with gluconolactone and citric acid.

[0184] Fig.78 The images depicted show a subject with curly and frizzy hair before and after semi-simultaneous grafting with an exemplary PEG-diacrylate monomer and post-treatment with gluconolactone and citric acid.

[0185] Fig.79 The images depicted show a subject with bleached and curly hair at various time points before and after semi-simultaneous grafting with an exemplary PEG-diacrylate monomer and post-treatment with gluconolactone and citric acid. DETAILED DESCRIPTION

[0186] Overview

[0187] Keratin-containing materials weather and become damaged in response to stresses, including normal wear and tear, harsh cleaning solvents, washing, drying, brushing, combing, rubbing, styling, bleaching, dyeing, and sun exposure. Damage can cause degradation of the function of keratin-containing materials. For example, when the natural 18-MEA layer is lost, the hair surface becomes more hydrophilic, negatively charged, and feels damaged. Many products attempt to address this need, including moisturizers, conditioners, leave-in creams, and smoothing oils. These products contain emollients and conditioning molecules such as natural oil derivatives, long-chain alcohols, carboxylic acids, and quaternary ammonium compounds. However, the conditioning molecules in these products are only deposited on the surface of the keratin-containing material via non-covalent interactions, and they are usually washed off from the keratin-containing material and the effect is short-lived. Therefore, consumers must often take the time to reapply these products. Long-term methods for obtaining healthy native-like keratin-containing materials such as nails and hair are still unmet needs.

[0188] Exemplary Methods of Treating Keratin-Containing Materials

[0189] Grafting monomers and polymer materials to keratin-containing materials can provide a covalent coating on the keratin-containing material. The keratin-containing material sample contains a plurality of disulfide bonds. A mixture containing a reducing agent is applied to the keratin-containing material sample. Then, the keratin-containing material sample contains a plurality of free thiol groups. A monomer is applied to the keratin-containing material sample. The free thiol groups react with the monomers to form a plurality of covalent bonds between the free thiol groups and the monomers.

[0190] In some embodiments, the keratin-containing material is selected from hair (including facial hair such as eyebrows, eyelashes, beards, and whiskers), fingernails, and toenails. In some embodiments, the keratin-containing material is selected from hair, eyebrows, eyelashes, fingernails, and toenails. In some embodiments, the keratin-containing material is hair. In some embodiments, the keratin-containing material is a fingernail or a toenail.

[0191] In one aspect, the present disclosure provides a method of treating a keratin-containing material comprising:

[0192] i) providing a sample of a keratin-containing material comprising a plurality of disulfide bonds;

[0193] ii) applying a mixture to the keratin-containing material sample for a period of time, the mixture comprising a reducing agent at a concentration of about 0.1 wt. % to about 15 wt. %, thereby producing a reduced keratin-containing material sample, wherein the reduced keratin-containing material sample comprises a plurality of free thiol groups; and

[0194] iii) applying a monomer to the reduced keratin-containing material sample, wherein the monomer is selected from acrylates, methacrylates, monomers comprising vinyl groups, monomers comprising alkyne groups and monomers comprising maleimide groups, thereby forming a plurality of covalent bonds between the free thiol groups and the monomer.

[0195] In some embodiments, the method is a two-step process for attaching functional molecules to keratin-containing materials. In some embodiments, the functional molecules are hydrophobic. First, functional groups for covalent attachment of monomers are generated. Keratin-containing materials (which are primarily composed of cysteine-rich protein keratin) contain a high concentration of disulfide bonds. In some embodiments, the first step of the grafting process is a reduction step ( Figure 2A ). Today, keratin reduction is commonly used in salon services such as permanent curling (perms) and permanent straightening (Japanese perms) and has been extensively studied for these purposes. 7-10 Although reduction chemistry is well known, reducing keratin-containing materials with minimal damage to the keratin-containing material has not been evaluated. In some embodiments, a reduced keratin-containing material sample is provided after applying a reducing agent, and then a grafted keratin-containing material sample is provided after applying a monomer.

[0196] In some embodiments of the methods disclosed herein, the method further comprises rinsing the keratin-containing material sample between steps ii) and iii). In some embodiments, the method further comprises washing the keratin-containing material sample between steps ii) and iii). In some embodiments, the method further comprises drying the keratin-containing material sample after washing and before step iii). In some embodiments, the method further comprises washing, rinsing and drying the keratin-containing material sample between steps ii) and iii).

[0197] In some embodiments of the methods disclosed herein, the methods are semi-simultaneous.In some embodiments, the keratin-containing material sample is first soaked in a solution of a reducing agent and optionally a catalyst, and then the monomer is added directly to the keratin-containing material sample.

[0198] In some embodiments of the methods disclosed herein, the keratin-containing material sample is not rinsed between steps ii) and iii). In some embodiments, the keratin-containing material sample is not washed between steps ii) and iii). In some embodiments, the keratin-containing material sample is not washed nor dried between steps ii) and iii). In some embodiments, the keratin-containing material sample is not rinsed, washed nor dried between steps ii) and iii).

[0199] In another aspect, the present disclosure provides a method of treating a keratin-containing material comprising:

[0200] i) providing a sample of a keratin-containing material comprising a plurality of disulfide bonds;

[0201] ii) applying a mixture comprising a reducing agent and a catalyst to a sample of keratin-containing material for a period of time, the mixture comprising a reducing agent at a concentration of about 0.1 wt % to about 15 wt %, wherein the sample of keratin-containing material comprises a plurality of free thiol groups; and

[0202] iii) applying a monomer to the keratin-containing material sample, wherein the monomer is selected from acrylates, methacrylates, monomers comprising vinyl groups, monomers comprising alkyne groups and monomers comprising maleimide groups, thereby forming a plurality of covalent bonds between the free thiol groups and the monomer.

[0203] In some embodiments of the methods disclosed herein, the methods are simultaneous. In some embodiments, the methods are one-step and encompass simultaneous reduction and grafting processes. In some embodiments, since disulfide bonds are converted to thiol groups upon exposure to a reducing solution, functional monomer molecules present in the solution are immediately bound to free thiol groups via a thiol-Michael addition reaction. In some embodiments, a mixture comprising a reducing agent and a monomer is applied to a sample of keratin-containing material. In some embodiments, the simultaneous method shortens the processing time and reduces the overall damage to the keratin-containing material. 11,12

[0204] In another aspect, the present disclosure provides a method of treating a keratin-containing material comprising:

[0205] i) providing a sample of keratin-containing material comprising a plurality of disulfide bonds; and

[0206] ii) applying a mixture comprising a reducing agent and a monomer, wherein the reducing agent concentration is from about 0.1 wt % to about 15 wt % to the sample of keratin-containing material for a period of time; wherein the monomer is selected from acrylates, methacrylates, monomers comprising vinyl groups, monomers comprising alkyne groups, and monomers comprising maleimide groups, thereby forming a plurality of free thiol groups, which react with the monomer to form a plurality of covalent bonds between the free thiol groups and the monomer.

[0207] In some embodiments, the reducing agent is selected from ammonium thioglycolate, L-cysteine, N-acetyl L-cysteine, glutathione, ascorbic acid, β-mercaptoethanol, 2-mercaptoethylamine, 2-mercaptoethylamine hydrochloride, dithiothreitol (DTT), thiolactic acid, thiosalicylic acid, tris-2-carboxyethylphosphine hydrochloride (TCEP), sodium bisulfite, sodium thiosulfate, potassium disulfite, sodium disulfite, sodium bisulfate, sodium bisulfite, ammonium bisulfite, thioglycolic acid, calcium thioglycolate, potassium thioglycolate, sodium thioglycolate, cysteine ​​hydrochloride, ammonium thiolactate, thioglycerol, mercaptopropionic acid, thioglycolic acid glyceride and dithiobutylamine (DTBA). In some embodiments, the reducing agent is selected from ammonium thioglycolate, L-cysteine, glutathione, β-mercaptoethanol, 2-mercaptoethylamine, DTT, thiolactic acid, TCEP, DTBA, sodium bisulfite and sodium thiosulfate. In some embodiments, the reducing agent is selected from ammonium thioglycolate, L-cysteine, glutathione and thiolactic acid. In some embodiments, the reducing agent is ammonium thioglycolate or L-cysteine. In some embodiments, the reducing agent is ammonium thioglycolate. In some embodiments, the mixture also comprises diammonium dithioglycolate.

[0208] In some embodiments, the commercial treatment comprises a reducing agent. In some embodiments, the mixture comprises a commercial treatment comprising a reducing agent. In some embodiments, the mixture of step ii) comprises a commercial treatment comprising a reducing agent. In some embodiments, the mixture comprises a commercial treatment comprising ammonium thioglycolate. In some embodiments, the mixture comprises a commercial treatment comprising a reducing agent and a monomer. In some embodiments, the mixture is formed by adding a monomer to a commercial treatment comprising a reducing agent.

[0209] In some embodiments, the reducing agent is a mild reducing agent. In some embodiments, the method of treating a keratin-containing material minimizes damage to the keratin-containing material. In some embodiments, the keratin-containing material is hair. In some embodiments, the disclosed method of treating hair is less damaging than a method of permanently curling hair. In some embodiments, the disclosed method of treating hair is less damaging than a method of permanently straightening hair.

[0210] In some embodiments, the concentration of the reducing agent in the mixture is selected from about 0.1 wt%, about 0.2 wt%, about 0.3 wt%, about 0.4 wt%, about 0.5 wt%, about 0.6 wt%, about 0.7 wt%, about 0.8 wt%, about 0.9 wt%, about 1 wt%, about 1.25 wt%, about 1.5 wt%, about 1.75 wt%, about 2 wt%, about 2.25 wt%, about 2.5 wt%, about 2.75 wt%, about 3 wt%, about 3.25 wt%, about 3.5 wt%, about 3.75 wt%, about 4 wt%, about 4.25 wt%, about 4.5 wt%, about 4.75 wt%, about 5 wt%, about 5.25 wt%, about 5.5 wt%, about 5.75 wt%, about 6 wt%, about 6.25 wt%, about 6.5 wt%, about 6.75 wt% %, about 7 wt %, about 7.25 wt %, about 7.5 wt %, about 7.75 wt %, about 8 wt %, about 8.25 wt %, about 8.5 wt %, about 8.75 wt %, about 9 wt %, about 9.25 wt %, about 9.5 wt %, about 9.75 wt %, about 10 wt %, about 10.25 wt %, about 10.5 wt %, about 10.75 wt %, about 11 wt %, about 1 In some embodiments, the concentration of the reducing agent in the mixture is about 0.1% by weight to about 11% by weight. In some embodiments, the concentration of the reducing agent in the mixture is about 5% by weight to about 20% by weight. In some embodiments, the concentration of the reducing agent in the mixture is about 0.1% by weight to about 5% by weight. In some embodiments, the concentration of the reducing agent in the mixture is about 0.5% by weight to about 5% by weight. In some embodiments, the concentration of the reducing agent in the mixture is about 2.5% by weight to about 7% by weight. In some embodiments, the concentration of the reducing agent in the mixture is about 2.5% to about 5% by weight. In some embodiments, the concentration of the reducing agent in the mixture is about 1% to about 4% by weight. In some embodiments, the concentration of the reducing agent in the mixture is about 2.5% by weight. In some embodiments, the concentration of the reducing agent in the mixture is about 5% by weight.

[0211] In some embodiments, the concentration of the reducing agent in the mixture is low. In some embodiments, the concentration of the reducing agent in the mixture is less than about 11 weight %. In some embodiments, the concentration of the reducing agent in the mixture is less than about 8 weight %. In some embodiments, the concentration of the reducing agent in the mixture is less than about 6 weight %.

[0212] In some embodiments of the methods disclosed herein, the weight ratio of the mixture to the keratin-containing material sample (also referred to herein as the liquor ratio) is from about 1:10 to about 500:1. In some embodiments, the ratio is selected from about 1:10, about 2:10, about 3:10, about 4:10, about 5:10, about 6:10, about 7:10, about 8:10, about 9:10, about 1:1, about 1.1:1, about 1.2:1, about 1.3:1, about 1.4:1, about 1.5:1, about 1.6:1, about 1.7:1, about 1.8:1, about 1.9:1, about 2:1, about 3:1, about 4:1, about 5:1, about 6:1, about 7:1, about 8:1, about 9:1, about 10:1, about 11:1, about 12:1, about 13:1, about 14:1, about 15:1, about 16:1, about 17:1, about 18:1, about 19:1, about 20:1, about 21:1, about 22:1, about 23:1, about 24:1, about 25:1, about 26:1, about 27:1, about 28:1, about 29:1, about 30:1, about 31:1, about 32:1, about 33:1, about 34:1, about 35:1, about 36:1, about 37:1, about 38:1, about 39:1, about 40:1, about 41:1, about 42:1, about 43:1, about 44:1, about 45:1, about 46:1, about 47:1, about 48:1, about 49:1, about 50:1, about 51:1, about 52:1, about 53:1, about 54:1, about 55:1, about 56:1, about 57:1 1, about 58:1, about 59:1, about 60:1, about 61:1, about 62:1, about 63:1, about 64:1, about 65:1, about 66:1, about 67:1, about 68:1, about 69:1, about 70:1, about 71:1, about 72:1, about 73:1, about 74:1, about 75:1, about 76:1, about 77:1, about 78:1, about 79:1, about 80:1, about 81:1, about 82:1, about 83:1, about 84:1, about 85:1, about 86:1, about 87:1, about 88:1, about 89:1, about 90:1, about 91:1, about 92:1, about 93:1, about 94:1, about 95:1, about 96:1 1, about 16:1, about 170:1, about 175:1, about 180:1, about 185:1, about 190:1, about 195:1, about 200:1, about 205:1, about 210:1, about 225:1, about 230:1, about 240:1, about 255:1, about 260:1, about 275:1, about 280:1, about 290:1, about 300:1, about 315:1, about 320:1, about 335:1, about 340:1, about 355:1, about 360:1, about 375:1, about 380:1, about 390:1, about 400:1, about 415:1, about 420:1, about 435:1, about 440:1, about 455:1, about 460:1, about 470:1, about 485:1, about 490:1, about 500:1, about 515:1, about 520:1, about 535:1, about 540:1, about 55about 210:1, about 215:1, about 220:1, about 225:1, about 230:1, about 235:1, about 240:1, about 245:1, about 250:1, about 255:1, about 260:1, about 265:1, about 270:1, about 275:1, about 280:1, about 285:1, about 290:1, about 295:1, about 300:1, about 31 In some embodiments, the ratio is about 1:10 to about 100:1. In some embodiments, the ratio is about 1:1 to about 100:1. In some embodiments, the ratio is about 1:1 to about 20:1. In some embodiments, the ratio is about 2:1 to about 10:1. In some embodiments, the ratio is about 3:1 to about 10:1. In some embodiments, the ratio is about 5:1. In some embodiments, the ratio is about 1:10 to about 5:1. In some embodiments, the ratio is about 5:10 to about 2:1. In some embodiments, the ratio is about 5:10 to about 1.5:1. In some embodiments, the ratio is about 1.1:1.

[0213] In some embodiments, the liquid ratio is low. In some embodiments, the ratio is less than about 50: 1. In some embodiments, the ratio is less than about 20: 1. In some embodiments, the ratio is less than about 10: 1. In some embodiments, the ratio is less than about 5: 1. In some embodiments, the ratio is less than about 2: 1.

[0214] In some embodiments of the methods disclosed herein, the mixture is applied overnight. In some embodiments of the methods disclosed herein, the mixture is applied for about 1 hour to about 12 hours. In some embodiments, the mixture is applied for a time period selected from about 1 hour, about 1.25 hours, about 1.5 hours, about 1.75 hours, about 2 hours, about 2.25 hours, about 2.5 hours, about 2.75 hours, about 3 hours, about 3.25 hours, about 3.5 hours, about 3.75 hours, about 4 hours, about 4.25 hours, about 4.5 hours, about 4.75 hours, about 5 hours, about 5.25 hours, about 5.5 hours, about 5.75 hours, about 6 hours, about 6.25 hours, about 6.5 hours, about 6.75 hours, about 7 ... In some embodiments, the mixture is applied for about 5 hours to about 12 hours. In some embodiments, the mixture is applied for about 6 hours to about 10 hours. In some embodiments, the mixture comprises a reducing agent. In some embodiments, the mixture comprises a reducing agent having a concentration of about 0.1 wt % to about 15 wt %.

[0215] In some embodiments of the methods disclosed herein, the mixture is applied for about 30 seconds to about 180 minutes. In some embodiments, the mixture is applied for a time period selected from the group consisting of about 15 seconds, about 30 seconds, about 45 seconds, about 1 minute, about 2 minutes, about 3 minutes, about 4 minutes, about 5 minutes, about 6 minutes, about 7 minutes, about 8 minutes, about 9 minutes, about 10 minutes, about 11 minutes, about 12 minutes, about 13 minutes, about 14 minutes, about 15 minutes, about 16 minutes, about 17 minutes, about 18 minutes, about 19 minutes, about 20 minutes, about 21 minutes, about 22 minutes, about 23 minutes, about 24 minutes, about 25 minutes, about 26 minutes, about 27 minutes, about 28 minutes, about 29 minutes, about 30 minutes, about 31 minutes, about 32 minutes, about 33 minutes, about 34 minutes, about 35 minutes, about 36 minutes, about 37 minutes, about 38 minutes, about 39 minutes, about 40 minutes, about 41 minutes, about 42 minutes, about 43 minutes, about 44 minutes, about 45 minutes, about 46 minutes, about 47 minutes, about 48 minutes, about 49 minutes, about 50 minutes, about 51 minutes, about 52 minutes, about 53 minutes, about 54 minutes, about 55 minutes, about 56 minutes, about 57 minutes, about 58 minutes, about 59 minutes, about 60 minutes, about 61 minutes, about 62 minutes, about 63 minutes, about 64 minutes, about 65 minutes, about 66 minutes, about 67 minutes, about 68 minutes, about 69 minutes, about 70 minutes, about 71 minutes, about 72 minutes, about 73 minutes, about 74 minutes, about 75 minutes, about 76 minutes, about About 42 minutes, about 43 minutes, about 44 minutes, about 45 minutes, about 46 minutes, about 47 minutes, about 48 minutes, about 49 minutes, about 50 minutes, about 51 minutes, about 52 minutes, about 53 minutes, about 54 minutes, about 55 minutes, about 56 minutes, about 57 minutes, about 58 minutes, about 59 minutes, about 60 minutes, about 65 minutes, about 70 minutes, about 75 minutes, about 80 minutes, about 85 minutes, about 90 minutes, about 95 minutes, about 100 minutes, about 105 minutes, about 110 minutes, about 115 minutes, about 120 minutes, about 125 minutes, about 130 minutes, about 135 minutes, about 140 minutes, about 145 minutes, about 150 minutes, about 155 minutes, about 160 minutes, about 165 minutes, about 170 minutes, about 175 minutes, and about 180 minutes. In some embodiments, the mixture is applied for about 30 seconds to about 60 minutes. In some embodiments, the mixture is applied for about 1 minute to about 30 minutes. In some embodiments, the mixture is applied for about 15 minutes to about 30 minutes. In some embodiments, the mixture is applied for about 15 minutes. In some embodiments, the mixture is applied for about 1 minute to about 10 minutes. In some embodiments, the mixture is applied for about 2 minutes. In some embodiments, the mixture comprises a reducing agent and a catalyst. In some embodiments, the mixture comprises a reducing agent and a monomer.

[0216] In some embodiments, the mixture is applied for a short time. In some embodiments, the mixture is applied for less than about 60 minutes. In some embodiments, the mixture is applied for less than about 30 minutes. In some embodiments, the mixture is applied for less than about 20 minutes. In some embodiments, the mixture is applied for less than about 15 minutes. In some embodiments, the mixture is applied for less than about 5 minutes.

[0217] In some embodiments, monomer is applied to keratin-containing material sample within about 30 minutes after applying mixture to keratin-containing material sample. In some embodiments, monomer is applied to keratin-containing material sample within a time period selected from the following after applying mixture to keratin-containing material sample: about 1 minute, about 2 minutes, about 3 minutes, about 4 minutes, about 5 minutes, about 6 minutes, about 7 minutes, about 8 minutes, about 9 minutes, about 10 minutes, about 11 minutes, about 12 minutes, about 13 minutes, about 14 minutes, about 15 minutes, about 16 minutes, about 17 minutes, about 18 minutes, about 19 minutes, about 20 minutes, about 21 minutes, about 22 minutes, about 23 minutes, about 24 minutes, about 25 minutes, about 26 minutes, about 27 minutes, about 28 minutes, about 29 minutes, and about 30 minutes. In some embodiments, monomer is applied to keratin-containing material sample within about 15 minutes after applying mixture to keratin-containing material sample. In some embodiments, the monomer is applied to the keratin-containing material sample within about 10 minutes of applying the mixture to the keratin-containing material sample. In some embodiments, the monomer is applied to the keratin-containing material sample within about 5 minutes of applying the mixture to the keratin-containing material sample. In some embodiments, the monomer is applied to the keratin-containing material sample within about 1 minute of applying the mixture to the keratin-containing material sample.

[0218] In some embodiments, applying the monomer to the keratin-containing material sample is performed after applying the mixture to the keratin-containing material sample.

[0219] In some embodiments of the methods disclosed herein, the monomer is applied for a period of time selected from the group consisting of about 1 minute, about 2 minutes, about 3 minutes, about 4 minutes, about 5 minutes, about 6 minutes, about 7 minutes, about 8 minutes, about 9 minutes, about 10 minutes, about 11 minutes, about 12 minutes, about 13 minutes, about 14 minutes, about 15 minutes, about 16 minutes, about 17 minutes, about 18 minutes, about 19 minutes, about 20 minutes, about 21 minutes, about 22 minutes, about 23 minutes, about 24 minutes, about 25 minutes, about 26 minutes, about 27 minutes, about 28 minutes, about 29 minutes, about 30 minutes, about 31 minutes, about 32 minutes, about 33 minutes, about 34 minutes, about 35 minutes, about 36 minutes, about 37 minutes, about 38 minutes, about 39 minutes, about 40 minutes, about 41 minutes, about 42 minutes, about 43 minutes, about 44 minutes, about 45 minutes, about 46 minutes, about 47 minutes, about 48 minutes, about 49 minutes, about 50 minutes, about 51 minutes, about 52 minutes, about 53 minutes, about 54 minutes, about 55 minutes, about 56 minutes, about 57 minutes, about 58 minutes, about 59 minutes, about 60 minutes, about 61 minutes, about 62 minutes, about 63 minutes, about 64 minutes, about 65 minutes, about 66 minutes, about 67 minutes, about 68 minutes, about 69 minutes, about 70 minutes, about 71 minutes, about 72 minutes, about 73 minutes, about 74 minutes In some embodiments, the monomer is applied for about 30 seconds to about 60 minutes. In some embodiments, the monomer is applied for about 1 minute to about 30 minutes. In some embodiments, the monomer is applied for about 15 minutes to about 30 minutes. In some embodiments, the monomer is applied for about 30 minutes. In some embodiments, the monomer is applied for about 15 minutes. In some embodiments, the monomer is applied for about 10 minutes.

[0220] In some embodiments of the methods disclosed herein, the mixture further comprises a buffer solution. In some embodiments, the buffer solution is selected from phosphate, phosphate buffered saline, imidazole-HCl, 4-morpholineethanesulfonic acid (MES); bis(2-hydroxyethyl)-amino-tris(hydroxymethyl)methane (bis-Tris); N-(2-acetamido)iminodiacetic acid; N-(2-acetamido)-2-aminoethanesulfonic acid; 1,4-piperazinediethanesulfonic acid; 3-morpholino-2-hydroxypropanesulfonic acid (MOPSO); 1,3-bis[tris(hydroxymethyl)methyl-amino]propane; N,N-bis(2-hydroxyethyl)-2-aminoethanesulfonic acid; 4-morpholinepropanesulfonic acid (MOPS); 2-[(2-hydroxy-1,1-bis(hydroxymethyl)ethyl)-amino]ethanesulfonic acid; 4-(2-hydroxyethyl)piperazine-1-ethanesulfonic acid (HEPES); 3-(N,N-bis[2-hydroxyethyl]amino)-2-hydroxypropanesulfonic acid; 4-(N -morpholinyl)butanesulfonic acid; 2-hydroxy-3-[tris(hydroxymethyl)methylamino]-1-propanesulfonic acid; tris(hydroxymethyl)aminomethane; piperazine-N,N′-bis(2-hydroxypropanesulfonic acid); 4-(2-hydroxyethyl)-1-piperazinepropanesulfonic acid; N-[tris(hydroxymethyl)methyl]glycine; diglycine; N,N-bis(2-hydroxyethyl)-glycine; N-(2-hydroxyethyl)piperazine-N′-(4-butanesulfonic acid); N-[tris(hydroxymethyl)-methyl]-3-aminopropanesulfonic acid; N-(1,1-dimethyl-2-hydroxyethyl)-3-amino-2-hydroxypropanesulfonic acid; 2-(cyclohexylamino)-ethanesulfonic acid; 3-(cyclohexylamino)-2-hydroxy-1-propanesulfonic acid; 2-amino-2-methyl-2-propanol; sodium carbonate-sodium bicarbonate; 3-(cyclohexylamino)-1-propanesulfonic acid; and 4-(cyclohexylamino)-1-butanesulfonic acid.

[0221] In some embodiments of the methods disclosed herein, the pH of the mixture is from about 5 to about 11. In some embodiments of the methods disclosed herein, the pH of the mixture is selected from about 5.0, about 5.1, about 5.2, about 5.3, about 5.4, about 5.5, about 5.6, about 5.7, about 5.8, about 5.9, about 6.0, about 6.1, about 6.2, about 6.3, about 6.4, about 6.5, about 6.6, about 6.7, about 6.8, about 6.9, about 7.0, about 7.1, about 7.2, about 7.3, about 7.4, about 7.5, about 7.6, about 7.7, about 7.8, about 7.9, about 8.0, about 8.1, about 8.2, about 8.3, about 8.4, about 8.5, about 8.6, about 8.7, about 8.8, about 8.9, about 9.0, about 9.1, about 9.2, about 9.3, about 9.4, about 9.5, about 9.6, about 9.7, about 9.8, about 9.9, about 10. In some embodiments, the pH of the mixture is about 7 to about 11. In some embodiments, the pH of the mixture is about 7 to about 10. In some embodiments, the pH of the mixture is about 7.5 to about 10.5. In some embodiments, the pH of the mixture is about 9.5. In some embodiments, the pH of the mixture is from about 7.0 to about 9.5. In some embodiments, the pH of the mixture is from about 8.5 to about 9.5. In some embodiments, the pH of the mixture is about 8.5.

[0222] In some embodiments of the methods disclosed herein, the monomer is selected from acrylate, methacrylate, a monomer comprising a vinyl group and a monomer comprising a maleimide group. In some embodiments, the monomer is selected from acrylate, methacrylate, a monomer comprising a vinyl group and a monomer comprising an alkynyl group. In some embodiments, the monomer is acrylate, methacrylate or a monomer comprising a vinyl group. In some embodiments, the monomer is acrylate, methacrylate or a monomer comprising a maleimide group. In some embodiments, the monomer is acrylate or methacrylate. In some embodiments, the monomer is alkyl acrylate or cycloalkyl acrylate.

[0223] In some embodiments, the monomer is hydrophobic.In some embodiments, the monomer forms a coating on the keratin-containing material sample.

[0224] In some embodiments, the coating mimics the behavior of the natural lipid layer (18-methyleicosanoic acid, 18-MEA) that is present on virgin (or virgin) hair coming out of the follicle. 18-MEA acts as a protective barrier, giving the hair a smooth feel and enhanced fiber alignment that lasts much longer than rinse-off hair treatments.

[0225] In some embodiments, the coating simulates the behavior of native keratin-containing materials. In some embodiments, the monomer is a long chain acrylate. In some embodiments, the monomer is a branched monomer. In some embodiments, the monomer is a branched alkyl acrylate.

[0226] In some embodiments, the covalent attachment of the monomer to the keratin-containing material sample is a click chemistry reaction. Click chemistry reactions have the characteristics of rapid and complete conversion and high tolerance to functional groups. 13,14

[0227] In some embodiments, the covalent attachment of a terminal "ene" molecule to a free thiol is via a thiol-ene free radical addition ( Figure 2B Without being bound by any theory, it is believed that when a free radical thiol-ene mechanism is employed, ene monomers are chain extended from thiols on the keratin-containing material to form surface-bound polymers and oligomers. If the ene monomers can be polymerized without thiol functionality, it is also possible to obtain free homopolymers that are not attached to the keratin-containing material. 15

[0228] In some embodiments, the covalent attachment of the terminal "ene" molecule to the free thiol is via a thiol-Michael addition ( Figure 2C ). The thiol-Michael addition allows the monomer to be grafted onto keratin-containing material fibers without the formation of undesirable homopolymer byproducts. Without being bound by any theory, it is believed that the mechanism consists solely of the addition of a nucleophilic thiol to an electrophilic ene monomer. 16

[0229] In some embodiments, the monomer is selected from ethyl acrylate; propyl acrylate; isobutyl acrylate; butyl acrylate; amyl acrylate; t-butyl acrylate; hexyl acrylate; heptyl acrylate; octyl acrylate; isooctyl acrylate; nonyl acrylate; decyl acrylate; isodecyl acrylate; dodecyl acrylate; tridecyl acrylate; tetradecyl acrylate; hexadecyl acrylate; octadecyl acrylate; cyclopentyl acrylate; cyclohexyl acrylate; cycloheptyl acrylate; cyclooctyl acrylate; 2-(dimethylamino)ethyl acrylate; 2-(diethylamino)ethyl acrylate Ester; 2-ethylhexyl acrylate; 3,5,5-trimethylhexyl acrylate; 8-methylnonyl acrylate; 3-isobutylnonyl acrylate; 3-(cyclohexylmethyl)nonyl acrylate; 3-butyl-7,11-dimethyldodecyl acrylate; (E)-3-butyl-7,11-dimethyldodec-2-en-1-yl acrylate; isobornyl acrylate; poly(ethylene glycol) (PEG) acrylate; 1,6-hexanediol diacrylate; octafluoropentyl acrylate; fluorescein-o-acrylate; fluorescein-oo-diacrylate; and PEG-diacrylate. In some embodiments, the monomer is selected from isobutyl acrylate; butyl acrylate; tert-butyl acrylate; hexyl acrylate; isodecyl acrylate; dodecyl acrylate; tetradecyl acrylate; hexadecyl acrylate; octadecyl acrylate; cyclohexyl acrylate; 2-(dimethylamino)ethyl acrylate; 2-ethylhexyl acrylate; 8-methylnonyl acrylate; 3-isobutylnonyl acrylate; 3-(cyclohexylmethyl)nonyl acrylate; 3-butyl-7,11-dimethyldodecyl acrylate; (E)-3-butyl-7,11-dimethyldodecyl acrylate; isobornyl acrylate; PEG acrylate; 1,6-hexanediol diacrylate; octafluoropentyl acrylate; fluorescein-o-acrylate; fluorescein-oo-diacrylate; and PEG-diacrylate. In some embodiments, the monomer is selected from hexyl acrylate; isodecyl acrylate; dodecyl acrylate; tetradecyl acrylate; hexadecyl acrylate; octadecyl acrylate; 2-ethylhexyl acrylate; 3-isobutyl nonyl acrylate; 3-(cyclohexylmethyl) nonyl acrylate; 3-butyl-7,11-dimethyldodecyl acrylate; (E)-3-butyl-7,11-dimethyldodecyl acrylate; isobornyl acrylate; PEG acrylate; and PEG diacrylate. In some embodiments, the monomer is selected from hexyl acrylate; isodecyl acrylate; dodecyl acrylate; octadecyl acrylate; 2-ethylhexyl acrylate; 3-butyl-7,11-dimethyldodecyl acrylate; (E)-3-butyl-7,11-dimethyldodecyl acrylate; isobornyl acrylate; PEG acrylate; and PEG diacrylate.In some embodiments, the monomer is hexyl acrylate or dodecyl acrylate. In some embodiments, the monomer is PEG-diacrylate. In some embodiments, the monomer is poly(ethylene glycol)-diacrylate or polyethylene glycol diacrylate (PEG diacrylate or PEG-DA) selected from PEG-DA 250, PEG-DA 575, PEG-DA 700, PEG-DA 1k, PEG-DA 1.5k, PEG-DA 2k, and PEG-DA 6k. In some embodiments, the monomer is selected from PEG-DA 700, PEG-DA 1k, and PEG-DA 2k. In some embodiments, the monomer is PEG DA 700. In some embodiments, the monomer is PEG-DA 1.5k. In some embodiments, the monomer is PEG-DA 2k. The numbers refer to the number average molecular weight. That is, PEG-DA 700 refers to poly(ethylene glycol) diacrylate having a number average molecular weight of 700, and PEG DA 1.5k refers to poly(ethylene glycol) diacrylate having a number average molecular weight of 1,500. In some embodiments, the monomer is an acrylate, which is a multi-arm PEG-acrylate (PEG-AA). In some embodiments, the monomer is a multi-arm PEG-acrylate selected from 4-arm PEG-AA 2k, 4-arm PEG-AA 5k, 4-arm PEG-AA 10k, 8-arm PEG-AA 5k, and 8-arm PEG-AA20k.

[0230] In some embodiments, the monomer is a monomer comprising a vinyl group. In some embodiments, the monomer comprising a vinyl group is selected from vinyl sulfone, acrylate group, methacrylate group, styrene group, acrylamide group, methacrylamide group, maleimide group, maleate group, fumarate group and itaconate group. In some embodiments, the monomer is selected from ethyl vinyl ether; propyl vinyl ether; isobutyl vinyl ether; butyl vinyl ether; amyl vinyl ether; tert-butyl vinyl ether; hexyl vinyl ether; heptyl vinyl ether; octyl vinyl ether; isooctyl vinyl ether; nonyl vinyl ether; decyl vinyl ether; dodecyl vinyl ether; tetradecyl vinyl ether; hexadecyl vinyl ether; octadecyl vinyl ether; N,N-dimethyl-2-(vinyloxy)-ethylamine; cyclopentyl vinyl ether; cyclohexyl vinyl ether; cycloheptyl vinyl ether; cyclooctyl vinyl ether; 2-(dimethylamino)ethyl vinyl ether; 2-(diethylamino)ethyl vinyl ether; 2-ethylhexyl vinyl ether; 1-(vinyloxy)adamantane; vinyloxy-trimethylsilane; and vinyloxy-triethylsilane. In some embodiments, the monomer is selected from isobutyl vinyl ether; butyl vinyl ether; dodecyl vinyl ether; octadecyl vinyl ether; cyclohexyl vinyl ether; and vinyloxy-triethylsilane.

[0231] In some embodiments, the monomer is a monomer comprising a maleimide group. In some embodiments, the monomer is selected from N-ethylmaleimide; N-cyclohexylmaleimide; N-arachidonylmaleimide; fluorescein 5-maleimide; succinimidyl-[(N-maleimidopropionamido)-diethylene glycol] ester (NHS-PEG n -maleimide); poly(ethylene glycol) (PEG)-maleimide; PEG-methyl ether maleimide (mPEG-maleimide); and methoxy-PEG-maleimide. In some embodiments, the monomer is selected from N-ethylmaleimide; NHS-PEG n -maleimide; PEG-maleimide; mPEG-maleimide; and methoxy-PEG-maleimide. In some embodiments, the monomer is N-ethylmaleimide or PEG-maleimide.

[0232] In some embodiments, the monomer is selected from hexyl acrylate; dodecyl acrylate; N-ethylmaleimide; and PEG-maleimide.

[0233] In some embodiments of the methods disclosed herein, the molar ratio of monomer to free thiol groups is from about 100:1 to about 1:10. In some embodiments, the molar ratio of monomer to free thiol groups is selected from about 100:1, about 99:1, about 98:1, about 97:1, about 96:1, about 95:1, about 94:1, about 93:1, about 92:1, about 91:1, about 90:1, about 89:1, about 88:1, about 87:1, about 86:1, about 85:1, about 84:1, about 83:1, about 82:1, about 81:1, about 80:1, about 79:1, about 78:1, about 77:1, about 76:1, about 75:1, about 76:1, about 77:1 4:1, about 73:1, about 72:1, about 71:1, about 70:1, about 69:1, about 68:1, about 67:1, about 66:1, about 65:1, about 64:1, about 63:1, about 62:1, about 61:1, about 60:1, about 59:1, about 58:1, about 57:1, about 56:1, about 55:1, about 54:1, about 53:1, about 52:1, about 51:1, about 50:1, about 49:1, about 48:1, about 47:1, about 46:1, about 45:1, about 44:1, about 43:1, about 42:1, about 41:1, about 40:1, about 39:1, about 38:1, about 37:1, about 36:1, about 35:1, about 34:1, about 33:1, about 32:1, about 31:1, about 30:1, about 29:1, about 28:1, about 27:1, about 26:1, about 25:1, about 24:1, about 23:1, about 22:1, about 21:1, about 20:1, about 19:1, about 18:1, about 17:1, about 16:1, about 15:1, about 14:1, about 13 In some embodiments, the molar ratio of monomer to free thiol groups is from about 20:1 to about 1:1. In some embodiments, the molar ratio of monomer to free thiol groups is from about 10:1 to about 1:1. In some embodiments, the molar ratio of monomer to free thiol groups is from about 10:1 to about 1:1. In some embodiments, the molar ratio of monomer to free thiol groups is about 5: 1. In some embodiments, the molar ratio of monomer to free thiol groups is about 2.5:1.

[0234] In some embodiments, the molar ratio of monomer to free thiol groups is from about 0.001:1 to about 2.5:1. In some embodiments, the molar ratio of monomer to free thiol groups is selected from about 0.001:1, about 0.005:1, about 0.01:1, about 0.011:1, about 0.012:1, about 0.013:1, about 0.014:1, about 0.015:1, about 0.016:1, about 0.017:1, about 0.018:1, about 0.019:1, about 0.02:1, about 0.021:1, about 0.022:1, about 0.023:1, about 0.024:1, about 0.025:1, about 0.026:1, about 0.027:1, about 0.028:1, about 0.029:1, about 0.03:1, about 0.031:1, about 0.032:1 .032:1, about 0.033:1, about 0.034:1, about 0.035:1, about 0.036:1, about 0.037:1, about 0.038:1, about 0.039:1, about 0.04:1, about 0.041:1, about 0.042:1, about 0.043:1, about 0.044:1, about 0.045:1, about 0.046:1, about 0.047:1, about 0.048:1, about 0.049:1, about 0.05:1, about 0.051:1, about 0.052:1, about 0.053:1, about 0.054:1, about 0.055:1, about 0.056:1, about 0.057:1, about 0.058:1, about 0.059:1, about 0.06:1, about 0.061:1, about 0.062:1, about 0.063:1, about 0.064:1, about 0.065:1, about 0.066:1, about 0.067:1, about 0.068:1, about 0.069:1, about 0.07:1, about 0.071:1, about 0.072:1, about 0.073:1, about 0.074:1, about 0.075:1, about 0.076:1, about 0.077:1, about 0.078:1, about 0.079:1, about 0.08:1, about 0.081:1, about 0.082:1, about 0.083:1, about 0.084:1, about 0.085:1 , about 0.086:1, about 0.087:1, about 0.088:1, about 0.089:1, about 0.09:1, about 0.091:1, about 0.092:1, about 0.093:1, about 0.094:1, about 0.095:1, about 0.096:1, about 0.097:1, about 0.098:1, about 0.099:1, about 0.1:1, about 0.11:1, about 0.12:1, about 0.13:1, about 0.14:1, about 0.15:1, about 0.16:1, about 0.17:1, about 0.18:1, about 0.19:1, about 0.2:1, about 0.21:1, about 0.22:1, about 0.23:1, about 0.24:1, about 0.25:1, about 0.26:1, about 0.27:1, about 0.28:1, about 0.29:1, about 0.3:1, about 0.31:1, about 0.32:1, about 0.33:1, about 0.34:1, about 0.35:1, about 0.36:1, about 0.37:1, about 0.38:1, about 0.39:1, about 0.4 :1, about 0.41:1, about 0.42:1, about 0.43:1, about 0.44:1, about 0.45:1, about 0.46:1, about 0.47:1, about 0.48:1, about 0.49:1, about 0.5:1, about 0.51:1, about 0.52:1, about 0.53:1, about 0.54:1, about 0.55:1, about 0.56:1 , about 0.57:1, about 0.58:1, about 0.59:1, about 0.6:1, about 0.65:1, about 0.7:1, about 0.75:1, about 0.8:1, about 0.85:1, about 0.9:1, about 1:1, about 1.05:1, about 1.1:1, about 1.15:1, about 1.2:1, about 1.25:1, about 1.3:1, about 1 In some embodiments, the molar ratio of monomer to free thiol groups is from about 0.05:1 to about 2.5:1. In some embodiments, the molar ratio of monomer to free thiol groups is from about 0.1:1 to about 1:1. In some embodiments, the molar ratio of monomer to free thiol groups is from about 0.2:1 to about 0.6:1. In some embodiments, the molar ratio of monomer to free thiol groups is about 0.38:1. In some embodiments, the molar ratio of monomer to free thiol groups is from about 0.02:1 to about 0.06:1. In some embodiments, the molar ratio of monomer to free thiol groups is about 0.04:1.

[0235] In some embodiments of the methods disclosed herein, the concentration of the monomer is from about 0.5% to about 95% by weight. In some embodiments, the concentration of the monomer is selected from about 0.5%, about 0.75%, about 1%, about 1.25%, about 1.5%, about 1.75%, about 2%, about 2.25%, about 2.5%, about 2.75%, about 3%, about 3.25%, about 3.5%, about 3.75%, about 4%, about 4.25%, about 4.5%, about 4.75%, about 5%, about 5.25%, about 5.5%, about 5.75%, about 6%, about 6.25%, about 6.5%, about 6.75%, about 7%, about 7.25%, about 7.5%, about 7.75%, about 7. %, about 7.5 wt %, about 7.75 wt %, about 8 wt %, about 8.25 wt %, about 8.5 wt %, about 8.75 wt %, about 9 wt %, about 9.25 wt %, about 9.5 wt %, about 9.75 wt %, about 10 wt %, about 10.5 wt %, about 11 wt %, about 11.5 wt %, about 12 wt %, about 12.5 wt %, about 13 wt %, about 13.5 wt %, about 14 wt %, about 14.5 wt %, about 15 wt %, about 15.5 wt %, about 16 wt %, about 16.5 wt %, about 17 wt %, about 17.5 wt %, about 18 wt %, about 18.5 wt %, about 19 wt %, about 19.%, about 45 wt %, about 46 wt %, about 47 wt %, about 48 wt %, about 49 wt %, about 50 wt %, about 51 wt %, about 52 wt %, about 53 wt %, about 54 wt %, about 55 wt %, about 56 wt %, about 57 wt %, about 58 wt %, about 59 wt %, about 60 wt %, about 61 wt %, about 62 wt %, about 63 wt %, about 64 wt %, about 65 wt %, about 66 wt %, about 67 wt %, about 68 wt %, about 69 wt %, about 70 wt %, about 71 wt %, about 72 wt %, about 73 wt %, about 74 wt %, about 75 wt %, about 76 wt %, about 77 wt %, about 78 wt %, about 79 wt %, about 80 wt %, about 81 wt %, about 82 wt %, about 83 wt %, about 84 wt %, about 85 wt %, about 86 wt %, about 87 wt %, about 88 wt %, about 89 wt %, about 90 wt %, about 58 wt %, about 59 wt %, about 60 wt %, about 61 wt %, about 62 wt %, about 63 wt %, about 64 wt %, about 65 wt %, about 66 wt %, about 67 wt %, about 68 wt %, about 69 wt %, about 70 wt %, about 71 wt %, about 72 wt %, about 73 wt %, about 74 wt %, about 75 wt %, about 76 wt %, about 77 wt %, about 78 wt %, about 79 wt %, about 80 wt %, about 81 wt %, about 82 wt %, about 83 wt %, about 84 wt %, about 85 wt %, about 86 wt %, about 87 wt %, about 88 wt %, about 89 wt %, about 90 wt %, about 91 wt %, about 92 wt %, about 93 wt %, about 94 wt %, and about 95 wt %. In some embodiments, the concentration of the monomer is from about 0.5% to about 70% by weight. In some embodiments, the concentration of the monomer is from about 2% to about 60% by weight. In some embodiments, the concentration of the monomer is from about 2% to about 30% by weight. In some embodiments, the concentration of the monomer is from about 0.5% to about 40% by weight. In some embodiments, the concentration of the monomer is from about 2% to about 30% by weight. .

[0236] In some embodiments of the methods disclosed herein, the method of treating a keratin-containing material comprises:

[0237] i) providing a sample of a keratin-containing material comprising a plurality of disulfide bonds;

[0238] ii) applying a mixture to the keratin-containing material sample for a period of time, the mixture comprising a reducing agent at a concentration of about 2.5 wt. % to about 7 wt. %, thereby producing a reduced keratin-containing material sample, wherein the reduced keratin-containing material sample comprises a plurality of free thiol groups; and

[0239] iii) applying a monomer to the reduced keratin-containing material sample, wherein the monomer is poly(ethylene glycol) diacrylate (PEG-DA), thereby forming a plurality of covalent bonds between free thiol groups and the monomer.

[0240] In some embodiments of the methods disclosed herein, the method of treating a keratin-containing material comprises:

[0241] i) providing a sample of a keratin-containing material comprising a plurality of disulfide bonds;

[0242] ii) applying a mixture comprising a reducing agent and a catalyst to a sample of keratin-containing material for a period of time, the mixture comprising a reducing agent at a concentration of about 2.5% to about 7% by weight, wherein the sample of keratin-containing material comprises a plurality of free thiol groups; and

[0243] iii) applying a monomer to the keratin-containing material sample, wherein the monomer is PEG-DA, thereby forming a plurality of covalent bonds between the free thiol groups and the monomer.

[0244] In some embodiments of the methods disclosed herein, the method of treating a keratin-containing material comprises:

[0245] i) providing a sample of keratin-containing material comprising a plurality of disulfide bonds; and

[0246] ii) applying a mixture to the keratin-containing material sample for a period of time, the mixture comprising a reducing agent and a monomer, the reducing agent concentration being from about 2.5 wt % to about 7 wt %; wherein the monomer is PEG-DA, thereby forming a plurality of free thiol groups, which react with the monomer to form a plurality of covalent bonds between the free thiol groups and the monomer.

[0247] In some embodiments, the reducing agent is ammonium thioglycolate. In some embodiments, the reducing agent concentration is about 5 wt %. In some embodiments, the weight ratio (liquid ratio) of the mixture to the keratin-containing material sample is about 1.1:1. In some embodiments, PEG-DA is PEG-DA 1.5k or PEG-DA 2k. In some embodiments, the reducing agent is ammonium thioglycolate and PEG-DA is PEG-DA 1.5k or PEG-DA 2k.

[0248] In some embodiments, the methods disclosed herein further comprise applying a catalyst to the keratin-containing material sample. In some embodiments, the catalyst is selected from the group consisting of amines, phosphines, and free radical initiators.

[0249] In some embodiments, the catalyst is an amine. In some embodiments, the catalyst is a primary amine or a secondary amine. In some embodiments, the catalyst is a tertiary amine. In some embodiments, the amine is selected from N,N-diisopropylethylamine, N-ethyldiisopropylamine, di-n-propylamine, trimethylamine, triethylamine, ethanolamine, diethanolamine and triethanolamine. In some embodiments, the amine is di-n-propylamine or triethylamine. In some embodiments, the amine is triethylamine.

[0250] In some embodiments, the catalyst is a phosphine. In some embodiments, the catalyst is a tertiary phosphine. In some embodiments, the phosphine is selected from dimethylphenylphosphine, diethylphenylphosphine, methyldiphenylphosphine, ethyldiphenylphosphine, trimethylphosphine, tripropylphosphine, triphenylphosphine, tri(o-tolyl)phosphine, tri(p-tolyl)phosphine, tri(2,4,6-trimethylphenyl)phosphine, tri(3,5-dimethylphenyl)phosphine, dicyclohexyl-(2,6-diisopropylphenyl)phosphine and tri(hydroxymethyl)phosphine. In some embodiments, the phosphine is dimethylphenylphosphine.

[0251] In some embodiments, the amine is selected from di-n-propylamine, dimethylphenylphosphine, and trimethylamine.

[0252] In some embodiments, the amount of catalyst is from about 1 mol% to about 100 mol% relative to the monomer. In some embodiments, the amount of catalyst is selected from about 1 mol%, about 2 mol%, about 3 mol%, about 4 mol%, about 5 mol%, about 6 mol%, about 7 mol%, about 8 mol%, about 9 mol%, about 10 mol%, 11 mol%, about 12 mol%, about 13 mol%, about 14 mol%, about 15 mol%, about 16 mol%, about 17 mol%, about 18 mol%, about 19 mol%, about 20 mol%, about 21 mol%, about 22 mol%, about 23 mol%, about 24 mol%, about 25 mol%, about 26 mol%, about 27 mol%, about 28 mol%, about 29 mol%, about 30 mol%, about 31 mol%, about 32 mol%, about 33 mol%, about 34 mol%, about 35 mol%, about 36 mol%, about 37 mol%, about 38 mol%, about 39 mol%, about 40 mol%, about 41 mol%, about 42 mol%, about 43 mol%, about 44 mol%, about 45 mol%, about 46 mol%, about 47 mol%, about 48 mol%, about 49 mol%, about 50 mol%, about 51 mol%, about 52 mol%, about 53 mol%, about 54 mol%, about 55 mol%, about 56 mol%, about 57 mol%, about 58 mol%, about 59 mol%, about 60 mol%, about 61 mol%, about 62 mol%, about 63 mol%, about 64 mol%, about 65 mol%, about 66 mol%, about 67 mol%, about 68 mol%, about 69 %, about 45 mol%, about 46 mol%, about 47 mol%, about 48 mol%, about 49 mol%, about 50 mol%, about 51 mol%, about 52 mol%, about 53 mol%, about 54 mol%, about 55 mol%, about 56 mol%, about 57 mol%, about 58 mol%, about 59 mol%, about 60 mol%, about 61 mol%, about 62 mol%, about 63 mol%, about 64 mol%, about 65 mol%, about 66 mol%, about 67 mol%, about 68 mol%, about 69 mol%, about 70 mol%, about 71 mol%, about 72 mol%, about 73 mol%, about 74 mol%, about 75 mol%, about 76 mol%, about 77 mol%, about 78 mol%, about 79 mol%, about 80 mol%, about 81 mol%, about 82 mol%, about 83 mol%, about 84 mol%, about 85 mol%, about 86 mol%, about 87 mol%, about 88 mol%, about 89 mol%, about 90 mol%, about %, about 51 mol%, about 52 mol%, about 53 mol%, about 54 mol%, about 55 mol%, about 56 mol%, about 57 mol%, about 58 mol%, about 59 mol%, about 60 mol%, 61 mol%, about 62 mol%, about 63 mol%, about 64 mol%, about 65 mol%, about 66 mol%, about 67 mol%, about 68 mol%, about 69 mol%, about 70 mol%, 71 mol%, about 72 mol%, about 73 mol%, about 74 mol%, about 75 mol%, In some embodiments, the amount of catalyst is about 10 mol% to about 60 mol% relative to monomer. In some embodiments, the amount of catalyst is about 20 mol% to about 50 mol% relative to monomer. In some embodiments, the amount of catalyst is about 40 mol% relative to monomer.

[0253] In some embodiments, the concentration of the catalyst is from about 0.1 wt % to about 15 wt %. In some embodiments, the concentration of the catalyst is selected from about 0.1 wt%, about 0.2 wt%, about 0.3 wt%, about 0.4 wt%, about 0.5 wt%, about 0.6 wt%, about 0.7 wt%, about 0.8 wt%, about 0.9 wt%, about 1 wt%, about 1.25 wt%, about 1.5 wt%, about 1.75 wt%, about 2 wt%, about 2.25 wt%, about 2.5 wt%, about 2.75 wt%, about 3 wt%, about 3.25 wt%, about 3.5 wt%, about 3.75 wt%, about 4 wt%, about 4.25 wt%, about 4.5 wt%, about 4.75 wt%, about 5 wt%, about 5.25 wt%, about 5.5 wt%, about 5.75 wt%, about 6 wt%, about 6.25 wt%, about 6.5 wt%, about 6.75 wt%, about 7 wt%, about 7.25 wt%, about 7.5 wt%, about 7.75 wt%, about 8 wt%, about 8.25 wt%, about 8.5 wt%, about 8.75 wt%, about 9 wt%, about 9.25 wt%, about 9.5 wt%, about 9.75 wt%, about 10 wt%, about 10.25 wt%, about 10.5 wt%, about 10.75 wt%, about 11 wt%, about 11 In some embodiments, the concentration of the catalyst is about 0.1% to about 10% by weight. In some embodiments, the concentration of the catalyst is about 1% to about 9% by weight. In some embodiments, the concentration of the catalyst is about 0.1% to about 5% by weight. In some embodiments, the concentration of the catalyst is about 1% to about 9% by weight. In some embodiments, the concentration of the catalyst is about 0.1% to about 5% by weight. In some embodiments, the concentration of the catalyst is about 1% to about 9% by weight.

[0254] In some embodiments of the methods disclosed herein, the catalyst is a free radical initiator. In some embodiments, the free radical initiator is selected from peroxides, azo compounds, photoinitiators. In some embodiments, the free radical initiator is a peroxide. In some embodiments, the peroxide is selected from hydrogen peroxide, tert-butyl hydroperoxide, tert-butyl peracetate, cumene hydroperoxide, dicumyl peroxide, benzoyl peroxide and tert-butyl peroxide. In some embodiments, the peroxide is hydrogen peroxide.

[0255] In some embodiments, the free radical initiator is an azo compound. In some embodiments, the azo compound is selected from 4,4'-azobis(4-cyanovaleric acid), 4,4'-azobis(4-cyanovaleric acid), 1,1'-azobis(cyclohexanecarbonitrile), 2,2'-azobis(2-methylpropylamidine) dihydrochloride, 2,2'-azobis(2-methylpropionitrile) and 2,2'-azobis(2-methylpropionitrile).

[0256] In some embodiments, the free radical initiator is a photoinitiator. In some embodiments, the photoinitiator is an aryl ketone. In some embodiments, the photoinitiator is selected from acetophenone; anisole; anthraquinone; anthraquinone-2-sulfonic acid; benzil; benzoin; benzoin ethyl ether; benzoin isobutyl ether; benzoin methyl ether; benzophenone; 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride; 4-benzoylbiphenyl; 2-benzyl-2-(dimethylamino)-4'-morpholinobutylphenone; 4,4'-bis(diethylamino)benzophenone; 4,4'-bis(dimethylamino)benzophenone; camphorquinone; 2-chlorothioxanthen-2-one; dibenzosuberenone; 2,2'-diethoxyacetophenone; 4,4'-dihydroxybenzophenone; 2,2'-dimethoxy-2-phenylacetophenone; 4-(di In some embodiments, the photoinitiator is 2,2'-diethoxyacetophenone.

[0257] In some embodiments of the methods disclosed herein, the method further comprises applying an additive to the keratin-containing material sample for a period of time. In some embodiments, an additive is applied to the keratin-containing material sample between steps i) and ii). In some embodiments, an additive is applied to the keratin-containing material sample as a pre-treatment agent. In some embodiments of the methods disclosed herein, the mixture further comprises an additive. In some embodiments, the mixture of step ii) further comprises an additive. In some embodiments, an additive is applied to the keratin-containing material sample after step ii). In some embodiments, the mixture of step iii) further comprises an additive. In some embodiments, an additive is applied to the keratin-containing material sample after step iii). In some embodiments, an additive is applied to the keratin-containing material sample as a post-treatment agent.

[0258] In some embodiments, the additive is selected from a fatty acid, a fatty alcohol, a fatty acid ester, an amino acid mixture, a peptide mixture, an acidulant, a polycarboxylic acid, or a mixture thereof.

[0259] In some embodiments, the additive is a fatty acid, a fatty alcohol, a fatty acid ester, or a mixture thereof. In some embodiments, the fatty acid, fatty alcohol, or fatty acid alcohol is selected from butyric acid, caproic acid, caprylic acid, capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, arachidic acid, behenic acid, lignoceric acid, cerotic acid, myristoleic acid, palmitoleic acid, cis-6-hexadecenoic acid (sapienic acid acid), oleic acid, oleic acid, vaccenic acid, linoleic acid, trans-linoleic acid, linolenic acid, arachidonic acid, eicosapentaenoic acid, erucic acid, docosahexaenoic acid, argan oil, coconut oil, jojoba oil, olive oil, palm oil, caprylic alcohol, nonanol, decanol, undecanol, lauryl alcohol, tridecanol, myristyl alcohol, pentadecanol, cetyl alcohol, palmitoleyl alcohol, heptadecanol, stearyl alcohol, oleyl alcohol, nonadecanol, eicosanol, heneicosanol, behenyl alcohol, erucyl alcohol, tetracosanol, ceryl alcohol, ascorbyl palmitate, ascorbyl stearate, cetyl myristate, cetyl palmitate, diglyceryl, ethyl caprate, ethyl macadamia oleate (ethyl In some embodiments, the fatty acid is selected from butyric acid, caproic acid, caprylic acid, capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, arachidic acid, behenic acid, lignoceric acid, cerotic acid, myristoleic acid, palmitoleic acid, cis-6-hexadecenoic acid, oleic acid, elaidic acid, vaccenic acid, linoleic acid, trans-linoleic acid, linolenic acid, arachidonic acid, eicosapentaenoic acid, erucic acid, docosahexaenoic acid, jojoba oil, argan oil, coconut oil, jojoba oil, olive oil, palm oil and mixtures thereof. In some embodiments, the fatty acid is selected from oleic acid, linoleic acid, jojoba oil and mixtures thereof. In some embodiments, the fatty alcohol is selected from octanol, n-nonanol, decanol, undecanol, lauryl alcohol, tridecanol, myristyl alcohol, pentadecyl alcohol, cetyl alcohol, palmitoleyl alcohol, heptadecanol, stearyl alcohol, oleyl alcohol, nonadecanol, eicosanol, heneicosanol, behenyl alcohol, erucyl alcohol, tetracosanol, wax alcohol and mixtures thereof. In some embodiments, the fatty alcohol is cetyl alcohol or cetearyl alcohol. In some embodiments, the fatty acid ester is selected from ascorbyl palmitate, ascorbyl stearate, cetyl myristoleate, cetyl palmitate, diglyceride, ethyl caprate, ethyl macadamia oleate, ethyl caprylate, ethyl palmitate, ethylhexyl palmitate, glyceryl monostearate, glyceryl hydroxystearate, ethylene glycol distearate, ethylene glycol stearate, glyceryl monolaurate, isopropyl palmitate, monoglyceride, 2-oleoylglycerol and mixtures thereof.

[0260] In some embodiments, the additive is an amino acid mixture or a peptide mixture. In some embodiments, the additive is an amino acid mixture comprising one or more amino acids (naturally occurring L- or D-forms), which can be identified by the conventional three-letter abbreviations shown in the table below.

[0261] Table 1 (Amino Acid Code)

[0262] name 3-letter code name 3-letter code Alanine Ala Leucine Leu Arginine Arg Lysine Lys Asparagine Asn Methionine Met Aspartic acid Asp Phenylalanine Phe Cysteine Cys Proline Pro Glutamate Glu Serine Ser Glutamine Gln Threonine Thr Glycine Gly Tryptophan Trp Histidine His Tyrosine Tyr Isoleucine Ile Valine Val

[0263] In some embodiments, the additive is an amino acid mixture or N-acetylated amino acid (e.g., N-acetylated alanine Ac-Ala) comprising one or more amino acids. In some embodiments, the additive comprises an amino acid mixture selected from glycine (Gly), L-alanine (L-Ala), L-serine (L-Ser), L-cysteine ​​(L-Cys), N-acetylglycine (Ac-Gly), N-acetylalanine (Ac-Ala), and N-acetylserine (Ac-Ser). In some embodiments, the additive comprises an amino acid mixture selected from Ac-Gly, Ac-Ala, and Ac-Ser. In some embodiments, the additive comprises an amino acid mixture or a peptide mixture used in the personal care industry. In some embodiments, the additive comprises an amino acid mixture or a peptide mixture selected from the following: KeraVeg 18 (a blend of plant amino acids), 500 (amino acid blend), Vegetamide 18MEA-NJ (cetearylaminoethyl diethylammonium succinyl hydrolyzed pea protein), Vegetamide 18MEA-MR (cetearylaminoethyl diethylammonium hydrolyzed rice protein), KERARICE TM (rice peptides and amino acids), KERATRIX TM (Carob hydrolysate), Promois WK-PD (Hydrolyzed Keratin) and Kera-P LM (low molecular weight plant peptide). In some embodiments, the additive is KERATRIX TM .

[0264] In some embodiments, the additive comprises an acidulant, a polycarboxylic acid, or a mixture thereof. In some embodiments, the additive comprises an acidulant or polycarboxylic acid selected from the following: disaccharide uronic acid, azelaic acid, citric acid, ethylenediaminetetraacetic acid, ethylenediamine-N, N'-disuccinic acid, gluconolactone, glutamic acid N, N-diacetic acid, lactic acid, methylglycine diacetic acid, tartaric acid, and mixtures thereof. In some embodiments, the additive comprises an acidulant or polycarboxylic acid selected from the following: citric acid, gluconolactone, glutamic acid N, N-diacetic acid, tartaric acid, tartronic acid, gluconic acid, succinic acid, itaconic acid, acetic acid, malonic acid, malic acid, 1,2,3,4-butanetetracarboxylic acid, and mixtures thereof. In some embodiments, the additive comprises citric acid and gluconolactone.

[0265] In some embodiments, the concentration of the additive is from about 0.1 wt % to about 15 wt %. In some embodiments, the concentration of the additive is selected from about 0.1 wt%, about 0.2 wt%, about 0.3 wt%, about 0.4 wt%, about 0.5 wt%, about 0.6 wt%, about 0.7 wt%, about 0.8 wt%, about 0.9 wt%, about 1 wt%, about 1.25 wt%, about 1.5 wt%, about 1.75 wt%, about 2 wt%, about 2.25 wt%, about 2.5 wt%, about 2.75 wt%, about 3 wt%, about 3.25 wt%, about 3.5 wt%, about 3.75 wt%, about 4 wt%, about 4.25 wt%, about 4.5 wt%, about 4.75 wt%, about 5 wt%, about 5.25 wt%, about 5.5 wt%, about 5.75 wt%, about 6 wt%, about 6.25 wt%, about 6.5 wt%, about 6.75 wt%, about 7 wt%, about 7.25 wt%, about 7.5 wt%, about 7.75 wt%, about 8 wt%, about 8.25 wt%, about 8.5 wt%, about 8.75 wt%, about 9 wt%, about 9.25 wt%, about 9.5 wt%, about 9.75 wt%, about 10 wt%, about 10.25 wt%, about 10.5 wt%, about 10.75 wt%, about 11 wt%, about 11 In some embodiments, the concentration of the additive is about 0.1% to about 10% by weight. In some embodiments, the concentration of the additive is about 0.1% to about 8% by weight. In some embodiments, the concentration of the additive is about 0.1% to about 5% by weight. In some embodiments, the concentration of the additive is about 2% by weight. In some embodiments, the concentration of each additive is about 2% by weight.

[0266] In some embodiments of the methods disclosed herein, the mixture further comprises a solvent. In some embodiments, the solvent comprises dimethyl sulfoxide, water, acetone, a buffer or a mixture thereof. In some embodiments, the solvent is benign. In some embodiments, the solvent is not an organic solvent. In some embodiments, the solvent comprises water. In some embodiments, the solvent is water.

[0267] In some embodiments, the thiol-Michael addition grafting reaction on keratin-containing materials proceeds faster and with better overall conversion in water compared to grafting in organic solvents. This behavior is consistent with a type of biphasic reaction known as "on-water". Certain organic reactions proceed optimally on water, even when the organic reactants are insoluble in the aqueous phase.

[0268] Without being bound by any theory, this phenomenon may arise from the ability of water to activate both electrophiles and nucleophiles through hydrogen bonding. In some embodiments, the proposed mechanism for activation on water in the thiol-Michael system is shown in Figure 3 middle.

[0269] In some embodiments, the mixture is an emulsion.In some embodiments, the mixture further comprises a surfactant.

[0270] Exemplary Properties of Keratin-Containing Materials

[0271] In some embodiments, the keratin-containing material is damaged in response to one or more stresses. In some embodiments, the one or more stresses are selected from washing, drying, brushing, combing, rubbing, styling, bleaching, dyeing, sun exposure, and heat treatment.

[0272] In another aspect, the present disclosure provides a method for treating a keratin-containing material, wherein the hydrophobicity of the keratin-containing material is improved, the method comprising:

[0273] i) providing a sample of a keratin-containing material comprising a plurality of disulfide bonds;

[0274] ii) applying a mixture comprising a reducing agent to a sample of keratin-containing material for a period of time, wherein the sample of keratin-containing material comprises a plurality of free thiol groups; and

[0275] iii) applying a monomer to the keratin-containing material sample, wherein the monomer is selected from the group consisting of acrylates, methacrylates, monomers comprising vinyl groups, monomers comprising alkyne groups and monomers comprising maleimide groups, thereby forming a plurality of covalent bonds between the free thiol groups and the monomer;

[0276] Thereby improving the hydrophobicity of keratin-containing materials.

[0277] In another aspect, the present disclosure provides a method for treating a keratin-containing material, wherein the hydrophobicity of the keratin-containing material is improved, the method comprising:

[0278] i) providing a sample of a keratin-containing material comprising a plurality of disulfide bonds;

[0279] ii) applying a mixture comprising a reducing agent and a catalyst to a sample of keratin-containing material for a period of time, wherein the sample of keratin-containing material comprises a plurality of free thiol groups; and

[0280] iii) applying a monomer to the keratin-containing material sample, wherein the monomer is selected from the group consisting of acrylates, methacrylates, monomers comprising vinyl groups, monomers comprising alkyne groups and monomers comprising maleimide groups, thereby forming a plurality of covalent bonds between the free thiol groups and the monomer;

[0281] Thereby improving the hydrophobicity of keratin-containing materials.

[0282] In another aspect, the present disclosure provides a method for treating a keratin-containing material, wherein the hydrophobicity of the keratin-containing material is improved, the method comprising:

[0283] i) providing a sample of keratin-containing material comprising a plurality of disulfide bonds; and

[0284] ii) applying a mixture comprising a reducing agent and a monomer to the sample of keratin-containing material for a period of time; wherein the monomer is selected from acrylates, methacrylates, monomers comprising vinyl groups, monomers comprising alkyne groups and monomers comprising maleimide groups, thereby forming a plurality of free thiol groups, which react with the monomer to form a plurality of covalent bonds between the free thiol groups and the monomer;

[0285] Thereby improving the hydrophobicity of keratin-containing materials.

[0286] In some embodiments, the advancing water contact angle is greater than about 70°. In some embodiments, the advancing water contact angle is greater than about 80°. In some embodiments, the advancing water contact angle is greater than about 90°. In some embodiments, the advancing water contact angle is greater than about 100°.

[0287] In some embodiments, the advancing water contact angle is selected from about 70°, about 71°, about 72°, about 73°, about 74°, about 75°, about 76°, about 77°, about 78°, about 79°, about 80°, about 81°, about 82°, about 83°, about 84°, about 85°, about 86°, about 87°, about 88°, about 89°, about 90°, about 91°, about 92°, about 93°, about 94°, about 95°, about 96°, about 97°, about 98°, about 99°, about 100°, about 101°, about 102°, about 103°, about 104°, about 105°, about 106°, about 107°, about 108°, about 109°, and about 110°. In some embodiments, the advancing water contact angle is about 100°.

[0288] In another aspect, the present disclosure provides a method for treating a keratin-containing material, wherein the elongation at break of the keratin-containing material is improved, the method comprising:

[0289] i) providing a sample of a keratin-containing material comprising a plurality of disulfide bonds;

[0290] ii) applying a mixture comprising a reducing agent to a sample of keratin-containing material for a period of time, wherein the sample of keratin-containing material comprises a plurality of free thiol groups; and

[0291] iii) applying a monomer to the keratin-containing material sample, wherein the monomer is selected from the group consisting of acrylates, methacrylates, monomers comprising vinyl groups, monomers comprising alkyne groups and monomers comprising maleimide groups, thereby forming a plurality of covalent bonds between the free thiol groups and the monomer;

[0292] Thereby improving the elongation at break of keratin-containing materials.

[0293] In another aspect, the present disclosure provides a method for treating a keratin-containing material, wherein the elongation at break of the keratin-containing material is improved, the method comprising:

[0294] i) providing a sample of a keratin-containing material comprising a plurality of disulfide bonds;

[0295] ii) applying a mixture comprising a reducing agent and a catalyst to a sample of keratin-containing material for a period of time, wherein the sample of keratin-containing material comprises a plurality of free thiol groups; and

[0296] iii) applying a monomer to the keratin-containing material sample, wherein the monomer is selected from the group consisting of acrylates, methacrylates, monomers comprising vinyl groups, monomers comprising alkyne groups and monomers comprising maleimide groups, thereby forming a plurality of covalent bonds between the free thiol groups and the monomer;

[0297] Thereby improving the elongation at break of keratin-containing materials.

[0298] In another aspect, the present disclosure provides a method for treating a keratin-containing material, wherein the elongation at break of the keratin-containing material is improved, the method comprising:

[0299] i) providing a sample of keratin-containing material comprising a plurality of disulfide bonds; and

[0300] ii) applying a mixture comprising a reducing agent and a monomer to the sample of keratin-containing material for a period of time; wherein the monomer is selected from acrylates, methacrylates, monomers comprising vinyl groups, monomers comprising alkyne groups and monomers comprising maleimide groups, thereby forming a plurality of free thiol groups, which react with the monomer to form a plurality of covalent bonds between the free thiol groups and the monomer;

[0301] Thereby improving the elongation at break of keratin-containing materials.

[0302] In some embodiments, the elongation at break of a keratin-containing material is used to evaluate the strength of the material. Stronger materials can withstand greater stress and strain. Stronger materials can stretch further before breaking.

[0303] In another aspect, the present disclosure provides a method of treating a keratin-containing material, wherein the Young's modulus of the keratin-containing material is improved, the method comprising:

[0304] i) providing a sample of a keratin-containing material comprising a plurality of disulfide bonds;

[0305] ii) applying a mixture comprising a reducing agent to a sample of keratin-containing material for a period of time, wherein the sample of keratin-containing material comprises a plurality of free thiol groups; and

[0306] iii) applying a monomer to the keratin-containing material sample, wherein the monomer is selected from the group consisting of acrylates, methacrylates, monomers comprising vinyl groups, monomers comprising alkyne groups and monomers comprising maleimide groups, thereby forming a plurality of covalent bonds between the free thiol groups and the monomer;

[0307] Thereby improving the Young's modulus of keratin-containing materials.

[0308] In another aspect, the present disclosure provides a method of treating a keratin-containing material, wherein the Young's modulus of the keratin-containing material is improved, the method comprising:

[0309] i) providing a sample of a keratin-containing material comprising a plurality of disulfide bonds;

[0310] ii) applying a mixture comprising a reducing agent and a catalyst to a sample of keratin-containing material for a period of time, wherein the sample of keratin-containing material comprises a plurality of free thiol groups; and

[0311] iii) applying a monomer to the keratin-containing material sample, wherein the monomer is selected from the group consisting of acrylates, methacrylates, monomers comprising vinyl groups, monomers comprising alkyne groups and monomers comprising maleimide groups, thereby forming a plurality of covalent bonds between the free thiol groups and the monomer;

[0312] Thereby improving the Young's modulus of keratin-containing materials.

[0313] In another aspect, the present disclosure provides a method of treating a keratin-containing material, wherein the Young's modulus of the keratin-containing material is improved, the method comprising:

[0314] i) providing a sample of keratin-containing material comprising a plurality of disulfide bonds; and

[0315] ii) applying a mixture comprising a reducing agent and a monomer to the sample of keratin-containing material for a period of time; wherein the monomer is selected from acrylates, methacrylates, monomers comprising vinyl groups, monomers comprising alkyne groups and monomers comprising maleimide groups, thereby forming a plurality of free thiol groups, which react with the monomer to form a plurality of covalent bonds between the free thiol groups and the monomer;

[0316] Thereby improving the Young's modulus of keratin-containing materials.

[0317] In another aspect, the present disclosure provides a method of treating a keratin-containing material, wherein the ultimate tensile strength of the keratin-containing material is improved, the method comprising:

[0318] i) providing a sample of a keratin-containing material comprising a plurality of disulfide bonds;

[0319] ii) applying a mixture comprising a reducing agent to a sample of keratin-containing material for a period of time, wherein the sample of keratin-containing material comprises a plurality of free thiol groups; and

[0320] iii) applying a monomer to the keratin-containing material sample, wherein the monomer is selected from the group consisting of acrylates, methacrylates, monomers comprising vinyl groups, monomers comprising alkyne groups and monomers comprising maleimide groups, thereby forming a plurality of covalent bonds between the free thiol groups and the monomer;

[0321] Thereby improving the ultimate tensile strength of keratin-containing materials.

[0322] In another aspect, the present disclosure provides a method of treating a keratin-containing material, wherein the ultimate tensile strength of the keratin-containing material is improved, the method comprising:

[0323] i) providing a sample of a keratin-containing material comprising a plurality of disulfide bonds;

[0324] ii) applying a mixture comprising a reducing agent and a catalyst to a sample of keratin-containing material for a period of time, wherein the sample of keratin-containing material comprises a plurality of free thiol groups;

[0325] iii) applying a monomer to the keratin-containing material sample, wherein the monomer is selected from the group consisting of acrylates, methacrylates, monomers comprising vinyl groups, monomers comprising alkyne groups and monomers comprising maleimide groups, thereby forming a plurality of covalent bonds between the free thiol groups and the monomer;

[0326] Thereby improving the ultimate tensile strength of keratin-containing materials.

[0327] In another aspect, the present disclosure provides a method of treating a keratin-containing material, wherein the ultimate tensile strength of the keratin-containing material is improved, the method comprising:

[0328] i) providing a sample of keratin-containing material comprising a plurality of disulfide bonds; and

[0329] ii) applying a mixture comprising a reducing agent and a monomer to the sample of keratin-containing material for a period of time; wherein the monomer is selected from acrylates, methacrylates, monomers comprising vinyl groups, monomers comprising alkyne groups and monomers comprising maleimide groups, thereby forming a plurality of free thiol groups, which react with the monomer to form a plurality of covalent bonds between the free thiol groups and the monomer;

[0330] Thereby improving the ultimate tensile strength of keratin-containing materials.

[0331] In some embodiments, the ultimate tensile strength of a keratin-containing material is used to evaluate the structural integrity of the material.Ultimate tensile strength is the ability of a material to withstand a load that tends to elongate the material.

[0332] In another aspect, the present disclosure provides a method of treating a keratin-containing material, wherein the protein loss level of the keratin-containing material is improved, the method comprising:

[0333] i) providing a sample of a keratin-containing material comprising a plurality of disulfide bonds;

[0334] ii) applying a mixture comprising a reducing agent to a sample of keratin-containing material for a period of time, wherein the sample of keratin-containing material comprises a plurality of free thiol groups; and

[0335] iii) applying a monomer to the keratin-containing material sample, wherein the monomer is selected from the group consisting of acrylates, methacrylates, monomers comprising vinyl groups, monomers comprising alkyne groups and monomers comprising maleimide groups, thereby forming a plurality of covalent bonds between the free thiol groups and the monomer;

[0336] Thereby improving the protein loss value of keratin-containing materials.

[0337] In another aspect, the present disclosure provides a method of treating a keratin-containing material, wherein the protein loss level of the keratin-containing material is improved, the method comprising:

[0338] i) providing a sample of a keratin-containing material comprising a plurality of disulfide bonds;

[0339] ii) applying a mixture comprising a reducing agent and a catalyst to a sample of keratin-containing material for a period of time, wherein the sample of keratin-containing material comprises a plurality of free thiol groups; and

[0340] iii) applying a monomer to the keratin-containing material sample, wherein the monomer is selected from the group consisting of acrylates, methacrylates, monomers comprising vinyl groups, monomers comprising alkyne groups and monomers comprising maleimide groups, thereby forming a plurality of covalent bonds between the free thiol groups and the monomer;

[0341] Thereby improving the protein loss value of keratin-containing materials.

[0342] In another aspect, the present disclosure provides a method of treating a keratin-containing material, wherein the protein loss level of the keratin-containing material is improved, the method comprising:

[0343] i) providing a sample of keratin-containing material comprising a plurality of disulfide bonds; and

[0344] ii) applying a mixture comprising a reducing agent and a monomer to the sample of keratin-containing material for a period of time; wherein the monomer is selected from acrylates, methacrylates, monomers comprising vinyl groups, monomers comprising alkyne groups and monomers comprising maleimide groups, thereby forming a plurality of free thiol groups, which react with the monomer to form a plurality of covalent bonds between the free thiol groups and the monomer;

[0345] Thereby improving the protein loss value of keratin-containing materials.

[0346] In some embodiments, the protein loss value of the keratin-containing material is used to evaluate the strength and structural integrity of the material. For example, after chemical treatments such as bleaching, perming or straightening, the keratin-containing material will be damaged, resulting in higher protein loss. Higher protein loss values ​​are associated with more damage and lower structural integrity.

[0347] In another aspect, the present disclosure provides a method for treating a keratin-containing material, wherein the denaturation temperature of the keratin-containing material is improved, the method comprising:

[0348] i) providing a sample of a keratin-containing material comprising a plurality of disulfide bonds;

[0349] ii) applying a mixture comprising a reducing agent to a sample of keratin-containing material for a period of time, wherein the sample of keratin-containing material comprises a plurality of free thiol groups; and

[0350] iii) applying a monomer to the keratin-containing material sample, wherein the monomer is selected from the group consisting of acrylates, methacrylates, monomers comprising vinyl groups, monomers comprising alkyne groups and monomers comprising maleimide groups, thereby forming a plurality of covalent bonds between the free thiol groups and the monomer;

[0351] Thereby improving the denaturation temperature of keratin-containing materials.

[0352] In another aspect, the present disclosure provides a method for treating a keratin-containing material, wherein the denaturation temperature of the keratin-containing material is improved, the method comprising:

[0353] i) providing a sample of a keratin-containing material comprising a plurality of disulfide bonds;

[0354] ii) applying a mixture comprising a reducing agent and a catalyst to a sample of keratin-containing material for a period of time, wherein the sample of keratin-containing material comprises a plurality of free thiol groups; and

[0355] iii) applying a monomer to the keratin-containing material sample, wherein the monomer is selected from the group consisting of acrylates, methacrylates, monomers comprising vinyl groups, monomers comprising alkyne groups and monomers comprising maleimide groups, thereby forming a plurality of covalent bonds between the free thiol groups and the monomer;

[0356] Thereby improving the denaturation temperature of keratin-containing materials.

[0357] In another aspect, the present disclosure provides a method for treating a keratin-containing material, wherein the denaturation temperature of the keratin-containing material is improved, the method comprising:

[0358] i) providing a sample of keratin-containing material comprising a plurality of disulfide bonds; and

[0359] ii) applying a mixture comprising a reducing agent and a monomer to the sample of keratin-containing material for a period of time; wherein the monomer is selected from acrylates, methacrylates, monomers comprising vinyl groups, monomers comprising alkyne groups and monomers comprising maleimide groups, thereby forming a plurality of free thiol groups, which react with the monomer to form a plurality of covalent bonds between the free thiol groups and the monomer;

[0360] Thereby improving the denaturation temperature of keratin-containing materials.

[0361] In some embodiments, the denaturation temperature of a keratin-containing material is used to evaluate the strength and structural integrity of the material. For example, after chemical treatments such as bleaching, perming or straightening, the keratin-containing material may be damaged. Damaged materials are associated with a reduced denaturation temperature.

[0362] In some embodiments of the methods disclosed herein, the treated keratin-containing material is evaluated by sensory evaluation. In some embodiments, the sensory evaluation is blind. In some embodiments, the results of the sensory evaluation are classified as "none", "moderate conditioning" or "very product-y". In some embodiments, a relatively high grafting efficiency is associated with a very product-y sensory evaluation result.

[0363] In some embodiments, the treated keratin-containing material is similar to native keratin-containing material. In some embodiments, the treated keratin-containing material has similar properties to native keratin-containing material.

[0364] In some embodiments, the keratin-containing material treatment provides a wash-resistant functional (ie, hydrophobic) layer.

[0365] In some embodiments, the treated keratin-containing material is treated hair. In some embodiments, the treated hair simulates the 18-MEA conditioning layer of virgin hair. In some embodiments, the monomers on the treated hair reinstall a hydrophobic "healthy hair" layer.

[0366] In some embodiments, the hair treatment provides a wash-resistant functional (i.e., hydrophobic) layer. In some embodiments, the treated hair has improved alignment. In some embodiments, the treated hair has durable smoothness. In some embodiments, the treated hair has improved gloss. For example, the health of the hair can be assessed based on one or more of elongation at break, Young's modulus, ultimate tensile strength, protein loss value, and denaturation temperature.

[0367] In some embodiments, the treated keratin-containing material is a treated nail. In some embodiments, the nail is a fingernail or a toenail. In some embodiments, the treated nail is similar to an original nail or a new nail. In some embodiments, the treated nail improves flexibility. In some embodiments, the brittleness of the treated nail is low. For example, brittleness can be assessed based on one or more of elongation at break, Young's modulus, ultimate tensile strength, protein loss value, and denaturation temperature.

[0368] Example Kit

[0369] One aspect of the present disclosure provides a kit comprising: a reducing composition comprising a reducing agent; a monomer composition comprising a monomer; and instructions for use.

[0370] In some embodiments, the reducing composition comprises a reducing agent; and a solvent.

[0371] In some embodiments, the monomer composition comprises a monomer; and a solvent.

[0372] In some embodiments, the solvent comprises dimethyl sulfoxide, water, acetone, a buffer, or a mixture thereof. In some embodiments, the solvent comprises water. In some embodiments, the solvent is water.

[0373] Another aspect of the present disclosure provides a kit comprising: a mixture comprising a reducing agent and a catalyst; a monomer composition comprising a monomer; and instructions for use.

[0374] Another aspect of the present disclosure provides a kit comprising: a mixture comprising a reducing agent and a monomer; and instructions for use.

[0375] In some embodiments of the kits disclosed herein, the reducing agent concentration is from about 0.1 wt % to about 15 wt %.

[0376] In some embodiments of the kits disclosed herein, the monomer is selected from the group consisting of acrylates, methacrylates, monomers comprising vinyl groups, monomers comprising alkyne groups, and monomers comprising maleimide groups.

[0377] Example

[0378] Having now generally described the invention, it will be more readily understood by referring to the following, which is introduced merely for the purpose of illustrating certain aspects and embodiments of the invention and is not intended to limit the invention.

[0379] Example 1 - Hair Restoration

[0380] In order to convert the hair keratin disulfide bonds to free thiols, the hair fiber must be exposed to and allowed to react with a reducing agent. While this reduction process has been well studied in the case of permanent hair curling, 17-19 However, conditions that reduce hair with minimal damage have yet to be found. Reduction of the entire hair fiber is accomplished using ammonium thioglycolate (ATG), and Table 2 shows the ATG reduction parameters adjusted to provide adequate thiol content while minimizing hair damage. Similar information is given in Table 3 for L-cysteine, a reducing agent that is active only at the surface of the hair.

[0381] Table 2: Bulk reduction parameters for achieving adequate thiol content and minimal damage.

[0382] parameter Available range Scope of the study Preferred level ATG concentration 1 wt% to 11 wt% 5 wt% to 30 wt% 5 wt% Liquid ratio 3:1 to 10:1 2:1 to 100:1 5:1 time 15-30 minutes 2-25 minutes 15 minutes pH 7-10 7.5-10.5 9.5

[0383] Table 3: Surface reduction parameters for achieving sufficient thiol content and minimal damage.

[0384]

[0385] Ellman Method

[0386] The reduction of disulfide bonds to free thiols was monitored using the Ellman method, which consists of thiol derivatization and subsequent spectroscopic methods. 20 First, a known concentration of the molecule 5,5'-dithiobis-(2-nitrobenzoic acid) (DTNB, Ellman's reagent) is stirred in solution with the hair fibers. DTNB reacts with thiols to form an equimolar mixture of mixed disulfides and UV-active TNB moieties ( Figure 4 ), followed by UV-VIS spectroscopy and comparison with a calibration curve obtained using L-cysteine ​​standards. TNB intensity was quantified at 407 nm. This method allows for μmol / mg quantification of free thiols present on hair.

[0387] This method also allows for μmol / mg quantification of free thiols present on other keratin-containing materials.

[0388] Concentration of reducing agent

[0389] As the concentration of ATG decreases, the conversion of disulfide bonds to free thiols increases (Table 4). The experiments were performed at a pH of 9.5 and a liquid ratio of 10:1 (mixture to hair sample weight ratio) for 15 minutes. Therefore, the preferred concentration of ATG for grafting is 5 wt%.

[0390] Table 4: Free thiol contents obtained using different ATG concentrations

[0391] ATG concentration (wt%) Free thiols (μmol / g hair) 5 38±3 10 41±2 20 24±1 30 17±1

[0392] Liquid ratio

[0393] The weight ratio of reducing solution to hair fiber - referred to in the textile industry as "liquor ratio" - has been shown to be an important parameter. As the liquor ratio decreases, the free thiol content after reduction increases (Table 5). The experiments were performed at a pH of 9.5 and 5 wt% ATG for 15 minutes. This effect is most likely due to the pseudo-primary nature of disulfide bond reduction, in which ATG is in large excess. Therefore, with an effective increase in disulfide bond concentration, the disulfide bond cleavage rate increases (Equation 1). 9,17 With lower liquor ratios, the level of visually observed hair fiber damage was lower ( Figure 5 ). In other words, as the liquor ratio increases, the fibers show more visible damage. For these two reasons, the preferred liquor ratio for grafting in the range of ratios studied is 5:1.

[0394] Table 5: Thiol content measured by Ellman's reagent using different liquid ratios during reduction

[0395] ratio Free thiols (μmol / g hair) 2:1 35±6 5:1 51±4 10:1 36±3 25:1 32±3 100:1 23±3

[0396]

[0397] Formula 1: Rate formula for disulfide bond reduction.

[0398] Restore time

[0399] The timing of the reduction step was varied to allow for sufficient conversion of disulfide bonds to free thiols without exposing the hair to the damaging reducing solution for longer than necessary. Kinetic studies of the reduction process showed that 15 minutes was sufficient to achieve maximum hair reduction ( Figure 6 ). The experiments were performed at a pH of 9.5 and 5 wt% ATG with a liquor ratio of 5:1. It should be noted that the maximum thiol content as measured by the Ellman method is much lower than that obtained using amino acid analysis (~800 μmol / g hair). 9 It is possible that measurements using Ellman's method are primarily limited to the surface of hair, most likely due to its relatively large molecular size.

[0400] N-ethylmaleimide assay

[0401] N-ethylmaleimide (NEM) is another reagent that reacts specifically with thiol groups to form stable thioether groups at pH 6.5-7.5 ( Figure 7 ). Since NEM has a characteristic absorption peak at 300nm in its UV-vis spectrum, the reaction can be monitored by the decrease in absorbance at 300nm. Compared with Ellman's reagent, NEM is a much smaller molecule and is therefore able to penetrate the epidermis into the cortical region. It is expected that the NEM assay will provide a bulk measurement of the thiol content in the hair sample. In a typical experiment, a known concentration of NEM is mixed with hair fibers in a phosphate buffered saline (PBS) solution containing 0.1M phosphate, 0.15M sodium chloride, and a pH of 7.2. The level of NEM concentration reduction is used to quantify the free thiol content on the hair.

[0402] When the experiment was carried out at a pH of 9.5 and 5 wt% ATG with a liquor ratio of 5:1, the thiol content was measured by the NEM assay in the range of 600-800 μmol / g hair. This result is very similar to that obtained using amino acid analysis. 9 The results showed that the NEM assay can be used as a bulk measurement method for quantification of thiols in hair samples, while the Ellman method is more useful for surface thiol content measurement.

[0403] This method also allows for μmol / mg quantification of free thiols present on other keratin-containing materials.

[0404] Example 2 - Grafting Monomers to Hair

[0405] Free radical thiol-ene grafting

[0406] Synthesis Procedure

[0407] One possible route to covalently attach monomers is the free radical thiol-ene grafting method, in which ene-functional monomers begin to polymerize at the thiol functional group when irradiated with UV light. 365 nm light and the initiator 2,2'-diethoxyacetophenone (DEAP) in acetone or ethanol are used to initiate the grafting of acrylates and vinyl ethers from the surface thiols of reduced hair ( Figure 8 ).

[0408] Choice of hydrophobic monomer

[0409] A variety of hydrophobic acrylates, vinyl ethers, and vinyl silanes have been studied (Table 6, Fig. 9 An exemplary structure-activity test was performed in which monomers were grafted onto reduced hair strands and then evaluated using Fourier transform infrared (FTIR) spectroscopy and sensory evaluation.

[0410] Thiol-Michael grafting

[0411] Synthesis Procedure

[0412] Thiol-Michael addition of small alkenes (small olefin-containing molecules) has also been used as a grafting route to covalently attach small molecules to hair. Without being bound by any theory, it is believed that depending on the initiator (catalyst), the reaction can proceed via either or both of the following two pathways: nucleophilic initiation and base catalysis. 21 Both reaction pathways were studied using different initiating reagents: amine-based catalysts, which can undergo both base-catalyzed and nucleophilic initiation pathways; and tertiary phosphine-based catalysts, which predominantly give rise to nucleophilic initiation. 21 For all thiol-Michael addition reaction studies, hexyl acrylate and N-ethylmaleimide (NEM) molecules were used as model monomers and dimethyl sulfoxide (DMSO), acetone, water or their mixtures were used as solvent systems. Important parameters that determine the reaction efficiency, such as monomer to thiol ratio, choice of solvent, catalyst concentration and liquid ratio were optimized.

[0413] Nucleophile-catalyzed thiol-Michael grafting (phosphine catalyst)

[0414] The thiol-Michael reaction is an addition mechanism that can occur between a thiol and an activated (electron-withdrawing) ene in the presence of a base or a nucleophilic catalyst. The nucleophilic reaction is usually mediated by a phosphine catalyst or by a primary or secondary amine. 22

[0415] The nucleophile-induced thiol-Michael addition reaction was studied using tertiary phosphine as catalyst and hexyl acrylate as model monomer. Without being bound by any theory, e.g. Fig.10 As proposed in , the reaction begins with a nucleophilic attack of the catalyst on the double bond of the monomer, which results in the formation of a basic carbanion, which further reacts with a free thiol to form the desired thiolate anion. In the addition step, the thiolate anion reacts with another molecule of the monomer to produce a product in anionic form, which further undergoes deprotonation in the presence of another free thiol. As a result, the final product and another thiolate anion are formed. The newly formed thiolate anion then undergoes the same chain transfer process described above, resulting in a very fast reaction rate. 21

[0416] Preferred grafting parameters

[0417] Four main parameters were varied for each system to achieve the preferred grafting conditions. Table 7 shows the preferred parameters for grafting with hexyl acrylate in the presence of a tertiary phosphine catalyst.

[0418] Table 7: Preferred grafting parameters for grafting hexyl acrylate using tertiary phosphine catalyst dimethylphenylphosphine

[0419]

[0420] Liquid ratio

[0421] Similar to the reduction process, the "liquid ratio" in the grafting process refers to the weight ratio of the total grafting solution to the hair fiber. For grafting, it is important to supply just enough liquid to saturate the entire hair strand. Any additional liquid only serves to dilute the concentration of hair thiols in the reducing system. Liquor ratios between 20:1 and 5:1 were studied. An equilibrium was found at the preferred grafting liquid ratio of 5:1.

[0422] Monomer to Thiol Ratio

[0423] The reaction efficiency was studied at different monomer to thiol ratios. For each experimental condition, the catalyst concentration was kept constant at 30 mol% relative to the monomer concentration. Based on empirical data obtained from the NEM assay, the free thiol concentration of the reduced hair samples was assumed to be 800 μmol free thiol / g hair. All further calculations of the monomer to thiol ratio were based on this assumption.

[0424] A wide range of monomer to thiol ratios from 1:1 to 10:1 was investigated. From the first series of experiments, it was found that a 5:1 monomer to thiol ratio gave a peak in the carbonyl peak region (about 1730 cm -1 ) produced the strongest peak, which corresponds to the presence of carbonyl groups of hexyl acrylate on the hair. In addition, for the 5:1 ratio, the alkyl peak region on the FTIR (approximately 3000-2800 cm -1 ) also shows the strongest signal ( Fig.11 ). The tertiary phosphine catalyst was kept constant at a concentration of 30 mol% relative to the acrylate. All spectra shown are of locks washed thoroughly with sodium laureth sulfate (SLES).

[0425] In the next set of experiments, lower monomer to thiol ratios (less than 5:1) were used while keeping the catalyst concentration constant under all conditions to truly investigate the effect of the concentration of monomer relative to thiol groups on hair. Fig.12 As can be seen in Figure 1, 1:1, 2.5:1 and 5:1 monomer to thiol ratios were explored. The preferred monomer to thiol ratio was found to be 2.5:1. The alkyl peak region (about 3000-2800 cm -1 ) and carbonyl peak region (about 1730cm -1 ) both show the strongest peak intensity for a monomer to thiol to catalyst ratio of 2.5:1:1. All spectra shown are of the locks after thorough SLES washing.

[0426] Catalyst concentration

[0427] Once the preferred monomer to thiol ratio was determined, the effect of catalyst concentration was investigated. Previous results showed that a monomer to thiol ratio of 2.5:1 was preferred. In this study, a 40 mol % tertiary phosphine catalyst was used. For the preferred monomer to thiol ratio of 2.5:1, a systematic study was conducted to cover catalyst concentrations of 20 mol % to 50 mol % relative to acrylate concentration. It was found that at monomer to thiol to catalyst ratios of 2.5:1:1 and 2.5:1:1.25, corresponding to catalyst concentrations of 40 mol % and 50 mol % relative to acrylate, the carbonyl peak region on the FTIR spectrum (approximately 1730 cm -1 ) produces the strongest peak ( Fig.13 ). All spectra shown are those of locks after thorough SLES washing. Since no significant advantage was observed using a high catalyst concentration of 50 mol %, the catalyst concentration was fixed at 40 mol % for the following experiments.

[0428] Solvent system

[0429] In all initial experiments, dimethyl sulfoxide (DMSO) was used as the sole solvent. However, due to the potential high permeability of DMSO through biological systems, experiments were initiated to test other more benign solvents. As a starting point, mixed solvent systems were explored in which DMSO was mixed with water at various weight ratios. Under the preferred grafting conditions found using DMSO as solvent (a monomer to thiol to catalyst ratio of 2.5:1:1), water was introduced to replace 50%, 75%, 90% and 100% of the DMSO.

[0430] As from Fig.14 As can be seen, the mixed solvent system in which water replaced 90% of DMSO showed the best results over the solvent systems of DMSO alone or water alone. Without being bound by theory, this result can be attributed to the high concentration of topical delivery of the reagent to the reactive thiol groups on the hair. The carbonyl peak region of the spectrum (about 1730 cm -1 ) and the alkyl peak region (about 3000-2800cm -1 ) shows the strongest peak intensity for the mixed DMSO / H2O solvent system at 90% H2O-10% DMSO concentration. All spectra shown are spectra of hair locks after thorough SLES washing.

[0431] Hexyl acrylate model monomer was successfully grafted onto thiol groups of hair via thiol-Michael addition using a tertiary phosphine as initiator. After systematically varying parameters, the preferred conditions that produced effective grafting based on FTIR spectroscopy included a 2.5:1 monomer to thiol ratio, a catalyst concentration of 40 mol% relative to monomer concentration, a 5:1 liquid ratio, and a H2O / DMSO solvent system at 90% H2O and 10% DMSO concentrations. The phosphine catalyst was found to be very active. The reaction was complete within 1 hour in the H2O / DMSO solvent system.

[0432] Nucleophile- and base-catalyzed thiol-Michael grafting (amine catalyst)

[0433] Thiol-Michael grafting can also be mediated by amine catalysts, which can proceed via a combination of basic and nucleophilic pathways, depending on the structure of the amine. Without being bound by any theory, it is believed that primary and secondary amines are generally assumed to proceed via both mechanisms, while tertiary amines act only as basic catalysts. 21 Not bound by any theory, Fig.15 A proposed mechanism for the base-mediated pathway is shown, which begins with the deprotonation of the thiol under the action of base to form a thiolate anion. 21 Chain extension occurs via β-addition of a thiol anion to the activated carbonyl group and subsequent transfer of a proton from the protonated base to form a thiol-Michael adduct.

[0434] Preferred grafting parameters

[0435] Four major parameters were varied for the amine catalyzed system to achieve the preferred grafting conditions. Table 8 shows the preferred parameters for grafting with hexyl acrylate in the presence of a secondary amine catalyst.

[0436] Table 8: Preferred grafting parameters for grafting of hexyl acrylate using the secondary amine catalyst di-n-propylamine (DNPA).

[0437]

[0438] Table 9 shows preferred parameters for reducing the hair-to-hair thiol grafting monomers for exemplary embodiments.

[0439] Table 9: Preferred grafting parameters for grafting exemplary monomers with catalysts.

[0440]

[0441] Liquid ratio

[0442] As in the disclosed reduction process and the phosphine-mediated grafting process, for the secondary amine grafting system, a liquor ratio of 5:1 was found to be preferred to ensure that the hair was fully saturated with the high concentration of active.

[0443] catalyst

[0444] The effect of catalyst concentration was also investigated. In this study, the mole % of the secondary amine catalyst DNPA relative to the monomer was investigated at values ​​of 30 mol %, 60 mol % and 90 mol %.

[0445] In this systematic study, it was found that at a 1:1 monomer to thiol ratio, the carbonyl peak intensity did not change significantly with the amount of catalyst used ( Fig.16 ). Carbonyl peak area (about 1730cm -1 ) showed a modest dose response. The peak intensity increased slightly with increasing mol% of catalyst. All spectra shown are spectra of the locks after thorough SLES washing. Therefore, additional studies were performed using a catalyst concentration of 30 mol%.

[0446] Monomer to Thiol Ratio

[0447] The reaction efficiency was studied at different monomer to thiol ratios. For each experimental condition, the catalyst concentration was kept constant at 30 mol% relative to the monomer concentration. Based on empirical data obtained from the NEM assay, the free thiol concentration of the reduced hair samples was assumed to be 800 μmol free thiol / g hair. All further calculations of the monomer to thiol ratio were based on this assumption.

[0448] A wide range of monomer to thiol ratios from 1:1 to 30:1 was investigated. From this series of experiments it was found that for the 10:1 ratio the intensity of the carbonyl peak was as strong as that observed for the 30:1 ratio ( Fig.17 ).

[0449] Solvent system

[0450] In all initial experiments, dimethyl sulfoxide (DMSO) was used as solvent because it is known to promote efficient thiol-Michael addition reactions. 23 However, due to the potentially high permeability of DMSO through biological systems, experiments were initiated to test other solvents.

[0451] Experiments were conducted to investigate the effect of water as a solvent or co-solvent on the grafting of hexyl acrylate to hair using a secondary amine catalyst. Here, hexyl acrylate was grafted to hair at a 1:10:3 thiol to monomer to catalyst ratio in various solvent compositions containing water at concentrations ranging from 50% to 100% by weight. Fig.18 It is shown that, in general, as the proportion of water in the solvent mixture increases, the intensity of the carbonyl peak also increases.

[0452] It is noteworthy that, although the carbonyl peak intensity tends to increase with the amount of water in the solvent mixture, the peak observed within each sample is less uniform than that observed when grafted entirely in DMSO. Without being bound by any theory, it is speculated that micellization of the organic material (monomer, catalyst, optional DMSO) in water results in significant grafting on the hair in certain high concentration regions but not in other regions.

[0453] Thiol-Michael Grafting of Maleimide (without Catalyst)

[0454] Compared to acrylates, maleimides are much more reactive due to their highly electron-deficient olefinic groups. 21 In this study, all maleimide grafting experiments were performed in PBS solution (0.1 M phosphate and 0.15 M sodium chloride, pH 7.2) without any catalyst. The main parameters, including liquid ratio, monomer to thiol ratio and reaction time, were changed to achieve the preferred grafting conditions. Table 10 shows the preferred parameters for grafting using NEM.

[0455] Table 10: Preferred grafting parameters for NEM grafting in PBS buffer

[0456] parameter Scope of the study Preferred conditions Liquid ratio 5:1 to 20:1 5:1 Monomer to Thiol Ratio 0.5:1 to 3:1 1.5:1 Reaction time 0-120 minutes 30 minutes

[0457] Liquid ratio

[0458] Similar to the disclosed hexyl acrylate grafted system, a 5:1 liquor ratio was found to be preferred to ensure that the hair was fully saturated with the high concentration of active.

[0459] Monomer to Thiol Ratio

[0460] Grafting efficiency was evaluated at different NEM to thiol ratios. All experiments were performed for 1 hour at the preferred liquor ratio of 5:1. The amount of thiol grafted by the NEM was determined using the NEM assay described in Example 1. Table 11 shows that the maximum amount of thiol was consumed at a NEM to thiol ratio of 1.5:1, indicating that the maximum amount of NEM grafting was achieved under this condition.

[0461] Table 11: Optimization of NEM to thiol ratios to achieve maximum thiol consumption and hence optimal NEM grafting

[0462]

[0463] Reaction time

[0464] Different reaction times were also explored to determine the preferred reaction time. Fig.19 The amount of thiol consumed during the 2 hour NEM grafting process is shown. The maximum amount of grafting was achieved already within the first 30 minutes. These results clearly show that NEM is highly reactive compared to hexyl acrylate, which generally requires a minimum of 1 hour of reaction time to achieve significant grafting.

[0465] Grafting with other maleimides

[0466] To further explore other maleimides, a series of succinimidyl-[(N-maleimidopropionamido)-diethylene glycol] esters (NHS-PEG n -maleimide), each of which has the same heterobifunctional structure but with different numbers of discrete ethylene glycol units (n=2, 6, 12, 24). In this case, in addition to the maleimide group reacting with the thiol group on the hair, the N-hydroxysuccinimide ester (NHS) group can also react with the amine group on the hair to further improve the grafting efficiency. Preliminary screening studies showed that all NHS-PEG n -maleimide were successfully grafted, which was confirmed by the obvious characteristic peaks in their FTIR spectra ( Fig. 20A and Fig. 20B ).

[0467] Simultaneous reduction and grafting

[0468] A "one-step" method of simultaneous reduction and grafting was also developed, which is a more efficient method for covalently attaching molecules to hair. The benefits of this method are greatly reduced processing time and less overall hair damage. A reducing solution using ammonium thioglycolate (ATG), L-cysteine ​​and glutathione was explored as a solvent medium. Due to regulatory restrictions on the use of di-n-propylamine (DNPA), a tertiary amine - triethylamine - was also explored as an alternative catalyst. Hexyl acrylate was used as a model monomer, but other acrylated monomers were also used to demonstrate simultaneous grafting. Important parameters such as the monomer to thiol ratio, choice of reducing medium, reducing agent concentration and catalyst concentration were varied.

[0469] Preferred grafting parameters

[0470] The grafting parameters for simultaneous grafting specificity include five different parameters. The liquid ratio for all studies was set to 5:1 because it has the highest grafting efficiency based on two-step grafting. Table 12 shows the preferred parameters for grafting using hexyl acrylate in the presence of a tertiary amine catalyst.

[0471] Table 12: Preferred simultaneous grafting parameters for grafting hexyl acrylate using tertiary amine catalyst trimethylamine

[0472]

[0473] Table 13 shows preferred parameters for simultaneous reduction and grafting of thiol monomers to hair for exemplary embodiments.

[0474] Table 13: Preferred grafting parameters for simultaneous reduction and grafting of exemplary monomers with catalyst.

[0475]

[0476] Reducing agent type

[0477] The most important difference between two-step grafting and one-step simultaneous grafting is the use of a reducing agent solution as a solvent system for grafting. Previously, in the two-step reduction grafting disclosed herein, water, an organic solvent, or a mixture thereof was used as a solvent system. A reserve reducing agent solution for simultaneous grafting was prepared in water at a concentration of 5 wt %. Three different reducing agents were explored in this study: ammonium thioglycolate (ATG), L-cysteine, and glutathione. Previous results of a two-step grafting method using an amine catalyst, di-n-propylamine, showed that the preferred monomer to thiol ratio was 10:1, and the catalyst was 30 mol % relative to the monomer. Therefore, all experiments here were performed under the same conditions. Fig.21 It was shown that a one-step process of simultaneous reduction and grafting in the presence of 3.5 wt% ATG or L-cysteine ​​relative to the total mixture concentration resulted in similar grafting after 1 h of reaction, with a peak at 1730 cm -1There are strong and obvious carbonyl peaks near the 5-hydroxy-1-hydroxy-2-yl group. These peaks indicate that both solutions have quite high grafting efficiency. All spectra shown are spectra of hair strands after thorough SLES washing.

[0478] Reducing agent concentration

[0479] A wide concentration range of reducing agent ATG between 0.5 wt% and 3.5 wt% was explored. In this study, the monomer to thiol ratio was kept at 10:1 and the catalyst concentration was kept at 30 mol% DNPA relative to the monomer. A clear positive dose response was observed with increasing ATG concentration, indicating higher grafting efficiency ( Fig. 22 ). All spectra shown are those of locks after thorough SLES washing. 3.5 wt% ATG at 1730 cm -1 The strongest carbonyl peak was produced near , while distinct peaks were also observed when using ATG concentrations of 1.5 wt% and 2.5 wt%. This suggests that lower preferred ATG concentrations can be used to reduce overall hair damage.

[0480] Monomer to Thiol Ratio

[0481] Since a 10:1 monomer to thiol ratio was found to result in high grafting efficiency, a ratio range of 0.5:1 to 10:1 was explored, with the catalyst concentration maintained at 30 mol % relative to the monomer. Fig.23A and 23B A clear positive dose response is shown with increasing monomer to thiol ratios obtained after 30 minutes of simultaneous grafting.

[0482] Catalyst selection

[0483] The secondary amine catalyst di-n-propylamine (DNPA) was previously identified as the lead catalyst in a two-step reduction and grafting process. It was also demonstrated that DNPA can be used in a one-step simultaneous reduction and grafting process, which resulted in high grafting efficiency. However, due to regulatory and safety restrictions on the use of DNPA catalysts in personal care, a tertiary amine, triethylamine (TEA), was explored. TEA was added at 30 mol% relative to the monomer and the monomer to thiol ratio was maintained at 10:1.

[0484] FTIR spectra of hair strands after simultaneous grafting with hexyl acrylate using TEA as catalyst and ATG reducing solution as solvent medium for 15 minutes, 30 minutes and 1 hour. All spectra shown are spectra of hair strands after thorough SLES washing. A peak at 1730 cm was observed just 15 minutes after simultaneous grafting. -1 The reaction appears to progress further with time and shows a stronger peak intensity after 1 hour ( Fig.24). This shorter time frame of 15 minutes for simultaneous reduction and grafting will be an advantage of this grafting method, as opposed to conventional chemical methods (two-step method: reduction for 15 minutes and grafting for up to 1 hour). In addition, the time frame of such grafting can be optimized based on the reaction kinetics observed here to achieve the desired grafting level.

[0485] The efficiency achieved using tertiary amines as catalysts was unexpected, since it is known from the literature that tertiary amines lead to slower reaction rates than secondary amines. Fig.25 As can be seen in the figure, the reaction initiated by TEA in the simultaneous grafting achieved a much higher grafting efficiency ( Fig.25 Without being bound by any theory, it is speculated that the unique basic conditions in which simultaneous grafting occurs in the presence of triethylamine promotes a base-catalyzed reaction pathway.

[0486] Catalyst concentration

[0487] The grafting efficiency was further evaluated based on different triethylamine concentrations. Due to regulatory restrictions on the use of hexyl acrylate as a monomer in personal care, minimizing the monomer to thiol ratio is of interest. Therefore, a systematic study was performed varying the TEA concentration between 10 mol% and 100 mol%, wherein the monomer to thiol ratio was reduced to 1:1.

[0488] At 10 mol %, 20 mol %, and 30 mol % TEA concentrations, similar carbonyl peak intensities were observed after 15 min of simultaneous grafting ( Fig.26A ), and the response does not progress over time ( Fig.26B However, as the TEA concentration increased to 60 mol % and 100 mol %, the grafting efficiency after 15 min was lower ( Fig.26C ), but the reaction still progressed after 1 hour, resulting in a strong peak intensity ( Fig.26D Without being bound by any theory, it is speculated that at high catalyst concentrations, the reaction is diffusion limited and therefore proceeds slowly, with high grafting efficiency being achieved after 1 hour.

[0489] Grafting on damaged hair

[0490] The main goal of the grafting process is to restore a healthy layer on the surface of the hair, especially for hair that has been severely damaged by bleaching and heat treatment. This hydrophobic layer is similar to the 18-MEA layer of healthy hair. For example, due to chemical bleaching, the disulfide bonds of cysteine ​​residues in the hair are oxidized to form cysteic acid groups. Since disulfide bonds provide mechanical connections within the proteins that make up the hair, degradation of the disulfide bonds may lead to degradation of the hair proteins and hair damage. In addition, during the bleaching process, the thioester bonds that bind 18-methyleicosanoic acid to the hair may be attacked by the alkaline bleaching agents, resulting in partial removal of this hydrophobic layer, thereby making the hair hydrophilic. 1Another common way to damage hair is through continuous heat treatments, such as straightening and curling at high temperatures. It is well known that within the temperature range of up to 230°C (450°F) commonly used in such hair styling treatments, the keratin structure of the hair begins to denature, especially above 200°C and in the presence of water. 24

[0491] Grafting on hair damaged by bleaching

[0492] Based on the encouraging results of grafting on virgin (undamaged) hair via simultaneous grafting, simultaneous grafting on bleached hair was explored. Experiments were conducted using 30 mol% TEA catalyst relative to monomer and in both 3.5 wt% concentration of L-cysteine ​​and ATG reducing solutions at a monomer to thiol ratio of 10:1.

[0493] In ATG reducing medium, under simultaneous grafting conditions, extensive grafting was achieved on bleached hair after only 15 minutes ( Fig.27A The reaction progressed over time, showing stronger carbonyl peaks after 30 minutes and 1 hour. It should be noted that the peak corresponding to the cysteic acid group appeared as expected after bleaching, indicating the level of sulfur oxidation and retention after grafting ( Fig.27B ). It appears that, although some disulfide bonds were converted to cysteic acid groups after bleaching, the remaining disulfide bonds were used in the simultaneous reduction and grafting.

[0494] When using the L-cysteine ​​reducing solution, slightly lower grafting efficiency was observed, but a clear progression of the reaction over time was observed after 15 minutes, 30 minutes, and 1 hour ( Fig.28A and Fig.28B Without being bound by any theory, the lower grafting efficiency obtained may be explained by the fact that L-cysteine ​​is a milder reducing agent than ATG and therefore causes reduction and grafting only on the surface of the hair. The data suggest that by using L-cysteine, a mild reducing agent, the hair surface can be targeted for grafting reaction, thereby minimizing damage within the hair cortex. When using strong reducing agents, damage within the hair cortex may occur.

[0495] Grafting on heat damaged hair

[0496] To simulate hair damage caused by heat, e.g., hair damage caused by the use of hot tools such as blow dryers, curling irons, flat irons, or other heat treatments, brown hair tresses were exposed to 26 applications of a styling iron at 400°F. Additionally, to further enhance the damage, some tresses were subjected to water sprays between heat applications. To study the effect of grafting, the hair was then reduced and grafted with hexyl acrylate using 30 mole % of DNPA catalyst relative to monomer in water at a monomer to thiol ratio of 10:1. Fig.29 As can be seen in Figure 5, the strong carbonyl peak intensity indicates that grafting is possible using hair that is severely damaged by heat treatment.

[0497] Additional Monomer Screening

[0498] Due to regulatory restrictions on the use of hexyl acrylate in personal care, other acrylated monomers were explored for simultaneous grafting. As a first round of such monomer screening, eight different acrylated monomers were investigated (Table 14, Fig.30 For all experiments, the monomer to thiol ratio was kept at 10:1 in the presence of 30 mol% TEA catalyst and the ATG reduction solution was used. After 15 min of reaction, the peak at 1730 cm -1 An obvious carbonyl peak was observed near Fig.31 ). All spectra shown are spectra of hair locks after thorough SLES washing. Among the four monomers tested in Table 14, the grafting efficiency is very high.

[0499] Semi-simultaneous reduction and grafting

[0500] Semi-simultaneous grafting process, where the reducing agent is applied and then the grafting monomer solution is applied immediately. No washing or rinsing is used between the two applications. PEG-diacrylate is used as the monomer.

[0501] Preferred grafting parameters

[0502] Since simultaneous grafting studies have shown that locks grafted with PEG-diacrylates bring favorable sensory attributes, PEG-diacrylates were selected as monomers for semi-simultaneous grafting studies. The grafting parameters specific for semi-simultaneous grafting include six different parameters: liquor ratio, monomer to thiol ratio, catalyst concentration, reaction time, reducing agent concentration, and pH. Table 15 shows the preferred parameters for semi-simultaneous grafting with PEG diacrylate (PEG-DA 700) having a molecular weight of about 700 g / mol. It is of interest to minimize the use of all chemicals and to perform the grafting under mild conditions, such as low reducing agent concentration, weakly alkaline pH, short reaction time, etc.

[0503] Table 15: Preferred semi-simultaneous grafting parameters for PEG-diacrylate grafting

[0504]

[0505] Liquid ratio

[0506] To reduce the use of chemicals, grafting at lower liquid ratios was also explored. Liquid ratio is the weight ratio of the mixture to the hair sample. The native ( Fig.32A ) or bleached ( Fig.32B ) FTIR spectra of hair strands. In both systems, very similar grafting was achieved when using a liquor ratio of 1.1:1 or higher; only at a liquor ratio of 0.7:1 was more uneven grafting observed. Blind sensory evaluations showed that grafted hair strands at any liquor ratio between 0.7:1 and 2.5:1 showed similar sensory properties, with all ratios exhibiting the desired sensory properties. Based on the FTIR and sensory evaluation results, a ratio of 1.1:1 was then selected as the preferred liquor ratio to achieve high grafting efficiency as well as the desired sensory properties.

[0507] Catalyst concentration

[0508] Due to regulatory and safety restrictions on the use of triethylamine (TEA) catalysts in personal care, minimizing TEA concentration is of interest. Fig.33 FTIR spectra of hair locks grafted with PEG-DA 700 in the presence of 0-30 mol% TEA (relative to the concentration of PEG-DA 700) are shown. Although maximum grafting was achieved at 30 mol% TEA, significant grafting was observed at all TEA concentrations and no clear differences were observed between no TEA and lower TEA concentrations (10-20 mol%). Blind sensory evaluations also showed that the feel of the locks was more favorable when TEA was not used. More specifically, the hair felt smoother, softer and more shaped when TEA was not used. Based on both the FTIR and sensory evaluation results, all subsequent grafting experiments were performed without any TEA catalyst.

[0509] Reducing agent concentration

[0510] Different reducing agent concentrations were explored. Fig.34 FTIR spectra of hair strands grafted with PEG-DA 700 at ATG concentrations of 1.5, 2.5, and 5 wt %. Although grafting efficiency decreased at the lowest ATG concentration of 1.5 wt %, grafting efficiency at 2.5 wt % was only slightly lower than at 5 wt %. Therefore, 2.5 wt % is considered to be the preferred ATG concentration.

[0511] pH

[0512] Grafting at a pH below 9.5 was also explored. Fig.35FTIR spectra of hair locks grafted with PEG-DA 700 at pH values ​​varying from about 8.0 to about 9.5 are shown. Very similar carbonyl peak intensities were observed for all pH values ​​in the range of 8.5-9.5, indicating that grafting can be achieved at any pH between 8.5 and 9.5. Therefore, pH 8.5 is considered to be the preferred pH for grafting under mild conditions.

[0513] PEG-Diacrylate Size Screening

[0514] Previously, although grafting of only a few different molecular weights of PEG-diacrylates was achieved when using the simultaneous grafting method, sensory evaluation did reveal a clear dose response, where more favorable lock feel was achieved as the molecular weight of the grafted PEG-diacrylate increased. Efficient grafting of PEG-diacrylates was achieved using the semi-simultaneous grafting method. Therefore, size screening of PEG-diacrylates using semi-simultaneous grafting was performed. FIG36 shows FTIR spectra of hair samples grafted with PEG-diacrylates having molecular weights of 700, 1k, and 2k Da (i.e., PEG-DA 700, 1k, and 2k) at the same molar concentration ( Fig.36A and 36B For the two PEG-diacrylates with higher molecular weights, i.e., 1k and 2k Da, the grafting efficiency was relatively low. However, the alkyl peak region (800–1500 cm -1 ), confirming the successful grafting of PEG-diacrylate. Blind sensory evaluation showed that the locks grafted with PEG-DA 2k felt smoother, softer and more shaped than locks grafted with lower molecular weight PEG-diacrylate. This is consistent with the sensory results on locks grafted with PEG-diacrylate using the simultaneous grafting method. The sensory benefit of grafting with PEG-DA 2k on bleached locks is clear. Without being bound by any theory, this may be due to the fact that compared to grafting on virgin locks ( Fig.36A and 36B ) compared to bleached hair strands ( Fig.37A and 37B ).

[0515] Grafting of multi-arm PEG-acrylate

[0516] Other multi-arm PEG-acrylates (PEG-AA) with high molecular weights were explored. These included 4-arm PEG-AA with molecular weights of 2k, 5k, and 10k and 8-arm PEG-AA with molecular weights of 5k and 20k. For all experiments, the monomer to thiol ratio remained the same as PEG-DA 700 and 2k (0.38:1). Unfortunately, no grafting of any multi-arm PEG-AA was detected by FTIR. However, 4-arm PEG-AA 5k consistently showed preferred organoleptic properties in both wet and dry states. The organoleptic properties using 4-arm PEG-AA 5k indicated that some grafting occurred.

[0517] Table 16: Screening of exemplary large multi-arm PEG-acrylates by semi-simultaneous grafting.

[0518]

[0519] Example 2 - Covalent Bonding Analysis

[0520] Fourier Transform Infrared (FTIR) Spectroscopy

[0521] About 1730cm -1 The presence of carboxylic acid ester stretching peaks at about 1407, 1295, 985 or 810 cm-1 was used to qualitatively detect the presence of grafted vinyl acrylate polymer. -1 The presence of this peak without any accompanying "ene" peak excludes the presence of adsorbed (not covalently bound) monomer. 17,18 The carboxylate stretching peak also remains intact after washing. Fig.38 The FTIR spectrum of hair grafted with isodecyl acrylate (solid line) is shown compared to virgin hair (dashed line). The FTIR spectrum of the grafted hair is at 1723 cm -1 The spectrum does not have any stretching peaks (at about 1407, 1295, 985 or 810 cm) indicative of unreacted acrylate. -1 The hydrophobic vinyl ether does not contain a characteristic stretching peak that can be assessed via FTIR in the presence of hair.

[0522] Gravimetric analysis

[0523] To further confirm and quantify the grafting efficiency, gravimetric analysis was performed. The absolute weight gain of the grafted hair strands was determined for each monomer to thiol ratio ( Fig.39A ) and monomer conversion ( Fig.39B As a control, reduced hair locks were used and treated with a similar washing and drying procedure as the grafted samples. Significant increases in weight gain and monomer conversion efficiency were found for all grafted samples compared to the reduced hair control, further supporting that grafting had occurred.

[0524] Example 3 - Characterization of Keratin-Containing Materials

[0525] Disclosed herein are methods of treating keratin-containing materials to graft monomeric and polymeric materials to the keratin-containing materials.

[0526] Sensory results

[0527] Free radical thiol-ene grafting

[0528] The visual and tactile properties of the hair strands and wig models grafted with hydrophobic acrylates or vinyl ethers were evaluated using a blind sensory test. Overall, the grafting provided a smooth, conditioned feel and good fiber alignment to the hair. In the hair strands, it was found that the tactile and sensory properties became more favorable with increasing weight % of the monomer used for grafting ( Fig.40 ). In these experiments, the monomer dodecyl vinyl ether was grafted to wavy / curly black hair strands in acetone at various concentrations for 1 hour under 365 nm light. Blind evaluation by experienced sensory panelists showed that the strands grafted with higher concentrations of monomer were more preferred. The reduction conditions were 5 wt% ATG, pH 9.5, 5:1 liquid ratio, 15 minutes. Note that the reduced strand control (not shown) was similar to the 5% monomer grafted strands as evaluated by the blind sensory panel. That is, the hair felt more shapely and smooth to the touch after being treated using the disclosed method.

[0529] When grafted onto a wig model head, PEG diacrylate provided noticeable tactile changes, improved fiber alignment, and caused hair straightening compared to untreated hair ( Fig.41 ). When evaluated by a blind sensory panel, the grafted side (left) had favorable tactile properties compared to untreated hair.

[0530] After either restoring or restoring and grafting the hair, the wig model head was curled with a 1" tubular curling iron. According to the sensory panel, the initial curl on the grafted side (right) of the wig model was significantly tighter. According to the sensory panel, the grafted side also showed better curl retention after exposure to 90% relative humidity (RH) and 25°C for 15 minutes. Therefore, the data also show that grafting has a favorable effect on styling ( Fig.42 ).

[0531] Comparison of various grafting methods with native keratin-containing materials

[0532] A blind sensory panel has evaluated the visual and tactile properties of wig models grafted with hexyl acrylate using various grafting methods. Overall, the grafting provided a smooth, conditioned feel to the hair and improved fiber alignment ( Fig.43 ). Fig.43Shown is a wig model with one side reduced and grafted with hexyl acrylate at a 1:30:9 thiol:acrylate:DNPA ratio (left) and one side untreated (right).

[0533] A blind sensory test was used to evaluate the visual and tactile properties of other keratin-containing materials, including fingernails and toenails. The treated keratin-containing materials were compared to native keratin-containing materials.

[0534] Grafting on heat damaged hair

[0535] Heat damaged hair locks (damaged using a styling iron-curling iron) before and after grafting were evaluated by a blind sensory panel. The grafted locks were found to have better sensory properties than ungrafted damaged hair. The grafted locks felt smoother and were easier to comb.

[0536] Grafting with PEG-diacrylate

[0537] In addition to the hexyl acrylate monomers having one acrylate group, diacrylate monomers having two acrylate groups were also explored for grafting. Without being bound by any theory, it is speculated that having two acrylate groups on one monomer will further increase the possibility of bonding with thiol groups and will also improve the mechanical properties of keratin-containing materials.

[0538] For example, the use of diacrylate monomers can make hair stronger, which is very meaningful for damaged hair. As evaluated by a blind sensory panel, hair grafted with PEG diacrylates of different molecular weights was found to have favorable tactile properties. Specifically, the hair felt smooth, strong and well-shaped.

[0539] Glossy band test

[0540] Fig.44 Shown are the gloss properties of hair locks grafted with (a) dodecyl acrylate, (b) octadecyl acrylate, or (c) 3-butyl-7,11-dimethyldodecyl acrylate, compared to hair locks that were reduced only (ungrafted). Blind sensory panelists determined that sample (c) exhibited the best gloss, followed by samples (a) and (b), and then the reduced lock control. It was also found that the particularly high molecular weight branched acrylates provided a noticeable increase in hair gloss ( Fig.44 ).

[0541] Mechanical testing

[0542] Mechanical characterization of keratin-containing material samples was performed on a 100 N load cell (Instron #2519-103). The keratin-containing material samples were mounted on the instrument via modified Instron 2710-101 clamps, which prevented the sample from slipping out of the clamps during testing. The instrument clamp distance was adjusted so that the sample was in neutral extension, as indicated by an instrument force close to zero (+0.01 N). For example, a keratin-containing material sample was mounted on the instrument via a modified Instron 2710-101 clamp ... Single fiber hair samples were evaluated.

[0543] The extension traction test is pre-programmed into the Bluehill Lite software for operating the instrument. The extension traction test is used to measure the stiffness, elasticity and strength of keratin-containing materials by measuring Young's modulus, elongation at break and ultimate tensile strength. Young's modulus is used as a measure of material stiffness, and elongation at break is used as a measure of material flexibility. The sample is mounted on the instrument so that the hair sample is fixed in the instrument fixture. The instrument fixture distance is adjusted so that the sample is in neutral extension, as indicated by the instrument force close to zero (+0.01N). Subsequently, extension is carried out at 20mm / min until the sample is destroyed. The stress-strain data recorded by the instrument during the extension process are exported to Excel, and the reported mechanical properties are calculated in Excel.

[0544] An Excel template is used to automatically extract many parameters from the data generated by the instrument. Young's modulus (YM) is calculated from the slope of the line of the stress-strain curve, between 0.1% and 0.4%. The R square value of the linear fit is higher than 0.98, otherwise the data point is discarded. Elongation at break is determined as the strain at which a sample, such as a hair fiber, breaks. Ultimate stress is calculated as the maximum stress recorded during the experiment. Ultimate tensile strength is the ability of a material to withstand a load that tends to elongate. Ultimate tensile strength is the maximum stress that a material or sample can withstand when pulled before breaking.

[0545] Water absorption test

[0546] First, the hair sample was dried in a dryer for 16 hours. The sample was weighed and placed in a humidity chamber at 90% RH for 15 minutes. The sample was then removed and weighed again.

[0547] Water contact angle

[0548] Water contact angles (CA) were measured using a goniometer (Model 500, Rame-Hart) equipped with an automatic dispenser. The advancing and receding angles were measured by the sessile drop method by depositing a 1 μL drop on the surface, increasing the volume to 4 μL, and finally reducing it. The advancing angle was considered to be the maximum angle observed during the growth of the drop. The receding contact angle was measured based on the drop profile just before the contact area was reduced. Each CA value was averaged from the measurements of four droplets, with an estimated maximum error of 4°. CA was measured using distilled water.

[0549] Differential Scanning Calorimetry

[0550] Differential Scanning Calorimetry (DSC) analysis was performed on both wet and dry hair. For wet DSC, approximately 5-10 mg of hair was weighed into a stainless steel pressure-resistant sample pan and 50 μl of water was added. The pan was then sealed and the sample was allowed to equilibrate overnight before DSC analysis. The sample was then heated from 30°C to 250°C at a heating rate of 5°C / min. For dry DSC, approximately 5-10 mg of hair was weighed into an aluminum sample pan and sealed with a lid. The lid was pierced later to allow moisture to escape during the analysis. The sample was then also heated from 30°C to 250°C at a heating rate of 5°C / min. Using DSC analysis, the denaturation temperature of the hair can be determined. The hair denaturation temperature is typically used to evaluate hair strength and structural integrity. After various chemical treatments such as bleaching, perming or straightening treatments, it will decrease, indicating that the hair is damaged. As expected, the hair denaturation temperature decreased by about 4°C after the bleaching treatment, and further decreased by 10-15°C after commercial treatment, indicating that the hair was greatly damaged ( Fig.60A However, after grafting on bleached hair (damaged hair) and post-treatment with gluconolactone and citric acid, the denaturation temperature returned to the level of untreated hair ( Fig.60A ), showing that hair strength was improved.

[0551] Scanning electron microscopy (SEM)

[0552] In order to investigate the morphological changes on the damaged hair surface before and after grafting, scanning electron microscopy (SEM) analysis was performed. The hair was evaluated after bleaching, after reduction of the bleached hair with ATG, and after simultaneous grafting of the bleached hair with hexyl acrylate in an ATG reduction solution. As expected, the hair was similar to the virgin hair ( Fig.45A and Fig.45B ) compared to bleached ( Fig.45C and Fig.45D ) The hair cuticle seemed to be lifted violently. No obvious difference was found after reduction of bleached hair in 5 wt% ATG reducing solution ( Fig.45E and Fig.45F Significant improvement in the epidermal morphology was observed after simultaneous grafting of hexyl acrylate in the ATG reducing solution ( Figure 45G and Figure 45H ). The epidermis no longer appears to be lifted, and the hair cuticle surface appears smooth, similar to native hair.

[0553] Lowry assay for protein loss

[0554] In order to study the changes in the hair surface before and after grafting, a protein quantification method was used. After applying various chemical treatments such as bleaching, perming or straightening treatments, the hair cuticle layer is damaged, resulting in higher protein losses. In order to quantify this loss before and after grafting, a modified Lowry protein assay was used. The hair fibers were first cut into 1 / 4 inch segments, and then about 250 mg of hair was immersed in 4 mL of water in a scintillation bottle. The vial was then placed on an automatic vortex machine for 4 hours. The supernatant was then collected for each hair sample, diluted with 0.2N NaOH solution at a ratio of 1:1 and left to stand for 30 minutes for solubilization. Then about 200 μL of the solubilized protein solution was added to a 2mL Eppendorf tube and mixed with 1 mL of modified Lowry reagent at 20 second intervals. Three parallel samples were taken for each sample. After about 10 minutes, 100 μL of Folin-Ciocalteu reagent was added to each sample and vortexed. The solution was then allowed to develop for 30 minutes. After 30 minutes, the solution was transferred to a cuvette and its absorbance at about 750 nm was measured using a UV-Vis spectrophotometer. As expected, protein was more easily leached from the hair fiber after bleaching, as indicated by the sharp increase in protein loss from 0.47 mg / g hair for virgin hair to 2.93 mg / g hair for bleached hair. In addition, chemical treatment with commercial products resulted in a further increase in protein loss, while protein loss decreased after grafting and post-treatment with gluconolactone and citric acid, indicating less damage to the hair fiber ( Fig.60B ).

[0555] Example 4 - Grafting with additives

[0556] To further improve the sensory benefits of hair, grafting with various additives was also explored. These include emollients, fatty acids, fatty alcohols, fatty esters, peptides and amino acids. The additive example was performed using the following process: A 5 wt% ammonium thioglycolate reducing solution at a pH of about 9.5 and a liquid ratio of 1.1:1 was applied to the hair strands, followed by the application of PEG-diacrylate 700 at a monomer to thiol ratio of about 0.38:1, with the additive added to the monomer mixture. The treatment was performed for 30 minutes.

[0557] Fatty acids and fatty alcohols

[0558] The types of fatty acids and fatty alcohols screened in this study included oleic acid, linoleic acid, jojoba oil (a mixture of fatty acids), cetyl alcohol, and cetearyl alcohol. Fig.46Grafting in the presence of 2 wt% (relative to the total grafted mixture) of oleic acid, linoleic acid or jojoba oil additive is shown. Grafting efficiency was similar for all three fatty acids. It was noted that all hair locks grafted with fatty acids felt very soft and smooth in the wet state, while the locks grafted with the oleic acid additive showed the most favorable sensory properties in the dry state. Protein loss values ​​were also determined for hair samples treated with or without the fatty acid additive using the Lowry assay. Fig.47 The results showed that the protein loss concentration of the hair strands grafted with linoleic acid or jojoba oil additives was slightly lower than that of the hair strands without the grafted additive or grafted with oleic acid, indicating that linoleic acid or jojoba oil can provide some protection for the hair cuticle during the grafting process. Differential scanning calorimetry (DSC) analysis also showed that the hair samples grafted with linoleic acid additives showed a hair denaturation temperature (T d ), suggesting that linoleic acid may improve the structural integrity of hair to some extent. In summary, the results suggest that the use of fatty acids such as oleic acid or linoleic acid as additives in the grafting process may result in desirable sensory properties or health benefits. In addition to fatty acids, selected fatty alcohols including cetyl alcohol and cetearyl alcohol were also explored. However, no statistically significant benefit was observed.

[0559] Amino Acid Blends and Peptide Blends

[0560] A range of amino acids or peptide mixtures that have been used in the personal care industry are also used as additives in the grafting process. These include: KeraVeg 18 (a blend of plant amino acids), 500 (amino acid blend), Vegetamide 18MEA-NJ (cetearylaminoethyl diethylammonium succinyl hydrolyzed pea protein), Vegetamide18MEA-MR (cetearylaminoethyl diethylammonium hydrolyzed rice protein), KERARICE TM (rice peptides and amino acids), KERATRIX TM (Carob hydrolysate), Promois WK-PD (Hydrolyzed Keratin) and Kera-P LM (low molecular weight plant peptide). Initial screening (Table 17) showed that most amino acid or peptide mixtures did not show any noticeable interference with the grafting efficiency when added to the grafting system at 2 wt % (relative to the total grafting mixture). In addition, almost all amino acid or peptide mixture additions resulted in improved sensory properties. In particular, KERATRIX TM To further optimize KERATRIX TM We further explored the use of 2 wt%, 4 wt% and 5 wt% KERATRIXTM Figure 48 shows that in all three different KERATRIX TM The blind sensory evaluation also showed that the hair strands grafted with KERATRIX 1000 had a significantly higher grafting rate than the hair strands without the additive. TM However, when using different KERATRIX TM There is no discernible difference between the strands of KERATRIX 100 at the concentration. TM concentration.

[0561] Table 17: Screening of exemplary amino acid or peptide mixtures as additives during semi-simultaneous grafting.

[0562]

[0563] Amino Acids and N-Acetyl Amino Acids

[0564] The types of amino acids and N-acetylglycine (Gly), L-alanine (L-Ala), L-serine (L-Ser), L-cysteine ​​(L-Cys), N-acetylglycine (Ac-Gly), N-acetylalanine (Ac-Ala), and N-acetylserine (Ac-Ser) were screened in this study. It was noted that all the hair strands grafted using monomers with amino acids or N-acetylalanine as additives felt very soft and smooth. Fig.49 In the graph, the peak intensity of the grafted sample in the carbonyl peak region was higher than that of the 2× bleached hair as a control, indicating that PEGDA was successfully grafted in the presence of 2 wt % of the following amino acids and N-acetylamoic acid—Gly, L-Ala, L-Ser, L-Cys, Ac-Gly, Ac-Ala, and Ac-Ser—as additives. Based on their peak intensities in the carbonyl peak region, the grafting efficiencies of Gly, L-Ser, L-Cys, and Ac-Gly were slightly higher than those of L-Ala, Ac-Ala, and Ac-Ser.

[0565] Protein loss values ​​for grafted hair samples with and without amino acid and N-acetylamino acid additives were also determined using the Lowry assay. Fig.50 It was shown that certain hair strands, such as those grafted with Ac-Gly, Ac-Ala or Ac-Ser additives, had lower protein loss values ​​compared to untreated hair strands (2× bleached). This suggests that N-acetylamino acid additives such as Ac-Gly, Ac-Ala or Ac-Ser can provide protection to the hair cuticle during the grafting process and prevent subsequent protein loss.

[0566] Because in Fig.50Ac-Gly had the lowest protein loss value and was the smallest in size among all acetylamino acids, so Ac-Gly was selected for dose response studies. 2× bleached brown hair locks were treated by grafting with PEGDA 700 using Ac-Gly as an additive at concentrations of 2 wt%, 4 wt% and 6 wt%. Fig.51 Differential Scanning Calorimetry (DSC) analysis in Figure 2 showed that the hair denaturation temperature (T) of hair samples grafted with Ac-Gly additive at concentrations of 2 wt%, 4 wt% and 6 wt% was significantly lower than that of hair samples grafted with Ac-Gly additive at concentrations of 2 wt%, 4 wt% and 6 wt%. d ) was slightly increased, indicating that Ac-Gly improved the structural integrity of hair. In summary, the results show that the use of amino acids or N-acetylamino acids such as Ac-Gly as additives in the grafting process can bring desirable sensory properties or health benefits.

[0567] Acidifiers and polycarboxylic acids

[0568] Various acidulants and polycarboxylic acids were explored as additional treatments to improve hair strength. The acidulants and polycarboxylic acids explored included gluconolactone, citric acid, tartaric acid, and glutamic acid N,N-diacetic acid. Three different ways of incorporating such treatments into the grafting process were explored: pre-treatment, post-treatment, and as an additive during the grafting process. A mixture of gluconolactone (GC) and citric acid (CA) (mix: GLCA) was used as a model system. Four main parameters were explored for the application of the solutions, such as liquid ratio, reaction time, composition, and pH. The preferred parameters are shown in Table 18.

[0569] Table 18: Preferred parameters for semi-simultaneous grafting with gluconolactone and citric acid treatment

[0570]

[0571] Gluconolactone / citric acid pretreatment

[0572] A pretreatment solution of a mixture of gluconolactone and citric acid was applied to dry hair and left on the hair for a certain period of time and then completely rinsed from the hair. The pretreated locks were then grafted. As observed by FTIR, the grafting performance decreased slightly after 15 minutes and 30 minutes of pretreatment. In addition, only in the case of GLCA pretreatment for 30 minutes followed by grafting, the hair denaturation temperature remained about the same as untreated hair. No statistically significant benefit was observed in terms of hair protein loss after 15 minutes or 30 minutes of pretreatment compared to grafting alone.

[0573] Gluconolactone / citric acid as additive

[0574] The effect of adding gluconolactone, citric acid and mixtures thereof to the monomer solution or to the reducing solution was also explored. When added to the monomer solution, a decrease in grafting efficiency was observed only in the presence of citric acid. Adding citric acid and a mixture of gluconolactone and citric acid to the monomer solution contributed to an increase in the denaturation temperature, while adding gluconolactone did not show any statistically significant benefit. Adding gluconolactone and citric acid to the reducing solution also did not show any statistically significant benefit.

[0575] Gluconolactone / citric acid post-treatment

[0576] Post-processing time

[0577] After the grafting reaction was complete, the post-treatment solution was applied to wet hair (towel dried) and rinsed completely from the hair. The length of time the post-treatment solution was left on the hair was varied between 2 minutes and 1 hour to find the preferred conditions. For these experiments, the concentrations of gluconolactone and citric acid were each kept at 2 wt%. Grafting under all conditions was confirmed by the presence of a chromatogram at 1730 cm in the FTIR spectrum. -1 The presence of the carbonyl peak at 140° and the presence of the -CH peak at 140° are confirmed. All spectra shown are spectra of locks of hair washed thoroughly with sodium laureth sulfate (SLES) solution. Fig.52A , 52B , 53A and 53B, after adding gluconolactone and citric acid post-treatment agents, there is no sacrifice in grafting efficiency, and even a slight increase in further carbonyl peaks. Without being bound by any theory, the further carbonyl peaks may be attributed to the additional carbonyl groups from citric acid ( Fig.52A ).

[0578] Fig.54 represents the denaturation temperature (T) of untreated hair (virgin) and hair after grafting and after post-treatment with gluconolactone and citric acid. d ). It was found that post-treatment times of 2, 5 or 15 minutes produced T values ​​similar to those of untreated hair samples. d , indicating that the hair was not damaged during the grafting and post-treatment with gluconolactone and citric acid. It was found that 2 minutes of post-treatment was sufficient to bring the denaturation temperature to the level of untreated hair, indicating that no damage was caused to the hair samples.

[0579] Fig.55 Protein loss values ​​are presented for untreated hair samples (virgin) and hair samples after semi-simultaneous grafting (SSG) and application of gluconolactone and citric acid (GLCA) post-treatment for various time periods between 15 minutes and 1 hour. No time dependency was found for protein loss, but the addition of GLCA post-treatment significantly reduced protein loss, indicating a healthier hair surface, which prevents leaching of proteins.

[0580] pH

[0581] The natural pH of a mixture of gluconolactone and citric acid is about 2, so a wider pH range was explored. Fig.56A and 56B FTIR spectra of hair samples grafted and after post-treatment with gluconolactone and citric acid at various pH values ​​are shown. As can be seen, minimal changes in grafting efficiency were observed. Additionally, the denaturation temperature for post-treatment at pH 2 was the highest, indicating improved hair strength compared to untreated hair, while post-treatment at pH values ​​of 3.9 and 4.7 showed improved T values ​​compared to untreated hair. d No change, indicating no damage to the hair ( Fig.57 ).

[0582] composition

[0583] Another parameter explored for the gluconolactone and citric acid post-treatment was the composition. The effect of using either gluconolactone alone or citric acid alone was explored. For all experiments, the total concentration of these components was kept at 4 wt %. Fig.58A and 58B As can be seen, no grafting efficiency was sacrificed with the various compositions. Varying the concentrations of gluconolactone and citric acid or using these components alone at a concentration of 4 wt% produced T values ​​similar to that of untreated hair. d No concentration dependence was observed ( Fig.59 ).

[0584] The addition of a gluconolactone and citric acid mixture as a pre-treatment, post-treatment and as an additive was explored. It was found that improvements in hair denaturation temperature and reductions in protein loss were observed, all of which indicate healthier hair conditions, particularly when the GLCA mixture was applied as a post-treatment, In addition, it was found that the post-treatment could be as short as 2 minutes in length and was applicable over a wide pH range (2-4.7).

[0585] The gluconolactone and citric acid mixture was also incorporated into a hair conditioner and used as a post-grafting conditioner treatment. Neither the denaturation temperature nor the protein loss was affected by such incorporation, meaning that GLCA can be easily incorporated into a hair conditioner and improve the overall strength of the hair.

[0586] The use of a mixture of gluconolactone and citric acid as a post-grafting leave-on treatment was also explored. It was found that low concentrations of 1 wt % or 0.5 wt % of gluconolactone and citric acid, respectively, were sufficient to observe improved T d and protein loss benefits. The post-treatment can be left on hair for up to 48 hours and can be easily washed out with shampoo and conditioner.

[0587] Such a gluconolactone and citric acid (GLCA) post-treatment was also found to be particularly beneficial for damaged hair, such as hair damaged by bleaching. It was found that the denaturation temperature after grafting and GLCA post-treatment could be increased to the level of untreated (unbleached virgin) hair and protein loss could be significantly reduced, making the initially severely damaged hair stronger and less porous. Unlike commercial treatments that can make the hair even more damaged (higher protein loss and lower denaturation temperature), grafting followed by a GLCA post-treatment made the hair stronger and healthier ( Fig.60A and 60B ).

[0588] Additional polycarboxylic acid screening

[0589] In addition to gluconolactone and citric acid, the use of other polycarboxylic acids was explored, applied as post-treatment agents after the grafting process. Initial screening included gluconolactone and polycarboxylic acids such as citric acid, tartaric acid, and glutamic acid N,N-diacetic acid. Fig.61A and 61B It can be seen that no sacrifice in grafting efficiency was observed after post-treatment with any of these materials. In addition, post-treatment with gluconolactone or various polycarboxylic acids did not show any sacrifice in grafting efficiency ( Fig.63A and 63B ). Fig.62 and 64 As can be seen, post-treatment including tartaric acid (4 wt % tartaric acid alone or a mixture of gluconolactone and tartaric acid at concentrations of 2 wt % to 2 wt % each) resulted in a decrease in T compared to untreated hair. d Post-treatment with 4% gluconolactone alone and with a mixture of gluconolactone and glutamic acid N,N-diacetic acid resulted in an increase in T d The slight decrease in T was negligible, however, indicating that the hair was not damaged after the grafting and post-treatment process. d This indicates that the hair was not damaged after the grafting and post-treatment process.

[0590] In addition to gluconolactone and citric acid, the use of other polycarboxylic acids such as tartaric acid and glutamic acid N,N-diacetic acid also yielded the desired properties.

[0591] Example 5 - Long-lasting in vitro performance

[0592] The durability of the grafting process was first evaluated on wavy, curly hair tresses. In a semi-simultaneous process, a 5 wt% ammonium thioglycolate reducing solution was applied to the wavy / curly hair tresses at a pH of about 9.5 and a liquid ratio of 1.1:1, followed by the application of PEG-diacrylate 1.5k at a monomer to thiol ratio of about 0.2:1. The grafting treatment was allowed to proceed for 30 minutes. After the tresses were thoroughly rinsed, a 2% gluconolactone and 2% citric acid solution was applied for a post-treatment of 15 minutes. The hair was then blow-dried and flat ironed. The tresses were washed 15 times with shampoo and conditioner to simulate durability over a 1-2 month period after receiving the grafting treatment. As in Fig.65A and 65B As can be seen in the figure, the initial straightening effect is well retained after 15 washes.

[0593] A wig mannequin was subjected to various tests to evaluate the performance of a semi-simultaneous grafting method using a 5 wt% ammonium thioglycolate reducing solution at a pH of about 9.5 and a liquor ratio of 1.1:1, followed by the application of PEG-diacrylate 2k at a monomer to thiol ratio of about 0.04:1. The grafting treatment was carried out for 30 minutes. After the wig mannequin was thoroughly rinsed, a mixture of 2% gluconolactone and 2% citric acid was applied as a post-treatment for 15 minutes. The hair was then blow-dried and flat ironed. Fig.66 It was shown that grafting on wavy / curly wig models resulted in effective straightening and improved fiber alignment. Sensory evaluation also showed that the grafted hair felt smoother, softer and more shaped than untreated hair. Both straightening and sensory benefits were maintained for at least 10 SLES washes ( Fig.66 ).

[0594] Grafting on a straight but curly wig model under the above conditions also produced much straighter, shinier and less curly hair ( Fig.67 ). Sensory evaluation showed that the grafted hair felt softer, smoother and more styled compared to untreated hair. Washing studies showed that hair remained straight, smooth, soft and styled after at least 10 SLES washes.

[0595] Grafting on wavy wig models was also performed to enhance natural curl definition. It was clear that grafting resulted in much less frizz and better curl definition compared to untreated hair ( Fig.68 ). Even after 10 washes with SLES, the curls remained very defined. Sensory evaluation also showed that the grafted hair felt softer, stronger and more defined than untreated hair.

[0596] Fig.69A comparison is shown between a commercial straightening treatment and the grafting method disclosed herein, which includes grafting with PEG-diacrylate molecules and post-treatment with a polycarboxylic acid. The commercial straightening treatment used here is based on an ammonium thioglycolate reducing agent and includes two main steps: a reduction step with ammonium thioglycolate and a neutralization step with a hydrogen peroxide-based solution. The disclosed semi-simultaneous grafting method uses a 5 wt% ammonium thioglycolate reducing solution at a pH of about 9.5 and a liquid ratio of 1.1:1, followed by the application of PEG-diacrylate 2k at a monomer to thiol ratio of about 0.04:1. The grafting treatment was carried out for 30 minutes. After thoroughly rinsing the hair, a post-treatment of 2 wt% gluconolactone and 2 wt% citric acid was applied to the wig model head. It can be seen that the hair after grafting and post-treatment looks straighter and more shiny. In addition, a significantly higher denaturation temperature ( ) was observed after grafting and post-treatment (labeled as LP treatment) compared to the commercially available product. Fig.70A ). Hair treated with commercially available products showed T d The sharp decrease in T indicates severe hair damage. d In addition, lower protein loss (meaning healthier and less porous hair) was observed after grafting and post-treatment (labeled as LP treatment) compared to hair treated with commercial products ( Fig.70B ). The protein loss in hair treated with the commercial product was almost doubled compared to hair treated with grafting and post-treatment.

[0597] Example 6 - Combining Monomers with Commercially Available Reducing Agents

[0598] Typical reducing agent based commercial straightening and perming treatments include two main steps: a reduction step with ammonium thioglycolate and a neutralization step with a hydrogen peroxide based solution. Using commercial treatments available on the market, the option of inserting a grafting monomer mixture into the commercial treatment process was explored. For example, for the commercial straightening and perming treatment, a mixture of PEG-diacrylate 1.5k with a monomer to thiol ratio of about 0.04:1 and 2 wt% N-acetylglycine as an additive was applied immediately after the reduction step. The rest of the commercial treatment process remained unchanged and followed the commercial kit instructions. It was found that there was no sacrifice in straightening or curling (perming) performance after such insertion ( Fig.71 and 72 ). For the straightening treatment, no sacrifice in performance was observed according to a blind sensory panel, as the hair on both sides looked perfectly straight, and the monomer-inserted side had a favorable tactile difference. Additionally, after monomer insertion, the denaturation temperature was not as low as with the commercial treatment alone, such as Fig.73A and 73B This further suggests that the addition of a monomer mix will mitigate the overall damage while still maintaining the final target properties.

[0599] The potential of using gluconolactone and / or polycarboxylic acids as post-treatment agents to replace commercial neutralizers that typically contain hydrogen peroxide was explored. Although hydrogen peroxide treatment is designed to oxidize thiol bonds back to form cystine bonds within the hair, hydrogen peroxide treatment can sometimes lead to severe hair damage in the case of over- or under-oxidation. The thiol groups may be converted to cysteic acid groups, which makes the hair more hydrophilic. On the other hand, the use of GLCA post-treatment showed that the hair became stronger based on an increase in denaturation temperature and a decrease in protein loss - indicating that the hair was less porous. Therefore, the use of GLCA post-treatment is proposed to replace conventional neutralizers. Fig.74 The wig model head before and after treatment is shown, with the left side treated with a commercial reducing agent and a commercial neutralizing agent, and the right side treated with a commercial reducing agent and a GLCA post-treatment. It can be seen that the straightening performance is not sacrificed after the GLCA post-treatment, as both sides look similarly straight. The commercial treatment does result in a lower denaturation temperature ( Fig.75A ), while the denaturation temperature showed a sharp increase when GLCA post-treatment was used. Similarly, protein loss increased after commercial treatment, while protein loss was less when GLCA post-treatment was used ( Fig.75B ). This suggests that post-treatment with GLCA or other polycarboxylic acids can be used as an alternative to conventional H2O2-based neutralizers without sacrificing performance and will mitigate hair loss.

[0600] Example 7 - Long-lasting in vivo performance

[0601] For in vivo subjects, the semi-simultaneous grafting method used a 5 wt% ammonium thioglycolate reducing solution at a pH of about 9.5 and a liquid ratio of 1.1:1, followed by the application of PEG-diacrylate 1.5k at a monomer to thiol ratio of about 0.04:1. The grafting treatment was performed for 30 minutes. After thoroughly rinsing the hair, a post-treatment of 2 wt% gluconolactone and 2 wt% citric acid was applied to the subject's head. The hair was then blow-dried and flat ironed.

[0602] Fig.76A and 76B The performance results after grafting are shown for two subjects with different hair types. In both cases, the grafting method was designed to straighten originally wavy or curly hair. Fig.76A The subjects in had naturally wavy and curly hair, which became very straight and smooth after the grafting treatment. Fig.76BThe subjects in had bleached (damaged) and curly hair, which became straight and smooth after the treatment. It can be seen that after the grafting method, the hair of both subjects looked much straighter, shinier and less frizzy. These subjects represent an example of using the grafting method as a straightening treatment, which can be performed on healthy hair or damaged (bleached) hair.

[0603] Fig.77 The de-frizzing and smoothing properties on a subject with naturally straight, curly hair are shown in Figure 2. After the grafting treatment, the hair looked much shinier, less curly, smoother, and the fibers were well aligned. Similarly, de-frizzing and smoothing properties were achieved on naturally curly hair without changing the natural hair shape ( Fig.78 ). Once again, the hair looked much shinier and less frizzy after the grafting treatment. This further shows how the grafting process can be used as a de-frizzing / smoothing treatment without changing the natural hair shape.

[0604] The durability of the grafting method is shown in Fig.79 Medium. The subject initially had curly, damaged (bleached) hair, and after the grafting the hair became much straighter, smoother, less frizzy and neater. It can be seen that after 6 weeks (about 1.5 months), the straightening properties are still there.

[0605] References cited

[0606] 1.Finlay,AY;Frost,P.;Keith,AD;Snipes,W.An assessment of factorsinfluencing flexibility on human fingernails.Br.J.Dermatol.1980,103,357-365.

[0607] 2.Robbins,CRChemical and Physical Behavior of Human Hair.5thed.2012.

[0608] 3.Kalkbrenner,U.;Koener,H.;Hoecker,H.;Rivett,DEStudies on the composition of the wool cuticle.Proc.8th Int.Wool Text.Res.Conf.,Christchurch,New Zealand.1990,1,398-407.

[0609] 4.Carr,C.M.;Leaver,I.H.;Hughes,A.E.X-ray photoelectron spectroscopicstudy of the wool fiber surface.Textile Res.1986,56,457.

[0610] 5.Breakspear,S.;Smith,J.R.,Luengo,G.Effect of the covalently linkedfatty acid 18-MEA on the nanotribology of hair’s outermostsurface.J.Struct.Biol.2005,149,235-242.

[0611] 6.Torre,C.A.;Bhusham,B.;Yang,J.-Z.;Torgerson,P.M.Nanotribologicaleffects of silicone type,silicone deposition level,and surfactant type onhuman hair using atomic force microscopy.J.Cosmet.Sci.,2006,57,37-56.

[0612] 7.Kuzuhara,A.,Hori,T.Diffusion behaviour of reducing agents intokeratin fibers using microspectrophotometry.J.Appl.Polym.Sci 2004,94,1131-1138.

[0613] 8.Kuzuhara,A.Hori,T.Analysis of heterogeneous reaction betweenreducing agents and keratin fibers using Raman spectroscopy and microspectrophotometry.J.Mol.Struct.2013,1037,85-92.

[0614] 9.Manuszak,M.A.;Borish,E.T.;Wickett,R.R.The kinetics of disulfidebond reduction in hair by ammonium thioglycolate and dithiglycolicacid.J.Soc.Cosmet.Sci.1996,47,49-58.

[0615] 10.Manuszak,M.A.;Borish,E.T.;Wickett,R.R.Reduction of human hair bycysteamine and ammonium thioglycolate:A correlation of amino acid analysisand single-fiber tensile kinetic data.J.Soc.Cosmet.Sci.1996,47,213-227.

[0616] 11.Schumacher,F.F.;Nobles,M.;Ryan,C.P.;Smith,M.E.B.;Tinker,A.;Caddick,S.;Baker,J.R.In situ maleimide bridging of disulfides and a newapproach to protein PEGylation.Bioconjugate Chem.2011,22,132-136.

[0617] 12.Richards,D.A.;Fletcher,S.A.;Nobles,M.;Kossen,H.;Tedaldi,L.;Chudasama;V.;Tinker,A.;Backer,J.R.Photochemically re-bridging disulfide bondsand the discovery of a thiomaleimide mediated photodecarboxylation of C-terminal cysteines.Org.Biomol.Chem.2016,14,455-459.

[0618] 13.Chatani,S.;Nair,D.P.;Bowman,C.N.Relative reactivity andselectivity of vinyl sulfones and acrylates towards the thiol-Michaeladdition reaction and polymerization.Polym.Chem.2013,4,1048-1055.

[0619] 14.Lowe,A.B.;Hoyle,C.E.;Bowman,C.N.Thiol-yne click chemistry:Apowerful and versatile method for materials synthesis.J.Mater.Chem.2010,20,4745-4750.

[0620] 15.Hoyle,C.E.;Bowman,C.N.Thiol-ene click chemistry.Angew.Chem.Int.Ed.2010,49,1540-1573.

[0621] 16.Mather,B.D.;Viswanathan,K.;Miller,K.M.;Long,T.E.Michael additionreactions in macromolecular design for emerging technologies.Prog.Polym.Sci.2006,31,487-531.

[0622] 17.Wickett,R.R.Kinetic studies of hair reduction using a single fibertechnique.J.Soc.Cosmet.Sci.1983,34,301-316.

[0623] 18.Yu,D.;Cai,J.Y.;Church,J.S.;Wang,L.Click chemistry of naturalkeratin fibers for sustained shrink-resist performance.Int.J.Biol.Macromol.2015,78,32-38.

[0624] 19.Tian,W.;Hu,Y.;Wang,W.;Yu,D.Synthesis of a gemini quaternaryammonium salt and its reaction with wool fabric using click chemistry.RSCAdv.2015,5,91932-91936.

[0625] 20.Fernandes,M.;Cavaco-Paulo,A.Protein disulphide isomerise-mediated graftingof cysteine-containing peptides onto over-bleached hair.Biocatal.Biotransfor.2012,30,10-

[0626] 21.Desmet,G.B.;Sabbe,M.K.;D’hooge,R.;Espeel,P.;Celasun,S.;Marin,G.B.;Du Prez,F.E.;Reyniers,M-F.Thiol-Michael addition in polar aprotic solvents:nucleophilic initiation or base catalysts?Polym.Chem.2017,8,1341-1352

[0627] 22.Chan,J.W.;Hoyle,C.E.;Lowe,A.B.;Bowman,M.Nucleophile-initiatedthiol-Michael reactions:effect of organocatalyst,thiol,and ene.Macromolecules2010,43,6381-6388.

[0628] 23. Li, G.-Z.; Randev, RK; Soeriyadi, AH; Rees, G.; Boyer, C.; Tong, Z.; Davis, TP; Becer, CR;

[0629] 24. Evans, T.; Wickett, RRPractical Modern Hair Science. 2012.

[0630] Incorporated by Reference

[0631] The contents of the articles, patents, and patent applications and all other documents and electronically available information mentioned or cited herein are incorporated herein by reference in their entirety to the same extent as if each individual publication was specifically and individually indicated to be incorporated by reference. Applicants reserve the right to physically incorporate into this application any and all materials and information from any such articles, patents, patent applications, or other physical and electronic documents.

[0632] Equivalent

[0633] The present invention has been described broadly and generally herein. A person of ordinary skill in the art will readily appreciate various other measures and / or structures for implementing the functions described herein and / or obtaining the results and / or one or more advantages described herein, and each of such variations and / or modifications is considered to be within the scope of the present invention. More generally, it will be readily understood by those skilled in the art that all parameters, dimensions, materials, and configurations described herein are intended to be examples, and actual parameters, dimensions, materials, and / or configurations will depend on one or more specific applications using the teachings of the present invention. Using only routine experiments, those skilled in the art will recognize or be able to determine many equivalents of the specific embodiments of the present invention described herein. Therefore, it should be understood that the aforementioned embodiments are given only as examples, and within the scope of the accompanying claims and their equivalents, the present invention may be implemented in a manner different from that specifically described and claimed. The present invention is directed to each individual feature, system, product, material, kit, and / or method described herein. In addition, any combination of two or more such features, systems, products, materials, kits, and / or methods is included within the scope of the present invention if such features, systems, products, materials, kits, and / or methods do not contradict each other. In addition, each narrower species and subgeneric grouping falling within the generic disclosure also forms part of the invention. This includes the generic description of the invention, a proviso or negative limitation being an exclusion of any subject matter from the genus, whether or not the omitted material is expressly recited herein.

Claims

1. A semi-simultaneous method for treating a keratin-containing material, the method comprising: i) providing a sample of a keratin-containing material comprising a plurality of disulfide bonds; ii) applying a mixture to the keratin-containing material sample for a period of time, the mixture comprising a reducing agent, thereby producing a reduced keratin-containing material sample, wherein the reduced keratin-containing material sample comprises a plurality of free thiol groups, wherein the reducing agent is selected from ammonium thioglycolate, L-cysteine, glutathione or thiolactic acid; and iii) applying a monomer to said reduced keratin-containing material sample, wherein said monomer is PEG-diacrylate, thereby forming a plurality of covalent bonds between said free thiol groups and said monomer, wherein the reduced keratin-containing material is not rinsed or washed between steps ii) and iii), wherein the weight ratio of the mixture to the sample of keratin-containing material is from 1:10 to 100:1, wherein the method further comprises applying a catalyst to the sample of keratin-containing material, wherein the catalyst is selected from amines, phosphines and free radical initiators, wherein the amount of the catalyst is from 1 mol % to 100 mol % relative to the monomer, wherein the concentration of the reducing agent in the mixture is from 0.1 wt % to 11 wt %, wherein the pH of the mixture is from 5 to 11, and wherein the PEG-diacrylate is selected from PEG-diacrylate 250, PEG-diacrylate 575, PEG-diacrylate 700, PEG-diacrylate 1k, PEG-diacrylate 1.5k, PEG-diacrylate 2k and PEG-diacrylate 6k.

2. A simultaneous method for treating keratin-containing materials, the method comprising: i) providing a sample of a keratin-containing material comprising a plurality of disulfide bonds; and ii) applying a mixture to the sample of keratin-containing material for a period of time, the mixture comprising a reducing agent and a monomer; wherein the monomer is PEG-diacrylate, thereby forming a plurality of free thiol groups, which react with the monomer to form a plurality of covalent bonds between the free thiol groups and the monomer, wherein the reducing agent is selected from ammonium thioglycolate, L-cysteine, glutathione or thiolactic acid, wherein the weight ratio of the mixture to the keratin-containing material sample is from 1:10 to 100:1, wherein the method further comprises applying a catalyst to the keratin-containing material sample, wherein the catalyst is selected from amines, phosphines and free radical initiators, wherein the amount of the catalyst relative to the monomer is from 1 mol % to 100 mol %, wherein the concentration of the reducing agent in the mixture is from 0.1 wt % to 11 wt %, wherein the pH of the mixture is from 5 to 11, and wherein the PEG-diacrylate is selected from PEG-diacrylate 250, PEG-diacrylate 575, PEG-diacrylate 700, PEG-diacrylate 1k, PEG-diacrylate 1.5k, PEG-diacrylate 2k and PEG-diacrylate 6k.

3. The method according to claim 1 or 2, wherein the reducing agent is ammonium thioglycolate.

4. The method according to claim 1 or 2, wherein the concentration of the reducing agent in the mixture is 0.5 wt% to 5 wt%.

5. The method according to claim 1 or 2, wherein the concentration of the reducing agent in the mixture is 1 wt% to 4 wt%.

6. The method according to claim 1 or 2, wherein the concentration of the reducing agent in the mixture is 2.5 wt% to 7 wt%.

7. The method according to claim 1 or 2, wherein the concentration of the reducing agent in the mixture is 2.5 wt%.

8. The method according to claim 1 or 2, wherein the concentration of the reducing agent in the mixture is 5 wt%.

9. The method of claim 1 or 2, wherein the ratio is 5:

1.

10. The method of claim 1 or 2, wherein the ratio is 5:10 to 1.5:

1.

11. The method of claim 10, wherein the ratio is 1.1:

1.

12. The method of claim 1 or 2, wherein the mixture is applied for 1 hour to 12 hours.

13. The method of claim 1 or 2, wherein the mixture is applied for 30 seconds to 60 minutes.

14. The method of claim 13, wherein the mixture is applied for 1 minute to 30 minutes.

15. The method of claim 14, wherein the mixture is applied for 30 minutes.

16. The method of claim 14, wherein the mixture is applied for 15 minutes.

17. The method of claim 1, wherein the monomer is applied to the keratin-containing material within 30 minutes of applying the mixture to the keratin-containing material sample.

18. The method of claim 17, wherein the monomer is applied to the sample of keratin-containing material within 15 minutes of applying the mixture to the sample of keratin-containing material.

19. The method of claim 18, wherein the monomer is applied to the sample of keratin-containing material within 10 minutes of applying the mixture to the sample of keratin-containing material.

20. The method of claim 19, wherein the monomer is applied to the sample of keratin-containing material within 5 minutes of applying the mixture to the sample of keratin-containing material.

21. The method of claim 20, wherein the monomer is applied to the sample of keratin-containing material within 1 minute of applying the mixture to the sample of keratin-containing material.

22. The method of claim 1, wherein the monomer is applied for 30 seconds to 60 minutes.

23. The method of claim 22, wherein the monomer is applied for 1 minute to 30 minutes.

24. The method of claim 23, wherein the monomer is applied for 15 minutes.

25. The method of claim 1 or 2, wherein the mixture further comprises a buffer solution.

26. The method according to claim 25, wherein the buffer solution is selected from the group consisting of phosphate, imidazole-HCl, 4-morpholineethanesulfonic acid; bis(2-hydroxyethyl)-amino-tri(hydroxymethyl)methane; N-(2-acetamido)iminodiacetic acid; N-(2-acetamido)-2-aminoethanesulfonic acid; 1,4-piperazinediethanesulfonic acid; 3-morpholino-2-hydroxypropanesulfonic acid; 1,3-bis[tri(hydroxymethyl)methyl-amino]propane; N,N-bis(2-hydroxyethyl)-2-aminoethanesulfonic acid; 4-morpholinepropanesulfonic acid; 2-[(2-hydroxy-1,1-bis(hydroxymethyl)ethyl)-amino]ethanesulfonic acid; 4-(2-hydroxyethyl)piperazine-1-ethanesulfonic acid; 3-(N,N-bis[2-hydroxyethyl]amino)-2-hydroxypropanesulfonic acid; 4-(N-morpholino)butanesulfonic acid; 2-hydroxy-3- [Tris(hydroxymethyl)methylamino]-1-propanesulfonic acid; tris(hydroxymethyl)aminomethane; piperazine-N,N′-bis(2-hydroxypropanesulfonic acid); 4-(2-hydroxyethyl)-1-piperazinepropanesulfonic acid; N-[tris(hydroxymethyl)methyl]glycine; diglycine; N,N-bis(2-hydroxyethyl)-glycine; N-(2-hydroxyethyl)piperazine-N′-(4-butanesulfonic acid); N-[tris(hydroxymethyl)-methyl]-3-aminopropanesulfonic acid; N-(1,1-dimethyl-2-hydroxyethyl)-3-amino-2-hydroxypropanesulfonic acid; 2-(cyclohexylamino)-ethanesulfonic acid; 3-(cyclohexylamino)-2-hydroxy-1-propanesulfonic acid; 2-amino-2-methyl-2-propanol; sodium carbonate-sodium bicarbonate; 3-(cyclohexylamino)-1-propanesulfonic acid; and 4-(cyclohexylamino)-1-butanesulfonic acid.

27. The method of claim 1 or 2, wherein the pH of the mixture is 7 to 11.

28. The method of claim 27, wherein the pH of the mixture is 7.5 to 10.

5.

29. The method of claim 28, wherein the pH of the mixture is 9.

5.

30. The method of claim 1 or 2, wherein the PEG-diacrylate is PEG-diacrylate 1.5k.

31. The method of claim 1 or 2, wherein the molar ratio of the monomer to the free thiol groups is from 0.001:1 to 2.5:

1.

32. The method of claim 31 , wherein the molar ratio of the monomer to the free thiol groups is from 0.2:1 to 0.6:

1.

33. The method of claim 32, wherein the molar ratio of the monomer to the free thiol groups is 0.38:

1.

34. The method of claim 31 , wherein the molar ratio of the monomer to the free thiol groups is from 0.02:1 to 0.06:

1.

35. The method of claim 34, wherein the molar ratio of the monomer to the free thiol groups is 0.04:

1.

36. The method of claim 1, wherein the method comprises: i) providing a sample of a keratin-containing material comprising a plurality of disulfide bonds; ii) applying a mixture to the keratin-containing material sample for a period of time, the mixture comprising a reducing agent at a concentration of 2.5 wt% to 7 wt% thereby producing a reduced keratin-containing material sample, wherein the reduced keratin-containing material sample comprises a plurality of free thiol groups; and iii) applying a monomer to said reduced keratin-containing material sample, wherein said monomer is PEG-diacrylate, thereby forming a plurality of covalent bonds between said free thiol groups and said monomer, The reduced keratin-containing material is not rinsed or washed between steps ii) and iii).

37. The method of claim 2, wherein the method comprises: i) providing a sample of a keratin-containing material comprising a plurality of disulfide bonds; and ii) applying a mixture to the keratin-containing material sample for a period of time, the mixture comprising a reducing agent and a monomer, the reducing agent concentration being between 2.5 wt% and 7 wt%; wherein the monomer is PEG-diacrylate, thereby forming a plurality of free thiol groups, which react with the monomer to form a plurality of covalent bonds between the free thiol groups and the monomer.

38. The method of claim 36 or 37, wherein the reducing agent is ammonium thioglycolate.

39. The method of claim 38, wherein the mixture comprises the reducing agent at a concentration of 5% by weight.

40. The method of claim 36 or 37, wherein the PEG-diacrylate is PEG-diacrylate 1.5k or PEG-diacrylate 2k.

41. The method of claim 1 or 2, wherein the catalyst is an amine.

42. The method of claim 41, wherein the catalyst is a primary or secondary amine.

43. The method of claim 41, wherein the amine is selected from N,N-diisopropylethylamine, N-ethyldiisopropylamine, di-n-propylamine, trimethylamine, triethylamine, ethanolamine, diethanolamine, and triethanolamine.

44. The method of claim 41, wherein the amine is trimethylamine.

45. The process of claim 1 or 2, wherein the catalyst is a phosphine.

46. ​​The process of claim 45, wherein the catalyst is a tertiary phosphine.

47. The method of claim 45, wherein the phosphine is selected from dimethylphenylphosphine, diethylphenylphosphine, methyldiphenylphosphine, ethyldiphenylphosphine, trimethylphosphine, tripropylphosphine, triphenylphosphine, tri(o-tolyl)phosphine, tri(p-tolyl)phosphine, tri(2,4,6-trimethylphenyl)phosphine, tri(3,5-dimethylphenyl)phosphine, dicyclohexyl-(2,6-diisopropylphenyl)phosphine, and tri(hydroxymethyl)phosphine.

48. The method of claim 47, wherein the phosphine is dimethylphenylphosphine.

49. The method according to claim 1 or 2, wherein the amount of the catalyst is 10 mol% to 60 mol% relative to the monomer.

50. The method of claim 49, wherein the amount of the catalyst is 20 mol% to 50 mol% relative to the monomer.

51. The method of claim 50, wherein the amount of the catalyst is 40 mol% relative to the monomer.

52. The method of claim 1 or 2, wherein the catalyst is a free radical initiator.

53. The method of claim 52, wherein the free radical initiator is selected from peroxides, azo compounds, photoinitiators.

54. The method of claim 53, wherein the free radical initiator is a peroxide.

55. The method of claim 54, wherein the peroxide is selected from the group consisting of hydrogen peroxide, t-butyl hydroperoxide, t-butyl peracetate, cumene hydroperoxide, dicumyl peroxide, benzoyl peroxide, and t-butyl peroxide.

56. The method of claim 55, wherein the peroxide is hydrogen peroxide.

57. The method of claim 53, wherein the free radical initiator is an azo compound.

58. The method of claim 57, wherein the azo compound is selected from 4,4'-azobis(4-cyanovaleric acid), 1,1'-azobis(cyclohexanecarbonitrile), 2,2'-azobis(2-methylpropylamidine) dihydrochloride and 2,2'-azobis(2-methylpropionitrile).

59. The method of claim 53, wherein the free radical initiator is a photoinitiator.

60. The method of claim 59, wherein the photoinitiator is an aryl ketone.

61. The method of claim 59, wherein the photoinitiator is selected from the group consisting of acetophenone; anisole; anthraquinone; anthraquinone-2-sulfonic acid; benzil; benzoin; benzoin ethyl ether; benzoin isobutyl ether; benzoin methyl ether; benzophenone; 3,3′,4,4′-benzophenonetetracarboxylic acid dianhydride; 4-benzoylbiphenyl; 2-benzyl-2-(dimethylamino)-4′-morpholinobutylphenone; 4,4′-bis(diethylamino)benzophenone; 4,4′-bis(dimethylamino)benzophenone; camphorquinone; 2-chlorothioxanthen-2-one; dibenzosuberenone; 2,2′-diethoxyacetophenone; 4,4′-dihydroxybenzophenone; 2,2′-dimethoxy- 2-phenylacetophenone; 4-(dimethylamino)benzophenone; 4,4'-dimethylbenzil; 2,5-dimethylbenzophenone; 3,4-dimethylbenzophenone; 2-hydroxy-2-methylacetophenone; 4'-ethoxyacetophenone; 2-ethylanthraquinone; 3'-hydroxyacetophenone; 4'-hydroxyacetophenone; 3-hydroxyacetophenone; 4-hydroxyacetophenone; 1-hydroxycyclohexylphenyl ketone; 2-methylbenzophenone; 3-methylbenzophenone; methylbenzoylformate; 2-methyl-4'-(methylthio)2-morpholinoacetophenone; phenanthrenequinone; 4'-phenoxyacetophenone; thioxanthen-9-one; and diphenyl(2,4,6-trimethyl-benzoyl)phosphine oxide.

62. The method of claim 61, wherein the photoinitiator is 2,2'-diethoxyacetophenone.

63. The method of claim 1 or 2, wherein the method further comprises applying an additive to the keratin-containing material sample for a period of time between step i) and step ii).

64. The method of claim 1 or 2, wherein the mixture further comprises an additive.

65. The method of claim 1 or 2, wherein the method further comprises a post-treatment comprising applying an additive to the keratin-containing material sample for a period of time.

66. The method of claim 65, wherein the additive is selected from the group consisting of fatty acids, fatty alcohols, fatty acid esters, amino acid mixtures, peptide mixtures, acidulants, or mixtures thereof.

67. The method of claim 66, wherein the additive is a fatty acid, a fatty alcohol, a fatty acid ester, or a mixture thereof.

68. The method of claim 67, wherein the fatty acid, the fatty alcohol or the fatty acid ester is selected from butyric acid, caproic acid, caprylic acid, capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, arachidic acid, behenic acid, lignoceric acid, cerotic acid, myristoleic acid, palmitoleic acid, cis-6-hexadecenoic acid, oleic acid, elaidic acid, vaccenic acid, linoleic acid, trans-linoleic acid, linolenic acid, arachidonic acid, eicosapentaenoic acid, erucic acid, docosahexaenoic acid, argan oil, coconut oil, jojoba oil, olive oil, palm oil, octanol, n-nonanol, decanol, undecanol, lauryl alcohol, tridecanol, meat oil, Myristyl alcohol, pentadecanol, cetyl alcohol, palmitoleyl alcohol, heptadecanol, stearyl alcohol, oleyl alcohol, nonadecanol, arachidyl alcohol, heneicosyl alcohol, behenyl alcohol, erucyl alcohol, lignocerol, ceryl alcohol, ascorbyl palmitate, ascorbyl stearate, cetyl myristoleate, cetyl palmitate, diglyceryl, ethyl caprate, ethyl macadamia oleate, ethyl caprylate, ethyl palmitate, ethylhexyl palmitate, glyceryl monostearate, glyceryl hydroxystearate, glycol distearate, glycol stearate, glyceryl monolaurate, isopropyl palmitate, monoglyceride, 2-oleoylglycerol, and mixtures thereof.

69. The method of claim 67, wherein the fatty acid is selected from the group consisting of oleic acid, linoleic acid, jojoba oil, and mixtures thereof.

70. The method of claim 66, wherein the additive is an amino acid mixture or a peptide mixture.

71. The method of claim 70, wherein the additive comprises an amino acid mixture selected from the group consisting of glycine, L-alanine, L-serine, L-cysteine, N-acetylglycine, N-acetylalanine, and N-acetylserine.

72. The method of claim 70, wherein the additive comprises an amino acid mixture or a peptide mixture selected from the group consisting of: KeraVeg 18, 500、Vegetamide 18MEA-NJ、Vegetamide18MEA-MR、KERARICE TM 、KERATRIX TM , Promois WK-PD and Kera-P LM.

73. The method of claim 66, wherein the acidulant is a polycarboxylic acid.

74. The method of claim 66, wherein the additive comprises an acidulant selected from the group consisting of disuronic acid, azelaic acid, citric acid, ethylenediaminetetraacetic acid, ethylenediamine-N,N'-disuccinic acid, gluconolactone, glutamic acid N,N-diacetic acid, lactic acid, methylglycine diacetic acid, tartaric acid, tartronic acid, gluconic acid, succinic acid, itaconic acid, acetic acid, malonic acid, malic acid, 1,2,3,4-butanetetracarboxylic acid, and mixtures thereof.

75. The method of claim 73, wherein the additive comprises citric acid and gluconolactone.

76. The method of claim 66, wherein the concentration of the additive is 0.1 wt% to 15 wt%.

77. The method of claim 76, wherein the concentration of the additive is 0.1 wt% to 5 wt%.

78. The method of claim 1 or 2, wherein the mixture further comprises a solvent.

79. The method of claim 78, wherein the solvent comprises dimethyl sulfoxide, water, acetone, a buffer, or a mixture thereof.

80. The method of claim 79, wherein the solvent comprises water.

81. The method of claim 80, wherein the solvent is water.

82. The method of claim 1 or 2, wherein the keratin-containing material is eyebrows or eyelashes.

83. The method of claim 1 or 2, wherein the keratin-containing material is hair.

84. The method of claim 1 or 2, wherein the keratin-containing material is a fingernail or a toenail.

Citation Information

Patent Citations

  • Methods for fixing hair and skin

    CN105431128A

  • Treatment of keratinous substrates

    GB1311902A